Temperature profiles under the ceiling of subway train inside a tunnel with longitudinal ventilation - Zhenkun Wu; Min Peng; Xiaolei Zhang; Xuyao Qi; Wenxuan Miao; Ding Li; Dongzi Qin (Tunnelling and Underground Space Technology, 2026)

Prevalence of Klebsiella pneumoniae in raw milk and biocontrol potential of phage vB_Kpn_18-1 - Ting Qin; Xinyan Yao; Dai Peng; Chaoxiang Jia; Linlin Huang; Yingqian Han; Yanbin Yang; Yang Liu; Guoyu Yang; Juan Geng; Yueying Wang; Heping Li (International Dairy Journal, 2026)

Real-world impacts of SCR deterioration on NOx emissions from China VI heavy-duty diesel vehicles: Insights from PEMS-based urea mass fraction deterioration tests - Yunpeng Li; Xin Lou; Tao Li; Lanlin Qin; Yingwen Yang; Jinzhu Cao; Dan Zhou; Chaojie Fan; Yong Peng (Fuel, 2026)

Late Holocene human activity and vegetation dynamics in the mountains of southern China - Weihe Ren; Yinglin Jiang; Lupeng Yu; Xiangqi Zhang; Qing Peng; Zhiqing Li; Guitian Yi; Chen Liang; Quan Li; Feng Qin (Global and Planetary Change, 2026)

High-degree-of-freedom shape optimization of bridge main girder sections based on deep reinforcement learning: A co-design approach for static wind load and sectional stiffness - Ke Li; Qinze Luo; Haoyu Peng; Yu Qin; Zengshun Chen; Genshen Fang (Engineering Structures, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Mechanisms and modeling of rock–ice interface shearing at low temperature: Experimental insights and strength prediction based on surface morphology - Ye Li; Xuanmei Fan; Qing Pan; Wensong Wang; Shaochi Peng; Yuheng Qin; Jie Tan (Cold Regions Science and Technology, 2026)

A novel data - driven prediction method for frozen soil unconfined compressive strength considering uncertainty: Partial Bayesian Neural Network - Jin-peng Xin; Jia-ting Wang; Hong-xin Reng; Qin-long Liu; Yuan-en Pang; Xu Li (Bulletin of Engineering Geology and the Environment, 2026)

Duplication and divergence: Two new Dmrt1 gene paralogs identified in autotetraploid Carassius auratus - Qian Xiao; Qingwen Xiao; Xu Huang; Yanlin Fu; Yuhan Yang; Chongqing Wang; Xiaowei Xu; Xidan Xu; Kun Zhang; Yue Zhou; Jinhai Bai; Zhengkun Liu; et al. (Aquaculture, 2026)

Genome-wide identification of the GIF gene family in Zanthoxylum armatum and functional characterization of ZaGIF5 in plant growth and drought tolerance - Qingqing Zhang; Haibo Lan; Chaoting Lang; Jin Qin; Yang Yu; Gaolin Peng; Jianrong Li; Xiaofang Zeng (Plant Science, 2026)

Fusicoccane glycosides from the endophytic fungus Talaromyces sp. DC-26 - Peng Zhou; Jingwen Yu; Xueying Deng; Jinyan Cai; Wenya Feng; Junjun Liu; Qin Li; Chong Dai; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Cavity-assisted multi-interface heat management in a hollow aerogel evaporator for efficient and salt-resistant solar evaporation - Long Peng; Haifeng Zhang; Tianxiang Zhou; Mingyu Wang; Zhijian Li; Xiangxin Hou; Danyan Qin; Yi E; Xianbao Wang; Liangyou Lin (Journal of Environmental Chemical Engineering, 2026)

Zero-valent Fe reshapes microbial and viral communities, regulating arsenic bioavailability reduction in composting: Metagenomic and metaproteomic insights - Guangsheng Qin; Xiaolin Lu; Qiqiang Zhang; Yaling Peng; Linghu Zeng; Rongchun Huang; Yanan Luo; Shengfei Yan; Hui Liang; Zhengzhun Tan; Weijun Pan; Shasha Liang; et al. (Journal of Environmental Chemical Engineering, 2026)

Lipidomic and physicochemical insights into thermal processing-induced changes in dried whole egg-dofu - Yunxiao Xie; Jiayao Peng; Yanyin Li; Yan Chen; Guo Chen; Renyi Qin; Jinqiu Wang; Gan Hu; Fang Geng (Food Bioscience, 2026)

“Tensile strain + X” multimodal sensors: Decoupling, anti-interference, and applications - Siyu Yin; Jinhui Wang; Yuyang Xiong; Yingjie Liu; Lanquan Peng; Jiarun Lin; Jiaqi Du; Hailiu Qin; Bo Wang; Mufang Li; Dong Wang (Chemical Engineering Journal, 2026)

Discriminating global ore deposit genetic types using chalcopyrite trace elements: Insights from interpretable machine learning - Hong-Kai Li; Ming-Yu Cao; Ben Qin; Peng-Fei Wang; Le Wang (Chemical Geology, 2026)

Synergistic effects of biomass sources and nitrogen doping on tuning biochar properties for efficient direct air capture of CO2 - Xuanxuan Li; Xiangping Li; Qing Liu; Caixia Zhang; Yifei Yu; Thilini Udayangani Ariyadasa; Pemaththu Hewa Viraj Nimarshana; Yaqing Zhang; Tiantian Jiao; Xizhuang Qin; Peng Liang (Biomass and Bioenergy, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Decoupling of abundance and activity: Low-abundance comammox contributes substantially to ammonia oxidation in N-fertilized paddy soils - Yi-Xuan Zhang; Wen-Jing Qin; Ran Jiang; Peng Li; Man-Young Jung; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Chlorine dioxide suppresses Aeromonas through thiol oxidation and modulates hepatic redox–immune responses in Aeromonas salmonicida-infected rainbow trout (Oncorhynchus mykiss) - Baorui Cao; Yan Qin; Tianqing Huan; Junran Tan; Enhui Liu; Wei Gu; Gaochao Wang; Kaibo Ge; Yunchao Sun; Datian Li; Peng Fan; Min Liu; et al. (Fish & Shellfish Immunology, 2026)

Corrigendum to “Genetic determinants of cell- and egg-preferred replication in H3N2 canine influenza virus” [Vet. Microbiol. 319 (2026) 111085] - Rang Wang; Yaohui Zhu; Min Zhu; Xiaolong Li; Huabo Zhou; Linying Peng; Shiqi Li; Haodong Zhang; Shanshan Dong; Yifeng Qin; Kang Ouyang; Yeshi Yin; et al. (Veterinary Microbiology, 2026)

A fully human antibody A140 neutralizes abrin toxin via lysosomal intracellular mechanisms, confers potent protection in vitro and in vivo, and reverses transcriptomic dysregulation with a Favorable safety profile - Feng Qin; Shi-You Chen; Peng Lin; Bin Wang; Xin Fu; Jian-Li Jiang; Hong-Yong Cui; Shi-Jie Wang (Toxicology and Applied Pharmacology, 2026)

Apatite fingerprints the magmatic-hydrothermal processes of the Wajilitag alkaline‑carbonatite complex, NW China - Li-Peng Qin; Wu-Bin Yang; Guo-Feng Xu; Pan Qu; He-Cai Niu (Lithos, 2026)

Transformation dynamics and controlling factors of dissolved organic matter along a groundwater–river–reservoir continuum in a subtropical karst region - Wen Lai; Xinlu Su; Jia Qin; Peng Chen; Jing Xiao; Qiaoqiao Huan; Tao Zhang; Jianhong Li; Hui Yang; Junbing Pu (Journal of Hydrology, 2026)

Dietary patterns reshape organ-specific biodistribution and toxicity upon exposure to polystyrene nanoplastics: Role of ROS-mediated intestinal senescence - Jie Dai; Tao Wu; Xialei Liu; Yijun Dong; Lan He; Peng Li; Jiamiao Qin; Sheng Wen; Lina Zhao (Journal of Hazardous Materials, 2026)

Microbial sulfur metabolism affects methane oxidation efficiency of anaerobic methane oxidation in different medium environments - Xunsen Chen; Peng Huang; Wenwen Huang; Zhenzhen Peng; Shubing Li; Yi Tang; Mengchen Lu; Teng Guo; Fangrong Wei; Jinshao Ye; Huaming Qin; Yan Long (International Biodeterioration & Biodegradation, 2026)

Global geopolitical risk and greenhouse gas emission inequality - Chong Xu; Shiqing Peng; Jianda Li; Zengqiang Qin (Environmental Impact Assessment Review, 2026)

High-throughput prediction of the lowest triplet excitation energies in organic photovoltaic acceptors using physics-guided excess-factor-corrected fragment descriptors - Lei Cheng; Rui-Cheng Qin; Peng Xie; Ming-Yang Li; Yue Ren; Guang-Yan Sun (Chemical Engineering Journal, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Interrogating vascular determinants of repair: Biofabricated constructs for precision intervention in peripheral neuropathies - Mouyuan Sun; Shuangyang Li; Xuankai Fan; Yiqian Xu; Yaxian Luo; Luying Qin; Jingyu Zhang; Zhixu He; Lianjie Peng; Xinyi Feng; Tao Qiu; Tian Zhang; et al. (Chemical Engineering Journal, 2026)

Ultra-fast degradation of sulfonamides by Fe/Cu-LDH functionalized biochar activated peroxymonosulfate: Interfacial catalysis driven multiple reactive oxygen species - Yongfei Ma; Keyi Li; Feifei Zhang; Zhaojun Nie; Shiyu Qin; Haiyang Liu; Yupeng Zhang; Jiayang Xu; Zulin Zhang; Peng Zhao; Hongen Liu (Chemical Engineering Journal, 2026)

Biodegradation potential and genomic characteristics of Trametes versicolor 604–2: a high-efficiency lignocellulolytic strain for corn stover - Xinyue Zhao; Zhong Xiao; Jie Qin; Qian Li; Haoyu Yang; Fude Liu; Tao Du; Bin Zhao; Chenchen Peng (Bioresource Technology Reports, 2026)

Chemical Characteristics, Sources, and Transport Pathways of PM2.5 in a Mid-Altitude Industrial City of the Upper Yellow River Basin - Lin Yi; Juanjuan Qin; Yuanyuan Qin; Yuwei Gao; Jingnan Li; Xiaoying Su; Shuming Zhang; Zhiguo Rao; Jihua Tan; Peng Yi (Water, Air, & Soil Pollution, 2026)

The transcriptional coactivator ZaGIF2 from Zanthoxylum armatum enhances growth and drought tolerance in plants by synergistically activating GRF activity - Haibo Lan; Qingqing Zhang; Chaoting Lang; Jin Qin; Yang Yu; Gaolin Peng; Jianrong Li; Xiaofang Zeng (Planta, 2026)

Interactive Toxic Impacts of Thermal Stress and Residual Chlorine on Growth, Nutritional Composition and Digestive Physiology in Meretrix meretrix - Shuai Han; Sitong Wang; Haopeng Hu; Wenping Yang; Shuo Qin; Peng Gao; Yanming Sui; Yebing Yu; Mei Jiang; Lei Li (Fishes, 2026)
Thermal elevation and residual chlorine pollution are two anthropogenic stressors that co-occur in estuarine waters affected by coastal power plant effluents. A 30-day exposure experiment was established with six treatment combinations comprising three temperatures (27 °C, 28 °C, and 30 °C) and two residual chlorine concentrations (0 mg/L and 0.02 mg/L) on Meretrix meretrix. Sampling was conducted on days 0, 10, 20 and 30 of the trial. The results indicated that elevated temperature (30 °C) significantly suppressed shell height and total body weight, while residual chlorine (0.02 mg/L) exerted time-dependent effects on shell length and width, with a significant interactive effect on shell length only at day 30. Crude lipid content declined with increasing temperature and residual chlorine exposure, whereas moisture and ash contents showed significant two-way interactions at all sampling time points. Intestinal amylase activity was continuously regulated by both stressors, with interactive responses on days 10 and 20, and was significantly suppressed under combined high temperature and residual chlorine stress. Collectively, we infer that combined exposure to elevated temperature and residual chlorine impairs shell growth, muscle biochemical composition and intestinal amylase activity of M. meretrix. Long-term experiments are required to further clarify the joint toxic effects of thermal stress and residual chlorine on the clam species.

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Oncorhynchus mykiss as a Salmonid Functional Genomics Model: A Structured Narrative Review of Genomic Resources, Mucosal Immunity, Disease Resistance, Environmental Stress, and Causal Validation - Zhongquan Jiang; Sijia Wu; Yong Zheng; Di Peng; Siping Li; Yuanhao Ren; Bo Qin; Hanfeng Zheng; Lei Li; Tingting Lin (Fishes, 2026)
Rainbow trout (Oncorhynchus mykiss) is an important cold-water aquaculture species and a tractable salmonid model for functional genomics. Rapid advances in chromosome-level genome assemblies, genetic variation resources, regulatory annotations, tissue and cell models, controlled challenge systems, and genome-editing technologies have established an increasingly integrated framework for linking genomic variation with measurable phenotypes. Evidence from studies of mucosal immunity, disease-resistance genetics, and environmental stress responses indicates that these resources can improve candidate-gene prioritization and mechanistic interpretation across molecular, cellular, tissue, and whole-fish levels. However, differential gene expression, quantitative trait locus and genome-wide association signals, genomic predictions, and cell-type localization remain largely associative and rarely provide direct evidence of causality. Interpretation is further complicated by salmonid-specific whole-genome duplication, because retained paralogues may exhibit tissue-specific divergence, functional redundancy, and compensatory responses. Further progress will require the integration of pangenomics, regulatory annotation, single-cell and spatial analyses, and paralogue-aware functional perturbation in both cell-based and whole-fish systems. Such integration will strengthen causal inference, clarify genotype–phenotype relationships, and support disease-resistant breeding, healthy aquaculture, and environmental risk assessment.

Mediation effects of thyroid hormones in the associations between essential metal elements and anxiety or depression symptoms in the elderly - Juanhua Li; Wenqi Wang; Yang Peng; Ning Qin; Jiemei Li; Ying Wei; Biwen Wang; Huaicai Zeng; Han Li; Lu Cheng (BioMetals, 2026)

EID1 blockade potentiates immunosurveillance against cancer metastasis via FPR1-mediated DC-NK crosstalk - Ziqi Jin; Xiao Zhang; Huijuan Zhang; Siying Qin; Siqi Zhang; Shuqing Zhang; Lin Xia; Peipei Li; Wen Xu; Peng Liu; Liwei Zhao; Ruidong Xue; et al. (Science China Life Sciences, 2026)

Genetic determinants of cell- and egg-preferred replication in H3N2 canine influenza virus - Rang Wang; Yaohui Zhu; Min Zhu; Xiaolong Li; Huabo Zhou; Linying Peng; Shiqi Li; Haodong Zhang; Shanshan Dong; Yifeng Qin; Kang Ouyang; Yeshi Yin; et al. (Veterinary Microbiology, 2026)

Thermal performance analysis of energy tunnel segments in a cross-river double-layer shield tunnel - Huiyuan Wang; Xiaozhao Li; Xueyin Zhu; Xue Wang; Haifeng Qin; Zihao Wang; Lei Zhang; Peng Zhao (Tunnelling and Underground Space Technology, 2026)

A topology-aware direction-adaptive multitask evolutionary algorithm - Yuxin Chen; Lizhong Yao; Rui Li; Pengjie Qin; Peng Jiang; Jun Yi (Swarm and Evolutionary Computation, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Thermal runaway propagation and flame behavior in power bank modules: Effects of stacking orientation and triggering position - Zonghou Huang; Mingpo Wang; Jian Yang; Jia Li; Qingsong Wang; Peng Qin (Process Safety and Environmental Protection, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Microbial carbon pump promotes refractory organic carbon accumulation in karst waters: Coupled responses of bacterial communities and dissolved organic matter under thermal stratification - Jia Qin; Xinlu Su; Yikun Jia; Peng Chen; Qiufang He; Wen Lai; Tao Zhang; Jianhong Li; Junbing Pu (Journal of Hydrology, 2026)

Microplastics impair cadmium adsorption in soils via changes in dissolved organic matter and Fe/Mn oxides - Zhenbo Wang; Peng Zhao; Shuanglong Ma; Linglu Wang; Xiaoyu Li; Mengchan Xie; Wenfeng Guo; Fuqing Sui; Chang Li; Shiyu Qin; Hongen Liu; Haichao Fu (Journal of Hazardous Materials, 2026)

Accelerated degradation of antiviral ribavirin by microalgae fuel cell (MFC), electricity generation and key metabolic process - Junhao Wang; Xinrui Qin; Jiajia Ge; Yongtao Cheng; Kang Li; Jun Liu; Kang Shan; Chuanyue Peng; Wenjing Yan; Juan Wang; Min Zuo; Ying Liu (Journal of Environmental Chemical Engineering, 2026)

Bound polyphenols from seabuckthorn pomace alleviate sleep deprivation-induced cognitive impairment via gut microbiota-driven homovanillic acid-mediated neuroprotection - Jing Peng; Xuyang Qin; Huizhen Yan; Aruzhan Amanbayeva; Xiangyu Han; Xiulian Li; Yang Yang; Xuebo Liu; Ying Lan (Food Research International, 2026)

Towards accurate cultivar-specific yield forecasting with a novel crop and climate fusion framework - Kunhong Li; Zhongbin Yan; Christoph Menz; Andrej Ceglar; Peng Qin; Haibo Pu; Haohui Peng; Jinyue Liao; Lei Tao; Jing Li; Li Xie; Desheng Yang; et al. (Field Crops Research, 2026)

Self-assembly-confined upconversion photogelation enables centimeter-deep curing for rapid deep-organ hemostasis with sustained pain modulation - Qian Chen; Hongyu Wen; Peng Zhang; Xuhui Xu; Hanying Wang; Guizhu Feng; Qiqi Pei; Li Tian; Yuanyuan Cao; Hongwei Qin; Fusheng Luo; Zhaowei Teng; et al. (Chemical Engineering Journal, 2026)

High-performance conductive eutectogel synthesized by carboxymethyl cellulose-enhanced physicochemical dual network for supercapacitors and wearable electronic devices - Yiheng Ruan; Min Peng; Wang Li; Chuanyang Chen; Zuzeng Qin; Tongming Su; Xuan Luo; Xueqiang Tan; Xinling Xie (Carbohydrate Polymers, 2026)

Elucidating the aromatic formation of humus via quorum sensing and redox function of thermophilic microbiota in compost - Xiaolin Lu; Qiqiang Zhang; Yaling Peng; Zeying Liang; Yuting Peng; Xiaorui Zhang; Guixian Liu; Guangsheng Qin; Qunliang Li (Bioresource Technology, 2026)

An Interpretable Machine Learning Model for Predicting the Presence of Talaromycosis in HIV Patients Lacking Skin Lesions - Jiaguang Hu; Wenming He; Qun Tian; Yanqiu Lu; Peng Zhang; Jinyu Qin; Chuan Qin; Ying Wu; Cheng Huang; Xu Li; Luhuai Feng; Linghua Li; et al. (Mycopathologia, 2026)
Introduction The existing predictive models for talaromycosis in people living with HIV without skin lesions are limited by established risk factors and traditional statistical approaches. This study aims to develop an interpretable machine learning(ML) model for predicting the presence of talaromycosis in HIV patients without skin lesions and to validate its clinical applicability. Methods This retrospective multicenter study involved the analysis of electronic medical records from four tertiary hospitals in China, covering the period from 2010 to 2019. The training dataset comprised 1009 HIV patients with opportunistic infections, while external validation was conducted using data from 305 patients at an independent center. From an initial set of 36 variables, twelve key features were selected, including albumin, absolute lymphocyte count, hemoglobin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), AST/ALT ratio, C-reactive protein, white blood cell count, platelet count, peripheral or abdominal lymphadenopathy, CD4 + T-cell count, and age. Five ML algorithms were evaluated using tenfold cross-validation. Model performance was measured using the AUC, ACC, and F1-score. Calibration curves and decision curve analysis (DCA) were employed to assess the model’s reliability and clinical net benefit. The optimal model was subsequently implemented as a web-based tool. Results The Support Vector Machine (SVM) exhibited superior performance compared to other models, achieving an AUC of 0.809 (95% CI 0.778–0.838), an ACC of 0.714, and an F1-score of 0.689. External validation demonstrated enhanced performance metrics, with an AUC of 0.921 (95% CI 0.889–0.951), ACC of 0.853, and an F1-score of 0.819. DCA indicated a significant net clinical benefit across various risk thresholds, and calibration curves showed strong concordance between predicted and observed risks. Conclusion The interpretable SVM model effectively stratifies the risk of talaromycosis in people living with HIV without skin lesions in endemic regions, aligning with WHO recommendations for early diagnosis and treatment of priority fungal pathogens. Its integration into a web-based tool enhances clinical accessibility for early intervention in resource-constrained settings.

The role of the HB-EGF-regulated EGFR-mitophagy axis in maintaining cartilage homeostasis and osteoarthritis - JunHua Wang; ChiShou Mo; Qiang Wang; Jia Qin; Yong Li; WuXun Peng (Journal of Molecular Histology, 2026)

Intensive management shifts litter decomposition from mycorrhizal to root-dominated pathway in a subtropical bamboo plantation - Wenhao Jin; Jiahe Wang; Jiangfei Ge; Xingcong Ma; Qifeng Wu; Shuai Shao; Chenfei Liang; Liyuan Peng; Xiaomin Ma; Yuchuan Fan; Yongfu Li; Junhui Chen; et al. (Applied Soil Ecology, 2026)

Assessing the impact of four tillage methods on soil and water conservation in karst areas of Southwest China: Evidence from a 10-year field study - Quanzhong Sun; Ruyi Zi; Fayong Fang; Bin Yang; Minghai Hong; Yuanze Xu; Lang Peng; Li Qin; Tao Song; Jiaojiao Du; Zhongxian Liu; Zhen Han; et al. (Agriculture, Ecosystems & Environment, 2026)

Warming-induced suppression of CO2 fertilization in high-elevation Qinghai spruce of the northeastern Tibetan Plateau - Yarong Qin; Liang Jiao; Zhengdong Guo; Qian Li; Ruhong Xue; Peng Zhang; Xuge Wang; Kuan Zhang; Le Zhang; Xueya Cai (Agricultural and Forest Meteorology, 2026)

T2T reference genome and population genomic analysis provide insight into enhanced disease resistance in gynogenetic grass carp - Chongqing Wang; Yuchen Jiang; Jinhai Bai; Xu Huang; Xidan Xu; Xiaowei Xu; Kun Zhang; Yue Zhou; Zhengkun Liu; Siyang Li; Enkui Hu; Wanjing Peng; et al. (Aquaculture, 2026)

Whole-Genome Identification of CML in Quinoa and Expression Analysis Under Drought Stress - Gao Lu Rongrong; Xie Yuming; Yang Jie; Zhou Jianlong; Xia Huanyao; Li Hanxue; Wang Xuqin; Bai Yutao; Jiang Guofei; Qin Peng (Journal of Plant Growth Regulation, 2026)

Evolutionary Pattern of Marine Stratocumulus Clouds Inferred from Satellite Snapshot Measurements - Yuan Li; Qi Liu; Zheng Qin; Zhenci Lu; Yanghui Peng; Qun Zheng (Advances in Atmospheric Sciences, 2026)

High glucose-induced mitochondrial fission promotes Müller cell activation via suppression of the Hippo pathway - Bo Li; Xing Wang; Xiao-li Hao; Qin Wang; Bing Xu; Hui Peng; Peng Wang (Molecular and Cellular Biochemistry, 2026)

NS1-A53D enhances HA stability to coordinate viral entry with vRNP export and replication during adaptation of H1N1 canine influenza virus - Min Zhu; Rang Wang; Xiaolong Li; Yefan Zhou; Linying Peng; Pingping Wang; Huabo Zhou; Jianni Huang; Yifeng Qin; Kang Ouyang; Yeshi Yin; Zuzhang Wei; et al. (Veterinary Microbiology, 2026)

Construction and immunogenicity evaluation of avian Escherichia coli-derived bacterial biomimetic vesicles displaying H9 subtype avian influenza virus HA1 protein - Yue Li; Yuji Quan; Keji Quan; Mengqi Lin; Peng Chen; Xiangkai Zhuge; Tao Qin; Sujuan Chen; Yuncong Yin; Daxin Peng (Veterinary Microbiology, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

A novel performance-oriented causal graph-based fault detection and root cause diagnosis integrated framework for complex manufacturing processes - Tie Li; Yuting Zeng; Xin Qin; Xueyi Zhang; Jie Dong; Kaixiang Peng (Process Safety and Environmental Protection, 2026)

Biodegradable nanoplastics pose a greater risk: Polylactic acid exceeds polystyrene in phytotoxicity and bioaccumulation in lettuce - Xiaoyu Li; Chang Li; Peng Zhao; Fuqing Sui; Hongen Liu; Shiyu Qin; Zhenbo Wang; Mengchan Xie; Wenfeng Guo; Haichao Fu (Journal of Hazardous Materials, 2026)

Synergistic cooperation of CoNi alloy nanoparticles with Brønsted acid sites in amorphous silica-alumina catalysts for enhanced nitrobenzene transfer hydrogenation - Zeyu Sun; Xingjin Zhang; An Cai; Lihong Qin; Xiaobin Fan; Wenchao Peng; Jijie Zhang; Yang Li (Fuel, 2026)

Multi-marker UPLC-MS/MS detection of sesame, soybean, and peanut oil adulteration in camellia and olive oils: a high-sensitivity approach for food authenticity - Nan Deng; Hui Wang; Fangping Yin; Xiaobo Hu; Jijun Qin; Feifei Zhong; Ben Li; Wenting Cao; Peng Zhou (Food Chemistry, 2026)

Nε-(carboxymethyl)-L-lysine exacerbates renal lipotoxicity via RAGE/AMPK-mediated renal tubular lipophagy impairment in diabetic mice - Yijun Dong; Peng Li; Jie Dai; Jiamiao Qin; Lan He; Tao Wu; Xialei Liu; Zhenhuan Zhao; Lina Zhao (Food Bioscience, 2026)

Targeting delivery of shikonin via cryo-shocked tumor cells for non-small cell lung cancer treatment - Huanhuan Huang; Hui Ren; Feiye Liu; Wenyue Lv; Mengzhen Xu; Huiheng Feng; Haoli Liu; Dong Chen; Peng Zhao; Hongjun Li; Jing Qin (Chemical Engineering Journal, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Direct recovery of silver and simultaneous purification of silicon from end-of-life photovoltaic modules via a one-step hydrothermal method - Danyan Qin; Kai Zhang; Shihao He; Xian Xie; Jie Liu; Long Peng; Yingzhu Li; Di Wu; Yaokai Zhong; Yun Shen; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2026)

Computational-guided semi-rational design to reprogram phospholipase D into industrially robust enzyme - Xiao-Li Kong; Peng Zhang; Zheng-Qiang Qin; Chang Su; Heng Li; Zhen-Ming Lu; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2026)

Analysis of Putative Key Genes for Agar Synthesis in Gracilaria textorii—Based on Transcriptome Analysis Under Salinity Stress - Feng Qin; Mengge Tu; Zheng Li; Shuangshuang Peng; Xiuyu Zhang; Di Xu; Weizhou Chen; Jinxia Wang; Xiaonan Zang (Journal of Ocean University of China, 2026)

Water-quality responses and management-oriented spatial thresholds in a complex river-estuary continuum - Jiang Wu; Tang Liu; Dian-Bao Li; Li-Juan Zhang; Hua-Peng Qin; Wei-Ling Sun; Nan Xu (Water Research, 2026)

Daidzein attenuates hepatic ischemia/reperfusion injury via HMGB1-TLR4 signaling pathway - Shanglin Li; Xinyue Hu; Xueqiang Yan; Fei Peng; Xinke Qin; Xin Liu; Guangyuan Zhao (Toxicon, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Liquid nitrogen suppression of thermal runaway in 18650 lithium-ion batteries: Coupled internal-external temperature field measurement - Zonghou Huang; Quantao Su; Fuqiang Yang; Jia Li; Qingsong Wang; Peng Qin (Process Safety and Environmental Protection, 2026)

The ZxCNIH4-ZxHKT1;1 module responding to external NaCl orchestrates Na+ partitioning in a xerophyte - Jie Huang; Pei-Qin Li; Tian-Qiong Wang; Wan-Peng Bai; Hu-Jun Li; Jin Ke; Yuan-Zhou Pan; Suo-Min Wang (Plant Science, 2026)

Process design and optimization for resource-efficient recovery of Fe, P, and Ti from a low-grade complex iron ore - Shiteng Qin; Xiaokun Li; Bing Zhao; Peng Gao; Yanjun Li; Zhidong Tang (Minerals Engineering, 2026)

Mechanism elucidation for electrochemical simultaneous detection of multiple electron-rich phytohormones on a portable flexible sensor and virtual visualization - Shiyu Hu; Xiaoli Wang; Fengwei Li; Shumo Zhou; Xiyi Tang; Yi Peng; Le Wu; Qinyi Cao; Shiyi Xia; Yahui Huang; Songbai Zhang; Jifei Yang; et al. (Journal of Hazardous Materials, 2026)

The dual origin of granites from fluid-absent and fluid-fluxed melting of the juvenile lower crust: New constraints from Mo isotopes and phase equilibrium modeling - You-Shan Xia; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Yao Zhou; Zhen-Xin Li; Gang Wen; Lei Qin (Geochimica et Cosmochimica Acta, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

Ecological resilience regulates growth recovery of Picea crassifolia in drought-stressed habitats under climate change - Ruhong Xue; Liang Jiao; Peng Zhang; Xuge Wang; Qian Li; Xin Yuan; Zhengdong Guo; Le Zhang; Yarong Qin; Kuan Zhang (Forest Ecology and Management, 2026)

An active cling film developed from pomelo peel for synergistic preservation of Oncorhynchus mykiss: Utilizing K/Fe enzyme-like materials and natural extracts - Tao Yu; Long Cheng; Yini Zhao; Long Gu; Hangfei Gao; Zicen Liu; Li Huang; Shuyan Bai; Dongli Qin; Peng Wang; Aimin Wang; Haijiao Xie; et al. (Food Packaging and Shelf Life, 2026)

Graphitization of marine kerogen and its effects on nanopores and adsorption performance - Guangming Meng; Xianming Xiao; Haifeng Gai; Yanming Zhao; Yijie Xing; Kun Zhang; Yu Liu; Qin Zhou; Tengfei Li; Wei Liu; Peng Cheng; Ping Gao (Science China Earth Sciences, 2026)

Seismic Description Technology for Deep, Low-Permeability Reservoirs in the Xihu Depression in the East China Sea - Jian Li; Dewen Qin; Yan Zhang; Wei Hu; Weizhe Yu; Qin Li; Lide Peng (Journal of Ocean University of China, 2026)

Montmorillonite-olivine combination for synergistic enhancement of marine diatom growth and particulate organic carbon production - Fucheng Yao; Wei Yan; Lulu Qin; Rongda Yu; Dong Liu; Yanfu Wei; Li Li; Qingcheng Zhang; Peng Yuan (Applied Clay Science, 2026)

GAN-FixMatch: A generative–semi-supervised deep learning framework for small-sample quantitative analysis in near-infrared spectroscopy of agricultural and pharmaceutical materials - Peng Li; Chenglong Qiu; Jinlong Duan; Yao Qin; Mingxing Li; Dandan Zhai; Xile Cheng; Yu Yang (Analytica Chimica Acta, 2026)

Observation‐Constrained Agroecosystem Model Inversion Reveals Continental‐Scale Variation of Winter Wheat Traits - Zhenyu Zhang; Kaiyu Guan; Robert F. Grant; Wang Zhou; Bin Peng; Rongzhu Qin; Tongxi Hu; Senthold Asseng; Jingting Zhang; Ziyi Li; Kimberlee K. Kidwell; Jiaying Zhang (Global Change Biology, 2026)
Understanding how crop trait variability shapes genotype × environment × management (G × E × M) interactions remains a key uncertainty in predicting agricultural performance under a changing climate. Continental‐scale crop models commonly rely on spatially uniform parameters, limiting their ability to represent adaptive variation in phenology, allocation, and yield formation. Here we integrate the mechanistic agroecosystem model Ecosys with a deep learning‐enabled model‐data fusion inversion to infer spatially explicit physiological controls (trait proxies) of U.S. winter wheat directly from observations. By constraining simulations with satellite‐derived photosynthesis and county‐level yield records from 2008 to 2022 across ~1000 winter wheat–producing counties, the inversion recovers coherent patterns of maturity group, reproductive capacity, harvest index, and root–shoot allocation. The optimized simulations reproduce observed carbon uptake and yield variability (gross primary productivity r = 0.76–0.88; phenology bias 90% of yields within ±20% of reports) and reveal distinct physiological profiles that align with the geographic distributions of major winter wheat market classes. The inferred controls explain class‐ and region‐specific climate sensitivities: warmer winters reduce vernalization success in late‐maturing cultivars, while elevated vapor pressure deficit causes strong yield losses in rainfed Hard Red Winter wheat. The results demonstrate that observation‐constrained trait inversion within model–data fusion framework reveals biologically meaningful crop‐class variation, thereby providing a scalable, physiologically grounded framework for diagnosing adaptive diversity and climate vulnerability across agroecosystems.

Association Between Lead Exposure and Anthropometric Indicators in School-aged Children: A Longitudinal Study - Xiangju Wu; Yang Zhou; Linhong Li; Jieying Gao; Rongchang Xiao; Qian Yang; Meng Wu; Siyan Ye; Chengpeng Cui; Peng Lin; Ruifeng Luo; Ge Yan; et al. (Biological Trace Element Research, 2026)

Deciphering programmed cell death for gastric cancer prognosis: AKR1B1 as a key player - Shan-peng Liu; Xiaomin Li; Qin Liu; Shun Xie (Journal of Applied Genetics, 2026)

Isolation of reassortant H5N1 and H5N8 avian influenza viruses from co-infections and their host-dependent replication dynamics - Yuwei Wu; Nuo Xu; Zhifan Li; Zijun Lu; Yurui Dong; Yijie Guo; Ying Bian; Kunlin Li; Chenzhi Huo; Tao Qin; Sujuan Chen; Hui Yang; et al. (Veterinary Microbiology, 2026)

Foliar boron application modulates antioxidant enzymes and gene expression to alleviate Cd toxicity in winter wheat (Triticum aestivum L.) - Mengchan XIE; Yifan FENG; Chaoming MA; Hongen LIU; Zhaojun NIE; Wei GAO; Chang LI; Fuqing SUI; Peng ZHAO; Shiyu QIN (Pedosphere, 2026)

Co-exposure to polystyrene microplastics and perfluorooctanoic acid can exacerbate lipid metabolism disorders and liver damage in adult zebrafish - Sijie Tian; Ruixiang Li; Ya Zeng; Lingfeng Qin; Caicheng Long; Taiping Qing; Peng Zhang; Bo Feng (Journal of Environmental Sciences, 2026)

Robust and interpretable grading of Baijiu base liquor via NIR spectroscopy: A Bagging–Boosting Hybrid Feature Fusion approach - Guiyu Zhang; Kerong Chen; Xianglin Zeng; Peng Yin; Maohan Qin; Shiliao Deng; Kuiting Li (Food Bioscience, 2026)

Direct optical combined measurement of bubble hydrodynamics in transition flow regime of a bubble column utilizing two in-line vision probes with distinct specifications - Qin Li; Peng Zhao; Zepeng Zhao; Jie Chen; Wenxiang Tang; Haoliang Wang; Xiangyang Li; Chao Yang (Chemical Engineering Journal, 2026)

Precursor engineering via multifunctional additive for modulating perovskite crystallization and interface passivation enabled high-performance perovskite solar cells over 26% - Zhenye Liang; Chen Tian; Zhenhuang Su; Te Ji; Zhengwu Liu; Kunming Hou; Yulin Qin; Lianjie Ma; Junxiang Chen; Lingling Guo; Luozhen Jiang; Meng Du; et al. (Chemical Engineering Journal, 2026)

Bidirectional shear-flow preparing lamellar graphene skeletons for tough and conductive nacre-like nanocomposites - Yicong Qin; Gangfeng Cai; Songhan Shi; Haodong Yang; Zihao Deng; Chendong Ge; Peng Li; Chao Gao; Zhen Xu (Chemical Engineering Journal, 2026)

Determinants of the variability of PGPB effects on zinc biofortification and crop yield: a meta-analysis - Hua He; Lu Peng; Jinzhi Liu; Fangchi Yang; Xiu Li; Qin Lan; Xiaoyan Tang; Yanyan Zhang; Bing Li; Changquan Wang; Yingjie Wu (Plant and Soil, 2026)

Genome-wide analysis of HSP70 family in Zygophyllum xanthoxylum and its heat stress response in Arabidopsis - Wan-Peng Bai; Tian-Qiong Wang; Qin Liu; Hu-Jun Li; Li Wei; Suo-Min Wang (Plant Cell Reports, 2026)

Gut microbiota-tryptophan-serotonin axis drives anxiety-like behavior via NLRP3-mediated neuronal pyroptosis in the medial prefrontal cortex - Guiqiang Zhou; Xing Wang; Tongzhou Qin; Ling Guo; Jiajin Lin; Zhaowen Zhang; Peng Gao; Yan Zhou; Wei He; Jing Li; Guirong Ding (Apoptosis, 2026)

Chlorella GY-D12-biochar composite for lead and cadmium removal from wastewater - Sana Irshad; Asad Nawaz; Xiyao Liu; Shiyang Wu; Sajad Ali; Yi Peng; Yixin Wan; Xu Liao; Zunhua Li; Meifeng Wang; Zuodong Qin (Journal of Environmental Chemical Engineering, 2026)

Assembling a complete metabolic pathway enables Escherichia coli to acquire naphthalene bioremediation ability - Bo Wang; Yu Wang; Qin Yang; Lijuan Wang; Jianjie Gao; Jing Xu; Zhenjun Li; Cen Qian; Yongdong Deng; Wenhui Zhang; Yongsheng Tian; Rihe Peng; et al. (Journal of Environmental Chemical Engineering, 2026)

Pre-harvest and post-harvest plant-based food quality evaluation based on near-infrared spectroscopy coupled with multiscale deep ensemble learning - Yu Yang; Yu Zhang; Lanxiang Yu; Pengtao Lv; Yao Qin; Chengxin Cai; Zelong Liu; Dandan Zhai; Peng Li; Nana Zhang (Food Chemistry, 2026)

Efficiency and mechanisms of microbial metabolic regulator addition on carbon and nitrogen retention in biochar-assisted distilled grain waste composting - Shi-Peng Wang; Ting-Ting Wang; Xiu-Fang Li; Min Gou; Song-Tao Wang; Zhao-Yong Sun; Yue-Qin Tang (Bioresource Technology, 2026)

Genome-wide transcription factors identification and transcriptome analysis of root development in Taraxacum kok-saghyz Rodin - Anqi Su; Hao Li; Yuxian Yang; Wenhui Rao; Youyang Qin; YuanPin Zhu; Wenyue Han; Fang Wang; Qing Dong; Haiyang Jiang; Xiaojian Peng (Planta, 2026)

Risk-adaptive planning for power system decarbonization: quantifying internal and external trade-offs based on a dual-triangle framework - Gang Lu; Peng Xia; Jingyun Li; Haitao Chen; Yanming Jin; Qin Wang (Journal of Industrial Ecology, 2026)

In vitro screening and in vivo evaluation of anti-virulence herbal compounds against Streptococcus agalactiae in tilapia (Oreochromis niloticus) - Ming-Li Xiang; Zi-Chen Zhao; Gui-Hua Li; Wei Tang; En-Peng Chen; Shui-Feng Qin; Yan Wang; Heng-Wei Deng; Zhi-Hong Zhong; Yun Sun; Wei-Liang Guo; Yong-Can Zhou (Aquaculture, 2026)

Effects of crop straw and furfural residue on microbial communities and maturation in swine manure composting - Qian Li; Chenchen Peng; Jie Qin; Xinyue Zhao; Dandan Li; Haoyu Yang; Tao Du; Bin Zhao (Process Safety and Environmental Protection, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Investigating the relationship between the crystal structure and catalytic activity of MnO2 nanomaterials for NO oxidation - Jia-Xin Zhang; Wei-Hao Liao; Peng-Song Li; Yuan-Hang Qin; Zhen Chen; Li Yang (Chemical Engineering Journal, 2026)

Enhancing the recognition accuracy of TENG-based vibration sensors through dielectric enhancement strategy - Zitian Ye; Minfeng Pan; Shi Wei; Zhenming Chen; Zhenwei Qin; Peng Li (Chemical Engineering Journal, 2026)

Concurrent stabilization of lattice framework and sodium kinetics at high voltages by heterotopic diffusion doping in P2-type cathode - Peng Wei; Shanshan Lv; Shaoyang Wu; Yuyang Qin; Xiangqun Zhuge; Kang Liang; Qian Zhao; Jianbin Li; Yangyang Huang; Yurong Ren (Chemical Engineering Journal, 2026)

Genome-Wide Identification and Expression Analysis of the TCP Gene Family in Quinoa (Chenopodium quinoa Willd.) - Yutao Bai; Heng Zhang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Rongbo Li; et al. (Journal of Plant Growth Regulation, 2026)

Analysis of drag force, deformation and stress distribution of biofouled flexible nets - Songchen Yu; Ning Wang; Hongde Qin; Peng Li (Aquacultural Engineering, 2026)

Changes in the explanatory power of factors influencing the spatial pattern of vegetation greenness in eastern coastal region of China - Yansong Jin; Xinyue Li; Kai Jin; Fei Wang; Quanli Zong; Chunxia Liu; Peng Qin; Xiuzhi Zhu (Environment, Development and Sustainability, 2026)

Ecological impacts of offshore wind power construction and operation on zooplankton communities in South China sea - Zhenzhen Peng; Mengchen Lu; Wenwen Huang; Yi Tang; Shubing Li; Huaming Qin; Lili Wang; JinShao Ye; Yan Long (Marine Pollution Bulletin, 2026)

An improved autotetraploid fish derived from the hybridization of gynogenetic homologous diploid crucian carp (♀) × autotetraploid carassius auratus (♂) - Yue Zhou; Ling Xiong; Xu Huang; Xi Dan Xu; Chongqing Wang; Xiaowei Xu; Kun Zhang; Jinhai Bai; Zhengkun Liu; Yuchen Jiang; Wanjing Peng; Enkui Hu; et al. (Aquaculture, 2026)

Effects of high-pH saline-alkaline water on tissue structure, osmoregulation, antioxidant capacity, and metabolic activity in mud crab Scylla paramamosain Estampador, 1950 - Yuntao Li; Cunhong Chen; Zihui Li; Jingli Yang; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; et al. (Aquaculture, 2026)

Multiomics approaches identify immunometabolic crosstalk in triploid cyprinid fish after Edwardsiella tarda 1 l-4 infection - Ruo-Xing Yu; Ting Luo; Qin-Yang He; Zi-Rou Zhong; Jie Peng; Yao-Hui Li; Zhuang-Wen Mao; Ming-Zhu Huang; Zi-Le Qin; Xu-Ying Kuang; Zi-Xuan Fang; Jian Li; et al. (Aquaculture, 2026)

Mechanistic insights into the sediment accumulation and fractionation of PAHs: Role of sedimentary organic carbon and an assessment of environmental implications - Weijie Liu; Xinli Xing; Xingchen Liu; Andrew J. Sweetman; Gaigai He; Shibin Qin; Peng Li; Li Liu; Xiaoshui Li; Shihua Qi (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

Transcriptomic analysis of the sprout-suppressive effects of rosemary essential oil on potato tubers - Shutong Wu; Xiangbin Xu; Di Wu; Peng Zhang; Guozheng Qin; Baodong Wei; Jiangkuo Li (Postharvest Biology and Technology, 2026)

Sources and transformations of inorganic and organic carbon in a stratified groundwater-fed reservoir, south China - Xinlu Su; Jia Qin; Wen Lai; Yikun Jia; Peng Chen; Tao Zhang; Jianhong Li; Junbing Pu (Journal of Hydrology, 2026)

Au–enhanced BiOBr/g–C3N4 quasi–2D core–shell S–scheme heterojunction for CO2 photoreduction - Shumei Li; Erhan Qin; Peng Tian; Yuan Teng; Jinghai Yang; Xin Li; Binrong Li; Lili Yang; Maobin Wei (Journal of Environmental Chemical Engineering, 2026)

Trace element geochemistry of magnetite and hematite from the Jinchang porphyry Au-Cu deposit, northeast China: Implications for fluid evolution and cobalt enrichment - Peng-Fei Shan; Ming-Jian Cao; Noreen J. Evans; Le Wang; Yi Li; Yu-Suo Zhao; Ke-Zhang Qin (Journal of Asian Earth Sciences, 2026)

Riverbank line migration dynamics and channel evolution processes along the Tarim River in China - Yun Zhao; Lin Li; Quanli Zong; Kai Jin; Chunxia Liu; Peng Qin; Xiuzhi Zhu (Journal of Arid Environments, 2026)

Unveiling spatiotemporal forest cover patterns breaking the cloud barrier: Annual 30 m mapping in cloud-prone southern China from 2000 to 2020 - Peng Qin; Huabing Huang; Jie Wang; Yunxia Cui; Peimin Chen; Shuang Chen; Yu Xia; Shuai Yuan; Yumei Li; Xiangyu Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

A comprehensive study on pyrolysis behavior and product characteristic of different components in brewer's spent grains - Peng-bo Liu; Shuo Sun; Xue-qin Li; Sheng Huang; You-qing Wu; Zong-yin Li; Xiao Wei; Shi-yong Wu (Fuel, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Crosslinked polymer aerogel with multiple binding sites for efficient uranium separation from uranium-containing wastewater - Yaping Jian; Jiacheng Zhang; Xuewen Cao; Jipeng Li; Qin Peng; Xuefeng Tian; Jianfei Du; Yihui Yuan; Ning Wang (Environmental Research, 2026)

New methodology for the seamless numerical simulation of flow-like landsliding–damming–breaching process: Application to the 2020 Shaziba Landslide, China - Bolin Huang; Zhen Qin; Bin Li; Peng Zhang; Xingchen Dong; Pengcheng Li; Wen Qi (Computers and Geotechnics, 2026)

Defective piezoelectric metal-organic frameworks elicit demethylation for enhanced cancer pyroptosis and immunotherapy - Xun Guo; Chunyan Yuan; Zhengchun Yang; Jiahuan Xu; Pan Li; Qin Zhou; Xiaoting Wang; Liang Chen; Peng Tu (Chemical Engineering Journal, 2026)

Revealing the sodium storage capacity, kinetics, and sodium plating signals of hard carbon - Wei Li; Shini Lin; Yuejing Zeng; Yuan Qin; Honghao Xie; Xing Chen; Jing Zeng; Peng Zhang; Jinbao Zhao (Chemical Engineering Journal, 2026)

Chitosan/β-glucan/cystine multifunctional hydrogel loading retinol liposomes for efficiently treating UV-induced skin damage and aging - Qingle Song; Yuan Wang; Zekai Tan; Hongping Xiang; Qin Liu; Meiting Li; Lanyue Zhang; Peng Shu (Carbohydrate Polymers, 2026)

Research on the influence of train-induced wind on the temperature field of high-speed railway tunnel in cold region in different temperature modes - Weiping Xu; JinHang Qin; KeGuo Sun; Yong Wei; Bing Jiang; Chao Liu; Yangyang Li; Leilei Peng (Cold Regions Science and Technology, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Climate warming and forest expansion significantly enhance China’s forest methane sink - Youbin Deng; Mingxu Li; Xiaoyan Kang; Li Xu; Boming Liang; Jiankun Chen; Lingli Yu; Xuanbo Wang; Xuyang Zhang; Mengze Qin; Changhui Peng; Nianpeng He (Agricultural and Forest Meteorology, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Effect of quorum sensing signal molecular analog 4-hydroxy-5-methyl-3(2H)-furanone on the microbial diversity and flavor characteristics of Sichuan Paocai - Chunhui Deng; Qin Peng; Xia Lin; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Lei Liu; Ziwei Liang; Yu Rao (International Journal of Food Microbiology, 2026)

Hypoxanthine accumulation caused by mutations of Bombyx mori xanthine dehydrogenase triggers female sterility - Wen-qing Lai; Zhan-peng Lu; Qiang Zhang; Zuo-min Shao; Han Gao; Xia Sun; Sheng Qin; Xue-yang Wang; Mu-wang Li (Insect Biochemistry and Molecular Biology, 2026)

Exploration, sequence optimization and inhibition mechanisms of xanthine oxidase inhibitory peptides from chicken hemoglobin - Jun Li; Shiqin Lai; Wen Hu; Jiaxian Liu; Jinming Peng; Dengle Duan; Yan Fan; Qin Wang; Gengsheng Xiao; Ying Zhang; Wenhua Yang (Food Research International, 2026)

Identification, evolutionary and characteristic analysis of apoptosis - related caspase gene family in Tachysurus fulvidraco and their expression profiles under bacterial, parasitic, and viral infections - Peng Tang; Yueping Chen; Tong Yue; Zhangyan Liang; Jianying Yang; Qiao Wang; Yang He; Chuanjie Qin; Zhengyong Wen; Qingchao Shi; Li Zhou; Jun Wang (Fish & Shellfish Immunology, 2026)

Developmental toxicity of functionalized polystyrene microplastics and their inhibitory effects on fin regeneration in zebrafish - Qian Li; Wenjing Cheng; Hongyu Wang; Jun Chen; Yueyun Qin; Ruozhu Sheng; Shaohong Peng; Zaitian Li; Tao Lu; Liwei Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

Process analysis of columnar dangerous rock mass collapse in the Three Gorges Reservoir Area based on 3D MPM - Shulou Cheng; Bolin Huang; Peng Zhang; Qiuwang Li; Xingchen Dong; Panpan Qin (Journal of Mountain Science, 2026)

Organoid chip based automatic system for long-term quantifying ciliary beating under drug intervention - Zixi Li; Zhicheng Huang; Daoyun Wang; Tong Li; Junya Peng; Anlan Zhang; Ruimeng Sun; Xin Wu; Yu Zhang; Naixin Liang; Qin Li; Zewen Wei (Analytica Chimica Acta, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Vegetation and tides regulate the emissions of volatile sulfur compounds from intertidal wetland sediments - Qin‐Dao Li; Pei‐Feng Li; Chun‐Ying Liu; Jiang‐Chen Gong; Jing‐Wen Hu; Qian‐Qian Yang; Gui‐Peng Yang (Limnology and Oceanography, 2026)
Volatile sulfur compounds (VSCs)—carbonyl sulfide (COS), dimethyl sulfide (DMS), and carbon disulfide (CS 2 )—play critical roles in atmospheric chemistry. Nevertheless, quantitative understanding of VSC exchange dynamics in coastal wetland ecosystems remains limited. Here, we quantified the sediment‐air fluxes of these VSCs across vegetated ( Spartina alterniflora and Suaeda glauca ) and unvegetated mudflat habitats via year‐round field observations in a temperate intertidal wetland. We found that S. alterniflora sediments exhibited net emissions of COS (4.61 ± 9.19 nmol m −2 s −1 ), DMS (10.25 ± 12.35 nmol m −2 s −1 ), and CS 2 (5.77 ± 7.29 nmol m −2 s −1 ), while S . glauca and mudflats exhibited variable sink–source dynamics. VSC fluxes from S. alterniflora habitats significantly exceeded those from other zones due to high root sulfate and total sulfur contents, as well as microbial organisms and temperature‐dependent microbial activity related to sulfur metabolism. The DMS flux in S. alterniflora zones decreased by 33–224% after ebb tide compared to before flooding, with principal component analysis identifying phase‐specific controls: pre‐flood fluxes were associated with porewater chemistry (pH, redox potential) and atmosphere (water content, pressure) coupling, while post‐ebb fluxes were governed by ionic gradients (conductivity) and residual moisture (water content). Tidal simulation experiments revealed the joint influences of illumination, water content, and anaerobic processes on VSC production, where anaerobic conditions suppressed DMS and CS 2 formation but enhanced COS emission in the dark. These findings establish that coastal VSC fluxes are regulated by the interplay between macrophyte‐mediated sediment biogeochemistry and tidal pumping. This provides mechanistic insights into wetland sulfur cycle modeling.

Groundwater level prediction in urban karst regions: The comparison of ensemble learning and deep learning models by considering climate conditions - Xiaoqing Song; Ruihan Xiong; Zhenzhu He; Danyuan Luo; Shuyi Li; Ying Wang; Qin Peng; Shilong Yang; Yuxuan Fang; Aiguo Zhou; Xu Guo; Hanxiang Xiong (Urban Climate, 2025)

Ethanol impregnated Ni modified ZSM-5 and its regeneration performance for catalytic pyrolysis of bituminous coal volatiles to prepare light aromatic hydrocarbons - Yingqi Liu; Xuan Qu; Yaqing Zhang; Tiantian Jiao; Xizhuang Qin; Haifeng Zhou; Xiangping Li; Peng Liang (Process Safety and Environmental Protection, 2025)

Construction of BiOBr/BiVO4 S-scheme heterojunction photocatalysts for efficient oxygen evolution from water splitting - Rui Li; Jingjing Peng; Fangxia Xie; Qing Xi; Jilong Qin; Houfen Li; Yawen Wang; Jianxin Liu; Xiaoli Ma; Xiuping Yue (Journal of Environmental Chemical Engineering, 2025)

CO2 mineralization of municipal solid waste incineration ashes in amine solutions: Carbon capture and heavy metal leaching - Yiming Cheng; Changlei Qin; Peng Zhang; Zijian Li; Jie Chen (Journal of Environmental Chemical Engineering, 2025)

Antihypertension study and untargeted serum metabolism analysis of fermented black sesame seed hydrolysate on spontaneously hypertensive rats - Tonghao Du; Shijin Xiong; Yuan Qin; Xiaoyan Xu; Yiming Luo; Huiyu Li; Mingwei Zhao; Tao Wei; Jinqing Huang; Muyan Xiao; Tao Huang; Xiang Wang; et al. (Food Bioscience, 2025)

Unveiling the phytoremediation potential and mechanisms of Phyla canescens in heavy metal-contaminated soils - Xixi Cai; Ruixiang Ou; Jianquan Wu; Dunhai Li; Jianying Li; Chengrong Peng; Jibing Li; Hongjie Qin (Environmental Research, 2025)

Passivation engineering at buried interface enables efficient and stable perovskite solar cells - Zhenye Liang; Zhengwu Liu; Kunming Hou; Yulin Qin; Lianjie Ma; Zhuofan Zhang; Lingling Guo; Luozhen Jiang; Meng Du; Bing Nan; Peng Fan; Yingguo Yang; et al. (Chemical Engineering Journal, 2025)

Study on the Influence of Geological Fault Structure on the Energy Evolution of Rockbursts - Shoujian Peng; Chaolong Qin; Qingfeng Xu; Jiang Xu; Yan Yang; Feng Jiao; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Optical Fiber Sensor Based Transportable Active Seismic Survey System Solution to OSI - Qin Li; Zhaoli Li; Zhifeng Wang; Ye Lang; Hong Liu; Wei Zhao; Chenyu Yi; Jing Yang; Peng Li (Pure and Applied Geophysics, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

Transcriptome profiling reveals the regulatory mechanisms of AsA (ascorbic acid) and flavonoid synthesis and metabolic processes in fruit development of Ribes nigrum L - Xuelin Zhang; Danni Zhang; Weihua Li; Jiachen Li; Shuxian Li; Weixia Zhang; Peng Zhang; Kaojia Cui; Junwei Huo; Huixin Gang; Dong Qin (Molecular Genetics and Genomics, 2025)

Enhanced remediation of paddy soils contaminated with butachlor through the application of nitrogen-fixing cyanobacteria as a nitrogen fertilizer substitute - Huiyao Liu; Yu Zhu; Xiao Liang; Kan Wang; Hongjie Qin; Genbao Li; Chengrong Peng; Dunhai Li (Journal of Applied Phycology, 2025)

Alveolar macrophages polarization switch via α2-adrenoceptor activation ameliorates pulmonary inflammation following kidney ischemia reperfusion - Jieyu Li; Zhigang Qin; Xinhai He; Ling Jiang; Xiangfeng Liu; Zhengwei Xue; Xiao Li; Yueming Xu; Peng Li; Jianteng Gu (Inflammation Research, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

Identification of homeobox gene family in Chenopodium quinoa and expression patterns in response to flooding stress during the filling stage - Guofei Jiang; Li Li; Yutao Bai; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Estimating and compensating for shear-wave splitting in orthotropic media - Hai-feng Chen; Peng-yuan Sun; Xiang-yang Li; Zhong-ping Qian; Jian-lei Zhang; Gui-ling Zhao; Xiao-ying Qin (Applied Geophysics, 2025)

Investigation of the Alterations in the Gut Microbiota and Intestinal Mucosa in Mice Infected with Echinococcus multilocularis - Deping Cao; Wenjun Huang; Mingquan Pang; Jiajing Li; Haitao Huang; Hui Ma; Dayu Li; Yufei Qin; Xiaohong Peng; Haining Fan (Acta Parasitologica, 2025)

The Association of Cadmium Exposure and Anthropometrics in School-Age Children: A Longitudinal Study - Meng Wu; Linhong Li; Tianwenjing Huang; Jieying Gao; Peng Gan; Shudan Liu; Dan Wu; Siyan Ye; Chengpeng Cui; Longjie Li; Ge Yan; Qin Liu (Biological Trace Element Research, 2025)

Research on the Reinforcement Effect of the Elephant-Foot Method in Aeolian Sand Tunnels - Ji-hua Qin; Xi-peng Li; Ya Wang; Xiao-li Cao; Dong Li; Yi-guo Xue; Fan-meng Kong; Hui-min Gong; Bang-xiang Li; Chao Lu; Guang-kun Li (Applied Geophysics, 2025)

Associations between Plasma Metal Concentrations and Mortality Risk in Non-Small-Cell Lung Cancer Patients: A Prospective Cohort Study - Yan Liu; Xiao-Yun Chen; Jing-si Chen; Miao Xu; Hong-Jun Zhang; Quan Tang; Yu‑Song Zhang; Da‑Peng Li; Li-Qiang Qin; Kun Wang (Biological Trace Element Research, 2025)

Interpretation Analysis of Influential Variables Dominating Impulse Waves Generated by Landslides - Xiaohan Xu; Peng Qin; Zhenyu Li; Jiangfei Wang; Yuyue Zhou; Sen Zheng; Zhenzhu Meng (Journal of Marine Science and Engineering, 2025)
Landslide impacts into water generate impulse waves that, in confined basins and along steep coasts, escalate swiftly into hazardous near-shore surges. In this study, we present a scenario-aware workflow using gradient boosting and k-means clustering, and explain them using Shapley additive explanations (SHAPs). Two cases are addressed: forecasting at water entry (Scenario I) with predictors Froude number Fr, relative effective mass M, and relative thickness S; and pre-event assessment (Scenario II) with predictors Bingham number Bi, relative moving length L, and relative initial mass Mi. Using 270 controlled physical-model experiments, we benchmark six learning algorithms under 5-fold cross-validation. Gradient boosting delivers the best overall accuracy and cross-scenario robustness, with XGBoost close behind. Scenario I attains a coefficient of determination R2 of 0.941, while Scenario II achieves R2=0.865. Residual analyses indicate narrower spreads and lighter tails for the top models. SHAP reveals physics-consistent controls: M and Fr dominate Scenario I, whereas initial mass and the Bi dominate Scenario II; interactions Fr×S and Mi×Bi clarify non-linear amplification of wave amplitude and height. The cluster–predict–explain framework couples predictive skill with physical transparency and is directly applicable to coastal hazard screening and integration into shoreline early-warning workflows.

Peroxymonosulfate activation by iron-sulfur tailings doped with SiO2 for efficient degradation of tetracycline - Chen-Chen Yin; Chun Cheng; Peng-Yu Zhang; Zheng-Yuan Zhang; Ying Qin; Li-Pin Xue; Yu-Qi Feng; Bai Sun; Shu-guang Zhu (Environmental Science and Pollution Research, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Beyond biodiversity: The more essential role of multi-trophic network complexity for predicting ecosystem multifunctionality under multiple stressors - Shangsheng Sun; Haojie Su; Qingyang Rao; Jianfeng Chen; Yafang Qin; Yongchao Peng; Chaoyue Cheng; Misha Zhong; Ruijing Ma; Yuwei Wang; Yihan Wang; Zengliang Jian; et al. (Water Research, 2025)

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

ZmPOD5 positively regulates drought tolerance by modulating ROS production - Rui Li; Jian Li; Minghao Sun; Yang Qin; Yunling Peng; Yiru Wang; Jun Zheng (Plant Science, 2025)

Risk assessment and underlying mechanisms of pydiflumetofen resistance in Alternaria tenuissima and Alternaria alternata - Lifen Luo; Guangda Shao; Xinyue Li; Tan Dai; Jianqiang Miao; Xingxing Lu; Qin Peng; Xili Liu (Pesticide Biochemistry and Physiology, 2025)

Numerical simulation of vortex-induced vibration response of flexible riser with internal flow under shear flow - Zhan-Long Chen; Nian-Nian Liu; Yu-Xiang Peng; Peng-Nan Sun; Qing-Yang Li; Zhen-Qin Yuan (Ocean Engineering, 2025)

Microplastic aging and plastisphere succession in mangrove sediments: Mechanisms, microbial interactions, and degradation potential - Yuanyuan Su; Jun Lei; Xiaoping Diao; Licheng Peng; Lianzheng Yin; Yongqiang Qin; Wen Zhang; Ping Li (Journal of Hazardous Materials, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

Response of macroinvertebrate drift to dam-induced flow fluctuations: A field experiment in the Yarlung Zangbo river - Jiaxuan Tang; Qinghui Zeng; Fengbo Zhang; Baolong Zhao; Kang Zhao; Qin Yang; Long Yan; Wenhang Su; Pingfeng Li; Jinliang Zhang; Peng Hu (Journal of Environmental Management, 2025)

Study on the effects of high temperature on autophagy and apoptosis in different organs of Bombyx mori based on calcium ion homeostasis - Peilin Peng; Hongbin Zou; Jialu Cheng; Haoyi Gu; Guimin Nong; Xuelin Qin; Bing Li (Insect Biochemistry and Molecular Biology, 2025)

Mineral chelating peptides derived from walnut protein: preparation, absorption pathways, and bioavailability - Rongrong Jin; Hao Yu; Bingna Li; Chen Peng; Jinwei Liu; Jie Yang; Ying Liu; Tian Li; Haitao Yue; Qin Guo; Qiang Wang; Yang Qu (Food Research International, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

Orthogonal functional group tagging combined with computational retention time prediction for discovering furan fatty acids in plant oils - Hua-Ming Xiao; Xiao-Hui Peng; Shuai Zhao; Dilshad Hussain; Qin-Feng Zhang; Jian-Li Chen; Dan Luo; Fang Wei; Xian Wang (Food Chemistry, 2025)

Investigation of the matrix effects on structural stability and application performance of aptamers: Insights from tetrodotoxin detection in typical seafood - Yu Li; Shuo Qi; Peifang Chen; Mingwei Qin; Ning Ding; Chifang Peng; Zhouping Wang (Food Chemistry, 2025)

Preparation of high-specificity monoclonal antibody based on rational hapten design and development of immunoassay for accurate detection of dexamethasone in milk and animal tissues - Hongfei Yang; Liangni Qin; Jiaxu Xiao; Xiaoming Pan; Shiyun Han; Linwei Zhang; Jixiang Liang; Yu Si; Hao Wen; Long Li; Xingyu Wang; Xiaojuan Zhang; et al. (Food Bioscience, 2025)

Spatial disparities in perfluoroalkyl and polyfluoroalkyl substances exposure and immunosuppressive effects on vaccine induced antibody levels in Guangzhou children - Zhimei Mou; Pingting Zhu; Fenfang Deng; Yang Xu; Pengzhe Qin; Rongfei Peng; Juntao Li; Lei Tan (Environmental Pollution, 2025)

Climate warming plays an important role in dissolved organic carbon loss in deep soil layers across China - Lingli Yu; Mingxu Li; Xiaoyan Kang; Li Xu; Boming Liang; Jiankun Chen; Youbin Deng; Xuanbo Wang; Xuyang Zhang; Mengze Qin; Changhui Peng; Nianpeng He (CATENA, 2025)

Xanthouhumol relieves stress-induced depressive-like behaviors through the Sirt1/NF-κB/NLRP3 pathway - Gangqiang Lin; Yi Zhang; Jing Qin; Yong He; Li Fan; Qing Tan; Peng Xie (Psychopharmacology, 2025)

Genome-Wide Identification of the Aux/IAA Gene Family in Quinoa and Analysis of its Expression Pattern Under Low-Temperature Stress - Huanyao Xia; Jie Yang; Yuming Xie; Jianlong Zhou; Lurongrong Gao; Lingyuan Zhang; Yutao Bai; Xuqin Wang; Guofei Jiang; Hanxue Li; Hui Zhang; Peng Qin (Journal of Plant Growth Regulation, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Effect of Ionic Strength and Electrolyte Type on Phosphorus Deposition and Release from the Sediments - Yuepeng Yin; Jie Qin; Anqi Guo; Yao Xiao; Lijihong Ye; Peng Wang; Qingman Li; Wen Zhang (Current Pollution Reports, 2025)

A Novel Felbinac Transdermal Patch with High Permeability: Design, Development and Evaluation - Li Qin; Cheng Liu; Ran Bai; Zhining Zhao; Yinghua Sun; Peng Zhang (AAPS PharmSciTech, 2025)

Retraction notice to “Effect of calcium and phosphorus on ammonium and nitrate nitrogen adsorption onto iron (hydr)oxides surfaces: CD-MUSIC model and DFT computation” [Chemosphere 357, June 2024, 142070] - Mengke Jia; Jie Ma; Qiongqiong Zhou; Lijie Liu; Xiaolei Jie; Hongen Liu; Shiyu Qin; Chang Li; Fuqing Sui; Haichao Fu; Haijiao Xie; Long Wang; et al. (Chemosphere, 2025)

Gynogenetic offspring from distant hybridization of red crucian carp × blunt snout bream: Insights into barbel origin - Zhengkun Liu; Xinyi Deng; Wanjing Peng; Siyang Li; Ling Xiong; Enkui Hu; Yan Tang; Zeyang Li; Qian Xiao; Yuhan Yang; Xu Huang; Chongqing Wang; et al. (Aquaculture, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Seismic vulnerability analysis of adobe structures considering historical Chinese seismic intensity standards - Si-Qi Li; Can Zhang; Peng-Fei Qin (Soil Dynamics and Earthquake Engineering, 2025)

Controls of organic matter content on shale oil occurrence and distribution: Insights from retained oil composition and pore structure in marine shales - Shangli Liu; Haifeng Gai; Xinyue Shi; Peng Cheng; Tengfei Li; Qin Zhou; Sui Ji; Hui Tian (Organic Geochemistry, 2025)

Interpretable machine learning models for predicting hormesis of binary antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Pei-Pei Zhang; Yan-Peng Liang; Hong-Hu Zeng; Yong-Hong Zhang; Li-Tang Qin (Journal of Hazardous Materials, 2025)

Selenium solubilization by Bacillus sp. S01: Mechanistic insights and environmental implications in paddy soils - Shirui Peng; Yan Qin; Bei Li; Guofei Pan; Weiwei Zhao; Yaxuan Feng; Jiawei Shen; Yuheng Qiu; Shanhe Liang; Hengyu Chen; Yanyan Wei (Journal of Hazardous Materials, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

Comprehensive analysis of T-2 toxin contamination in maize from Northeast China using automated immunomagnetic beads system coupled with LC-MS/MS - Jinnan Chen; Di Cai; Peng Li; Jin Ye; Meng Wang; Yu Wu; Li Li; Hongmei Liu; Qinghui Zhang; Yao Qin; Quan Pan; Songxue Wang (Food Chemistry, 2025)

Engineered albumin host for ratiometric fluorescent indicator-displacement assay: Distinguishing testosterone from estrone and estradiol - Yuting Luo; Linhui Peng; Zhang Lin; Zhiqing Xun; Na Li; Naiyu Liu; Yalong Wang; Xinfeng Du; Tianyi Qin; Bin Liu; Mingqiang Zhu (Chemical Engineering Journal, 2025)

Crystalline porous organic frameworks for aqueous zinc-iodine batteries: Progress, challenges, and opportunities - Tao Sun; Haian Peng; Qin Chen; Jiaxu Yang; Peng Zhang; Yanjiao Zhang; Shun Li; Jun Qian; Li Li; Siew Yee Wong; Xu Li; Jianming Zhang (Chemical Engineering Journal, 2025)

Divergent effects of cropland management practices and global change factors on microbial necromass across ecosystems: implications for soil organic carbon - Chen-Hao Lyu; Wen-Jun He; Peng Chen; Xin-Xin Jing; Guo-Shi Zhang; Run-Qin Zhang; Zi-Yan Li; Zhi-Guo Li; Yi Liu (CATENA, 2025)

Multi-constraint analysis reveals distinct aerosol effects on high cloud properties at SACOL and SGP sites - Yang Xia; Jinming Ge; Qingyu Mu; Yue Hu; Nan Peng; Ziyang Qin; Xiang Li; Chi Zhang; Bochun Liu (Atmospheric Research, 2025)

Transcriptomic evidence from peripheral blood reveals nonlinear gene expression trajectories of aging in female rhesus macaques - Chong-Jun Weng; Long-Bao Lv; Li-Qin Yang; Long Zhao; Zheng-Fei Hu; Si-Yu Ma; Yi-Jiang Li; Wen-Xian Xiao; Yun Wang; Xin-Tian Hu; Gong-Hua Li; Qing-Peng Kong (Science China Life Sciences, 2025)

Transcriptome Reveals Molecular Characteristics and Immune Response in Triploid Cyprinid Fish Infected with a Novel Pathogenic Aeromonas sp. AS1-4 - Qin-Yang He; Jie Peng; Ruo-Xing Yu; Ting Luo; Yao-Hui Li; Zi-Rou Zhong; Zi-Le Qin; Fei Wang; Jian Li; Sheng-Wei Luo (Marine Biotechnology, 2025)

Nitrogen-fixing cyanobacteria substitute for nitrogen fertilizer: A dual win for greenhouse gas mitigation and rice productivity - Yu Zhu; Huiyao Liu; Kan Wang; Hongjie Qin; Panpan Zhou; Jiaoli Zheng; Jingwu Yao; Dunhai Li; Chengrong Peng; Genbao Li (Journal of Applied Phycology, 2025)

Genome-wide identification and expression analysis of C2H2 zinc finger protein transcription factor in quinoa - Xuqin Wang; Xingmei Zong; Guofei Jiang; Lingyuan Zhang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

Overlooked role of aged cationic natural organic matter in aquatic microplastics aggregation-sedimentation - Qian Peng; Zhiyan Feng; Miao Li; Chencheng Qin; Xiaoai Guo; Jiaxin Wu; Aoqiang Shu; Lin Liu; Xiaodong Wu; J. Paul Chen; Xingzhong Yuan; Hou Wang (Water Research, 2025)

In situ generation of Cu(III) synergized with crystalline amorphous strong interfacial interaction for autocatalytic degradation of LEV - Chun Zhang; Qin Chen; Yuxuan Li; Zhiyong Cai; Zhiguo Wang; Wei Huang; Peng Yu (Water Research, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Dynamic response reconstruction technique investigation of catenary submarine cables based on inverse finite element method - Li Guo; Shuo Peng; Yuchao Yuan; Wenyong Tang; Hao Qin (Ocean Engineering, 2025)

OsATG1 and OsATG8 exhibit autophagy-independent functions to oppositely regulate ROP GTPase-mediated plant immunity in rice - Feng He; Hui Tao; Ruyi Wang; Jinling Liu; Zeyun Hao; Debao Wang; Xuetao Shi; Fan Zhang; Jiawei Long; Hao Zhang; Xiao Yang; Mengchao Qin; et al. (Molecular Plant, 2025)

Electric field distribution and selective liberation in magnetite quartzite under high voltage pulse discharge - Yonghong Qin; Ziyu Yang; Yuexin Han; Peng Gao; Yanjun Li; Ningyu Zhang (Minerals Engineering, 2025)

Enhancing anammox resistance to salinity stress through waste iron scraps addition: Performance and microbial community dynamics - Haozhe Xu; Manyu Qin; Zengyi Li; Xingyu Zhang; Xiaoming Ji; Peng Wu; Feiyue Qian; Chongjun Chen; Wenru Liu (Journal of Environmental Management, 2025)

Tracking climate fluctuations in the North China during the Carboniferous-Permian transition using chemical weathering indices - Wanli Gao; Qin Zhang; Jingtao Zhao; Qiang Fang; Wen Liu; Weiliang Kong; Wenyu Li; Hongjie Peng; Tianquan Qu; Guangyin Cai; Jianghai Yang; Zhen Qiu (Global and Planetary Change, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Selenium-enriched lactic acid bacteria inoculation enhances the quality of Paocai by imparting the microbiome and metabolome - Mingye Peng; Qin Li; Binbin Long; Bo Li; Zhicong Shen; Ning Xu; Yong Hu; Chao Wang; Yang Chen; Mengzhou Zhou (Food Chemistry, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Targeted capture of Bacillus thuringiensis using phage endolysin cell wall binding domain with high recognition specificity - Qin Peng; Lushuang Wang; Gege Feng; Xi Chen; Dan Li; Yating Zeng; Yingqi Qian; Zhirou Sun; Yihui Yuan (Chemical Engineering Journal, 2025)

Maximizing singlet oxygen generation: Cobalt single-atom advanced oxidation system for efficient and selective degradation of phenolic pollutants in actual waters - Wanju Peng; Dongyang Li; Deyu Qin; Hanzhuo Luo; Fanzhi Qin; Hao Weng; Lei Chen; Chen Zhang (Chemical Engineering Journal, 2025)

Nobiletin alleviates hypoxia-induced pulmonary hypertension by inhibiting calcium-sensing receptor - Qin Yin; Wanhong Peng; Jie Yang; Cunyu Fan; Qinru Wang; Hongyu Gan; Shiwei Zhang; Xiaohang Fan; Fajiu Li (Journal of Natural Medicines, 2025)

High-resolution population density mapping in urban areas using a contextualized geographically weighted neural network (CGWNN) model - Ge Qiu; Yuchen Li; Kun Qin; Chen Li; Shuhan Yang; Chun Yin; Yaolin Liu; Shaoqing Dai; Peng Jia (Applied Geography, 2025)

Monitoring the nicotine delivery stability in electronic cigarettes based on in-situ AS/SRD/FOS technology - Shuai Yuan; Shihao Sun; Ruilin Qin; Peng Li (Analytica Chimica Acta, 2025)

Mesh-Free Method for Static Analyses of Carbon Nanotube-Reinforced Composite Plates - Peng-chu Ding; Qin-qiang Guo; Li-wu Chang; Jun-feng Xu; Zhen Li; Shi-heng Yan; Dong Han (Applied Geophysics, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Characterizing dynamics of built-up height in China from 2005 to 2020 based on GEDI, Landsat, and PALSAR data - Peimin Chen; Huabing Huang; Peng Qin; Xiangjiang Liu; Zhenbang Wu; Feng Zhao; Chong Liu; Jie Wang; Zhan Li; Xiao Cheng; Peng Gong (Remote Sensing of Environment, 2025)

Prediction and verification of arsenic phytoavailability in paddy soil based on CD-MUSIC model in the Xiangjiang River Basin - Qian Tian; Jian He; Shuangling He; Qin Zhang; Hongbin Li; Limei Peng; Daoyou Huang; Hanhua Zhu; Xinliang Liu; Qihong Zhu (Journal of Hazardous Materials, 2025)

In-situ synthesized Fe-SSZ-13 zeolite with superior performance for NO oxidation over a wide temperature range - Sai Zhang; Peng-Song Li; Jia-Xin Zhang; Yuan-Hang Qin; Zhen Chen; Li Yang; Tielin Wang; Cun-Wen Wang (Fuel, 2025)

Cobalt-modification on UiO-bpydc MOF facilitates ligand-to-metal charge transfer for superior visible-light photocatalytic degradation of refractory fluoroquinolone antibiotics - Kaichun Lin; Jingjun Qin; Zhang Liu; Weicheng Xu; Meng Li; Yuanzhi Zheng; Wei Han; Guangying Zhou; Jianzhang Fang; Zhanqiang Fang; Feng Peng; King Lun Yeung (Environmental Research, 2025)

Differential responses of pinaceae and cupressaceae tree radial growth to drought in Central Asia - Peng Zhang; Liang Jiao; Ruhong Xue; Xuge Wang; Qian Li; Zhengdong Guo; Le Zhang; Yarong Qin (Dendrochronologia, 2025)

Complete chloroplast genome sequence and phylogenetic analysis of Lactuca sativa var. ramosa hort - Yihui Gong; Yalin Qin; Tao Luo; Peng Li; Guihua Zhou (Genetic Resources and Crop Evolution, 2025)

Experimental Study on Mechanical Integrity of Cement and EICP-Solidified Soil for Scour Protection of Pile Foundations - Feng Cao; Qilin Zhang; Wei Qin; Haoran Ouyang; Zhiyue Li; Yutao Peng; Guoliang Dai (Journal of Marine Science and Engineering, 2025)
Among the scour protection measures for pile foundations, the use of solidified mud has demonstrated effective protection against scour. However, research on the mechanical integrity of this protective measure is relatively scarce. Therefore, a series of experiments were performed on cement-solidified soil and Enzyme-Induced Carbonate Precipitation (ECIP) solidified soil to analyze fluidity, disintegration, and unconfined compressive strength, along with an analysis of influencing parameters. Test results show the following: for cement-solidified soil, fluidity decreases with higher cement content, while its disintegration rate decreases with more cement and its unconfined compressive strength increases with a longer curing time and higher cement content. For ECIP-solidified soil, fluidity decreases with higher soy powder concentration but increases with higher binder solution concentration. ECIP’s initial disintegration rate increases with binder concentration, but after 7 days curing, its disintegration rate decreases with both higher binder concentration and higher soy powder concentration. ECIP’s strength increases with higher soy powder concentration. Crucially, both types of solidified soil exhibit decreased unconfined compressive strength with higher initial water content. The research results can provide a reference for the construction of solidified soil in the field of scour protection.

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

A preliminary investigation of pore development mechanisms in highly matured solid bitumen: Implications from the Ediacaran Dengying Formation solid bitumen in the central Sichuan Basin, Southwest China - Lianqiang Zhu; Hui Tian; Peng Cheng; Haifeng Gai; Tengfei Li; Qin Zhou; Wei Wu; Chao Luo; Ping'an Peng (Marine and Petroleum Geology, 2025)

Driving factors of soil selenium accumulation in regional enrichment area at selenium-deficient soil belt of China: An enlightenment of Moran's index and machine learning - Yuanli Qin; Li Zhang; Qiaolin Wang; Yuntao Song; Min Peng; Hangxin Cheng (Journal of Geochemical Exploration, 2025)

Effect of air frying on in vitro digestion and transport properties of scallop (Patinopecten yessoensis) adductor muscles: Insights from peptidomics analyses - Zi-Ye Wang; Qian Wang; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2025)

Self-enhanced multifunctional composite membranes based on metal-organic frameworks embedded with thymol nanoparticles for post-harvest preservation of fruits - Qi Chen; Dianpeng Han; Xiaoyu Qu; Wen Zhang; Yuan Peng; Shuang Li; Kang Qin; Shuyue Ren; Yu Wang; Huanying Zhou; Pei Zhao; Zijian Wu; et al. (Food Hydrocolloids, 2025)

Self-assembled multifunctional antimicrobial composite films of humidity-responsive pterostilbene@β-cyclodextrin inclusion complexes/carboxymethyl cellulose/zein for fruit preservation - Xiaoyu Qu; Dianpeng Han; Qi Chen; Guangna Ji; Yuan Peng; Shuang Li; Kang Qin; Shuyue Ren; Yu Wang; Huanying Zhou; Wenqiang Guan; Xinxuan Wang; et al. (Food Packaging and Shelf Life, 2025)

Association of urinary pesticide metabolites and iodine with thyroid volume in school-aged children - Fuhai Zhong; Conghui Xu; Fenfang Deng; Juntao Li; Yuehong Wei; Pengzhe Qin; Rongfei Peng; Lei Tan (Environmental Pollution, 2025)

Exploring policy support for efficiency improvement of wind power from an environmental perspective: Evidence from wind farms in Qinghai, China - Li-Qiu Liu; Yu-Yan Qin; Xian-Peng Chen; Xiang-Cheng Zhang; Zhen-Yu She; Bai-Chen Xie (Environmental Impact Assessment Review, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Drought increased the response sensitivity of tree-ring δ18O for Qinghai spruce to climate change at different elevations in the eastern Tibetan Plateau - Yarong Qin; Liang Jiao; Qian Li; Zhengdong Guo; Peng Zhang; Ruhong Xue; Xuge Wang; Kuan Zhang (Quaternary International, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Isolation, identification, and virulence of three strains of Beauveria bassiana from silkworms, Bombyx mori - Qiang Zhang; Wenqing Lai; Qin Li; Xiaoying Zhang; Zhan-peng Lu; Jiawei Jiang; Wenjing Yu; Zuo-min Shao; Xue-yang Wang; Mu-wang Li (Journal of Asia-Pacific Entomology, 2025)

Solid bitumen formation and resulting differential porosity development in the Mesoproterozoic Xiamaling shale during artificial thermal maturation - Ji Chen; Jingwen Zheng; Daxiang He; Peng Cheng; Qin Zhou; Tengfei Li; Haifeng Gai (International Journal of Coal Geology, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

Rapid absolute quantification of glucose and fructose isomers in honey using a boronic acid-based reactive matrix by MALDI-TOF/TOF tandem mass spectrometry - Zhang-Na Qin; Jia-Min Chen; Jia-Wei Li; Zhen-Peng Zhen; Qi-Zhao Chen; Zhi-Qiang Zhang; Gui-Hua Wang; Yu-Feng Gao (Food Chemistry, 2025)

Impact of fermentation duration in fermented glutinous rice wine dough procedure on the staling of Chinese steamed bread - Jia-Xuan Shang; Jia-Xuan Li; Feng-Ping Qin; Yi-Peng Bai; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Design and discovery of POLQ helicase domain inhibitors by virtual screening and machine learning - Wei Feng; Lei Liu; Lingjun Li; Peng Du; Zhichen Yuan; Jing Yuan; Changjiang Huang; Zijian Qin (Medicinal Chemistry Research, 2025)

Ulva clathrata Enzymatic Hydrolysate Protects Wheat from Salt–Alkaline Stress by Regulating ABA Biosynthesis - Chunying Du; Feiyu Li; Fang He; Yongzhou Chi; Bo Zhu; Xiuchao Song; Siqi Zuo; Xinyu Wang; Yimin Qin; Peng Wang (Journal of Plant Growth Regulation, 2025)

Knockout of the Staphylococcus aureus virulence gene sdrC promotes Myh7 expression to inhibit the progression of osteomyelitis - Baochuang Qi; Lili Yang; Xinyu Fan; Dongdong Qin; Jiming Gan; Tao Chen; Yu Rao; Zhongyu Peng; Longjun Su; Chuan Li; Yongqing Xu (Journal of Molecular Histology, 2025)

Integrated volatile metabolomics and transcriptomics provide insights into the formation of characteristic flavor in gynogenetic grass carp and its offspring - Jinhai Bai; Yan Tang; Xinyi Deng; Zhengkun Liu; Siyang Li; Enkui Hu; Ling Xiong; Wanjing Peng; Xu Huang; Chongqing Wang; Xidan Xu; Xiaowei Xu; et al. (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Corrigendum to “Machine learning-based optimization of impact-resistant layups for FRP hybrid laminates in yachts” [Ocean Eng. 324 (30) (2025) 120600] - Miaomiao Zhang; Qinglin Chen; Jiayong Zhuo; Yingqiang Cai; Zhaoyi Zhu; Xiaowen Li; Miaojiao Peng; Kuan Fan; Yezhi Qin (Ocean Engineering, 2025)

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Evaluate the sensitivity of rapeseed lodging under low light：A field study on the biomechanics of stem and root lodging in rapeseed (Brassica napus L.) - Yue Hu; Hafiz Hassan Javed; Li Liu; Nadiyah M. Alabdallah; Kamran Ghaffor; Ya-long Liu; Yu-qin Luo; Faiza Gulzar; Xiao Peng; Yong-cheng Wu (Field Crops Research, 2025)

How the dispersion and coalescence behaviors of CO2 bubbles affecting carbonation reaction in bubble column reactor: experimental and numerical simulation study - Lin Chen; Jintao Ma; Cheng Chen; Xin Wang; Yonghong Qin; Enze Li; Yanxia Guo; Ran Peng; Zihe Pan (Chemical Engineering Journal, 2025)

Optimizing Nickel-Based catalysts for UOR: The role of W interface in nickel-selective oxidation reaction (NSOR) enhancement - Yu Duan; Fozia Sultana; Xiaofan Zhang; Xiaoqing Yan; Xiangbowen Du; Meijie Shi; Peng Zhang; Xiaojun Qin; Kaicheng Qian; Tongtong Li; Mingwu Tan; Renhong Li (Chemical Engineering Journal, 2025)

Frequency influence on freestanding-mode triboelectric nanogenerators - Zhongjie Li; Bingyan Cui; Hengyu Guo; Ying Gong; Chao Yang; Qin Zhang; Xiaofan Li; Yan Peng; Junlei Wang (Chemical Engineering Journal, 2025)

The Physical Simulation Study on Impact Damage Characteristics of Deep Elliptical Roadway - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Yan Yang; Chaolong Qin; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Effects of Subchronic Manganese and Iron Exposure, Alone or in Combination, on Elemental Distribution in Rats - Yan Li; Jian-chao Peng; Yuan-yuan Fang; Li-mei Qin; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2025)

Three new metabolites from the endophyte Fusarium proliferatum T2-10 - Jian-Bing Tan; Wei-Wei Peng; Mei-Fang Li; Feng-Hua Kang; Yu-Ting Zheng; Li Xu; Si-Yu Qin; Yuan-Tao Huang; Zhen-Xing Zou (Natural Product Research, 2025)

Transcriptomics and physiological indicators analyzed the delayed effect of carboxymethyl chitosan on lignification of okra during postharvest cold storage - Lijuan Wei; Shunjiao Gao; Fan Li; Xinyue Zhang; Yue Peng; Yaowen Liu; Yiqin Zhang; Wen Qin (Postharvest Biology and Technology, 2025)

Machine learning-based optimization of impact-resistant layups for FRP hybrid laminates in yachts - Miaomiao Zhang; Qinglin Chen; Jiayong Zhuo; Yingqiang Cai; Zhaoyi Zhu; Xiaowen Li; Miaojiao Peng; Kuan Fan; Yezhi Qin (Ocean Engineering, 2025)

Origin and accumulation of natural gas in the Sinian-Cambrian reservoirs of the central Sichuan Basin, southwest China: Implications from both closed and semi-open pyrolysis experiments - Xing Wang; Haifeng Gai; Peng Cheng; Qin Zhou; Tengfei Li; Sui Ji; Hui Tian (Marine and Petroleum Geology, 2025)

Hormesis effect of cadmium on pakchoi growth: Unraveling the ROS-mediated IAA-sugar metabolism from multi-omics perspective - Runze Li; Mengzhan Qin; Jiyuan Yan; Tao Jia; Xiaodong Sun; Jiawen Pan; Wenwen Li; Zhiguo Liu; Mohamed A. El-Sheikh; Parvaiz Ahmad; Peng Liu (Journal of Hazardous Materials, 2025)

Accelerated removal and mechanism of tetracycline from water using immobilized bacteria combined with microalgae - Jinli Wang; Xiangnan Chen; Haibo Sun; Xueying Li; Qiang Lu; Pufeng Qin; Yang Yang; Dengni Lai; Lin Luo; Xin Peng; Yuan Yang; Zhibin Wu (Journal of Environmental Chemical Engineering, 2025)

Mitigation effect and mechanism of different pretreatment methods on reverse osmosis membrane fouling in coal chemical wastewater treatment - Peng Tang; Jialin Shi; Can He; Xifan Li; Guijing Chen; Yi Deng; Jiawang Qin; Baicang Liu (Desalination, 2025)

Comparison of the performances and mechanisms of anammox bacteria in-situ self-enrichment under heterotrophic and autotrophic conditions by inoculating ordinary activated sludge - Zhaoxu Peng; Jing Qin; Ying Zhao; Ying Li; Feiyue Hu; Zhixuan Bai; Haosen Yang; Baodan Jin; Jiantao Ji (Bioresource Technology, 2025)

Landscapes of gut microbiome and blood metabolomic signatures in relapsing remitting multiple sclerosis - Jinzhou Feng; Shi Tang; Xiaolin Yang; Mengjie Zhang; Zhizhong Li; Shaoru Zhang; Yongliang Han; Yongmei Li; Philippe P. Monnier; Gang Yu; Peng Zheng; Cunjin Zhang; et al. (Science China Life Sciences, 2025)

Identification of quinoa B3 gene family and its expression pattern in response to low temperature stress - Lingyuan Zhang; Yanbo Xia; Guofei Jiang; Xuqin Wang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Increase of ATP synthesis and amino acids absorption contributes to cold adaptation in Antarctic bacterium Poseidonibacter antarcticus SM1702T - Wen-Yue Xu; Sha-Sha Liu; Xiao-Han Guo; Peng Wang; Chun-Yang Li; Li Liao; Qi-Long Qin (Extremophiles, 2025)

Corrigendum to “Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain” [Aquaculture, Volume 586, Part 2, 15 February 2025, 741875] - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Navigating the gut-liver axis: The potential of tea to alleviate inflammatory bowel disease and associated metabolic syndromes - Qi Fang; Chunyin Qin; Ying Peng; Liang Zhang; Daxiang Li; Shanshan Hu (Trends in Food Science & Technology, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Angular normalization of GOES-16 and GOES-17 land surface temperature over overlapping region using an extended time-evolving kernel-driven model - Boxiong Qin; Shuisen Chen; Biao Cao; Yunyue Yu; Peng Yu; Qiang Na; Enqing Hou; Dan Li; Kai Jia; Yingpin Yang; Tian Hu; Zunjian Bian; et al. (Remote Sensing of Environment, 2025)

Unveiling the resistance risk and resistance mechanism of florylpicoxamid in Corynespora cassiicola from cucumber - Qin Peng; Xinchang Hao; Chunyue Liu; Xiuhuan Li; Xingxing Lu; Xili Liu (Pesticide Biochemistry and Physiology, 2025)

Incartrilactones A and B: Two schinortriterpenoids with a 14,15-seco-15,17-cyclolancifoartane skeleton from Schisandra incarnata - Ying Gao; Juan Chen; Junjun Liu; Zijian Huang; Xiaogang Peng; Wanpeng Li; Chunlun Qin; Hanli Ruan (Phytochemistry, 2025)

Unlocking flaxseed oleosomes (oil bodies) potential: Optimal extraction and functional insights through enzymolysis or dehulling treatment - Rao Fu; Chenqiang Qin; Yu Peng; Yuanying Ni; Jingming Li; Remko Marcel Boom; Constantinos V. Nikiforidis; Mo Li; Xin Wen (Food Research International, 2025)

Integrated metabolomic and transcriptomic analysis reveals the regulatory effects of IAA on polyphenol biosynthesis and antioxidant activity in Phlebopus portentosus - Taobo Xiang; Feng Ge; Lei Zhu; Gaige Shao; Tao Wu; Hao Fan; Yueqian Liu; Longyu Wang; Jing Wang; Peng Li; Qin He; Ailiang Jiang; et al. (Food Bioscience, 2025)

Protection of glutamine: The NF-κB/MLCK/MLC2 signaling pathway mediated by tight junction affects oxidative stress, inflammation and apoptosis in snakehead (Channa argus) - Xue-qin Wu; Ji-wu Wan; Zhi-nan Yang; Hong-jian Liu; Yue Chang; Si-bo Peng; Xiao-tian Niu; Yi-di Kong; Min Li; Xiu-mei Chen; Gui-qin Wang (Fish & Shellfish Immunology, 2025)

Size effect in shear failure of RC beams reinforced with CFRP sheets: Influences of CFRP adhesion angle and shear-span ratio - Liu Jin; Peng Qin; Jiangxing Zhang; Dong Li; Xuan-ang Jiang; Xiuli Du (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Antimony-induced hippocampal neuronal impairment through ferroptosis activation from NCOA4-mediated ferritinophagy - Shali Yu; Ziyu Qin; Yuqing Chen; Fengxu Wang; Zhijie Li; Ruiyao Huang; Zhengnan Gao; Yi Qu; Peng Xue; Yonghua Luo; Xiaoke Wang; Xinyuan Zhao (Chemico-Biological Interactions, 2025)

Multi-omics analysis of the accumulation mechanism of flavonoids in rice caryopsis under blue light - Ping Zhang; Yongsheng Tang; Juxiang Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Yutao Bai; Peng Qin (Plant Cell Reports, 2025)

Sex-biased juvenile hormone and gene expression underlie sex difference of stress resistance in the American cockroach - Fangfang Liu; Shudian Zhang; Ping Chen; Wei Tang; Xiaoyi Chen; Yingting Wu; Sishi Xia; Diqi Peng; Zhengyi Shao; Qin Li; Yuqing Liu; Xiaoshuai Zhang; et al. (Journal of Pest Science, 2025)

Prediction of Seawater Intrusion Run-Up Distance Based on K-Means Clustering and ANN Model - Jiatao Li; Zhenzhu Meng; Junkang Zhang; Yukai Chen; Jiewen Yao; Xinyue Li; Peng Qin; Xian Liu; Chunmei Cheng (Journal of Marine Science and Engineering, 2025)
Coastal regions are increasingly vulnerable to sea-level rise and extreme storm events, making the accurate prediction of wave run-up on seawalls crucial for effective flood and erosion protection. This study presents a novel hybrid approach combining K-means clustering with artificial neural networks (ANNs) to predict wave run-up distance. The method begins with dimensionless analysis to scale all the variables, followed by data segmentation using K-means clustering to group wave characteristics such as the Froude number, scaled distance from the wave front to the shoreline, and wave nonlinearity. These clusters help to focus the ANN on more homogeneous wave conditions, significantly improving prediction accuracy. Two-dimensional flume experiments systematically varied wave height, period, and steepness, producing a robust dataset that accounts for a range of wave conditions. The model’s performance is demonstrated through a high R2 value of 0.97 and low mean squared error (MSE) of 0.0092, surpassing traditional ANN models in its ability to capture complex wave dynamics.

Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Integrated physiological, transcriptomic, and metabolomic investigation reveals that MgO NPs mediate the alleviation of cadmium stress in tobacco seedlings through ABA-regulated lignin synthesis - Mengzhan Qin; Jiyuan Yan; Runze Li; Tao Jia; Xiaodong Sun; Zhiguo Liu; Mohamed A. El-Sheikh; Parvaiz Ahmad; Peng Liu (Journal of Hazardous Materials, 2025)

Facile electrophoretically deposited of iron/carbon nanotube-based electro-Fenton cathode for high-performance organics degradation - Yuanlu Xu; Qi Peng; Yueling Yu; Zhifei Li; Yanming Liu; Zijian Qin; Xinfei Fan (Journal of Environmental Chemical Engineering, 2025)

Heavy metals migration and in-situ solidification in the co-combustion of solid waste fuels: Rules and differences - Shuning Qin; Li Jia; Xiaolei Qiao; Chenxing Wang; Baihe Guo; Xinyue Chang; Peng Cheng; Yan Jin (Journal of Environmental Chemical Engineering, 2025)

An ammonia-responsive aerogel-type colorimetric sensor for non-destructive monitoring of shrimp freshness - Jichao Qin; Yujie Li; Yue Li; Zhuoqun Qiao; Li Yan; Kai Chen; Kao Wu; Hong Qian; Bo Peng; Fatang Jiang (Food Research International, 2025)

Multi stimulus responsive composite nanoparticles as efficient and recyclable emulsifiers for oil recovery processes - Jing Li; Keran Li; Qin Zhang; Lifei Peng; Xiaoping Zhu (Chemical Engineering Journal, 2025)

Landscape indices explain different responses of runoff and sediment yield to land use/cover change on the Loess Plateau, China - Yanli Qin; Peng Shi; Yuan Hu; Qiang Li; Yaping Wang; Qiaoqiao Wang; Duoduo Zhou (CATENA, 2025)

Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Loaded Mir-29-3p Targets AhR to Improve Juvenile Idiopathic Arthritis via Inhibiting the Expression of IL-22 in CD4+ T Cell - Xinyi Wei; Kunpeng Sui; Yuanyuan Peng; Sha Li; Yu Fang; Zhi Chen; Xiao Du; Xue Xie; Haiming Tang; QiuYue Wen; JingWei Li; Meilin He; et al. (Stem Cell Reviews and Reports, 2025)

The different parts of Dendrobium officinale Kimura et Migo: traditional uses, phytochemistry, pharmacological activities, and product development status and potential - Yuan Li; Qin-Xiang Chang; Peng-Guo Xia; Zong-Suo Liang (Phytochemistry Reviews, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Spatial distribution and driving factors of soil selenium on the Leizhou Peninsula, southern China - Xiaomeng Cheng; Li Zhang; Chen Zhao; Min Peng; Yuanli Qin; Wei Han; Fugui Zhang; Daoming Zeng; Fan Yang (Environmental Geochemistry and Health, 2025)

Intergranular fracture induced by helium bubbles segregation in NiFe single-phase concentrated solid solution alloys - Jie Li; Xinhua Yang; Peng Wang; Qin Qian (Annals of Nuclear Energy, 2025)

Well-developed root systems and a nitrogen-rich rhizosphere recruit key bacterial taxa to resist disease invasion of field crop - Junhui Li; Yidong Zou; Kun Yang; Yi Zhu; Qiyun Zhou; Lanjun Shao; Jia Gong; Shuguang Peng; Guangjue Peng; Tian Qin; Meijie Tian; Yunhe Tian; et al. (Agriculture, Ecosystems & Environment, 2025)

Wave Motion Response Analysis of Flip-Type Ocean Aquaculture Platforms Based on AQWA - Hongling Qin; Li Peng; Zhiyuan Wang; Siqi Wu; Wei He; Yuanping Yang; Jian Li; Hao Zhang (Journal of Marine Science and Engineering, 2025)
The stability of deep-sea aquaculture equipment under extreme sea conditions such as typhoons directly affects the safety and operational reliability of the aquaculture platform, which in turn affects the economic benefits of fish farming. Therefore, it is particularly important to systematically analyze the hydrodynamic response of aquaculture facilities using numerical methods. This paper employs the hydrodynamic analysis software AQWA, integrating the boundary element method of three-dimensional potential flow theory with the Morison equation, to conduct hydrodynamic research on a flip-type aquaculture platform. The calculations include the platform’s amplitude response operators (RAOs), added mass, as well as motion responses and mooring line tensions under extreme sea conditions. The results indicate that the platform’s sway, surge, and heave motions are highly sensitive to wave frequency in the low-frequency range, with a significant resonance phenomenon occurring at a wave frequency of 0.84 Hz. The main wind and wave responses of the platform manifest as surge and roll motions. To address this issue, it is recommended to add additional anchor chains on the short sides of the platform to effectively reduce the amplitude of surge and roll motions. Furthermore, under extreme sea conditions when the platform faces the windward waves on the short side, its motion response frequency is lower than when facing the windward waves on the long side, but the difference in response amplitude between the two conditions is small.

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Luteolin-borneol complex, a novel pharmaceutical preparation for aquaculture against NNV infection - Jia-Le Zhou; Xiang Liu; Qin-Xue Liu; Tian-Qiang Liu; Tao Liu; Peng-Fei Li; Fei Ling; Gao-Xue Wang (Aquaculture, 2025)

Positively charged mesoporous silica nanocarriers loaded with arbidol: A novel effective nano antiviral system against nervous necrosis virus - Xiang Liu; Zong-Yi Ren; Qin-Xue Liu; Jia-Le Zhou; Bin Yang; Peng-Fei Li; Tian-Qiang Liu; Fei Ling; Gao-Xue Wang (Aquaculture, 2025)

Effects of bicarbonate on antioxidant, immune, osmolytic and metabolic capabilities of Scylla paramamosain - Chenxi Che; Yuntao Li; Kangxiang Qin; Ziwei Fan; Wenjun Li; Shan Gao; Peng Yang; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Stability of China's terrestrial ecosystems carbon sink during 2000-2020 - Liang Shi; Honglin He; Li Zhang; Junbang Wang; Xiaoli Ren; Guirui Yu; Peng Hou; Jixi Gao; Bin Chen; Keyu Qin; Lili Feng; Shaoqiang Wang; et al. (Resources, Conservation and Recycling, 2025)

LcMYB5, an R2R3-MYB family gene from Lonicera caerulea L., enhances drought and salt tolerance in transgenic tobacco and blue honeysuckle - Chunlin Fu; Chunyang Bian; Jing Chen; Qian Zhang; Dong Qin; Jiangkuo Li; Peng Zhang; Junwei Huo; Huixin Gang (Journal of Plant Physiology, 2025)

Study on the evolution of ecological flow in river and its guarantee degree during different hydrological periods - Xue Chen; Qin Li; Zhuo Jia; Rui Xiao; Zhijin Cheng; Yuhao Peng (Journal of Cleaner Production, 2025)

Deciphering thermal failure mechanism of Sodium-Ion battery with O3-phase layered cathode - Shini Lin; Wei Li; Yuan Qin; Honghao Xie; Xue Li; Jing Zeng; Peng Zhang; Jinbao Zhao (Chemical Engineering Journal, 2025)

Multi-modal resonance of topological hybrid graphene foam for enhanced acoustic absorption - Chengqi Zhang; Wenhao Tong; Huasong Qin; Xin Ming; Lidan Wang; Yue Yu; Yi Mao; Jiahao Lu; Peng Li; Tongyang Shi; Kai Pang; Yingjun Liu; et al. (Chemical Engineering Journal, 2025)

Engineering atomic Pt-N3 sites on CdS nanorods for overcoming the rate-determining organic dehydrogenation in photocatalytic coproduction of H2 and value-added chemicals - Huanmin Liu; Jiayi Peng; Xu Zhang; Kun Zheng; Lirong Zheng; Kangle Lv; Qin Li; Peng Zhou (Chemical Engineering Journal, 2025)

Rapid gelation of mechanical robust, conductive, and self-healing lignocellulosic nanofibrils hydrogel toward flexible sensor over a broad temperature spectrum - Zhi-Chao Xu; Yu-Qin Yang; Xiao-Wen Pang; Baiyu Jiang; Peng-Fei Mao; Li-Xiu Gong; Binghao Wang; Li Peng; Long-Cheng Tang; Shi-Neng Li (Chemical Engineering Journal, 2025)

Corrigendum to “Copper doped carbon dots modified bacterial cellulose with enhanced antibacterial and immune regulatory functions for accelerating wound healing” [Carbohydrate Polymers 346 (2024) 122656] - Yingyu Liu; Yifan Zhao; Susu Guo; Danlei Qin; Jingyu Yan; Huaiyi Cheng; Jian Zhou; Jianing Ren; Lingxiang Sun; Hongyi Peng; Xiuping Wu; Bing Li (Carbohydrate Polymers, 2025)

China's methane emissions derived from the inversion of GOSAT observations with a CMAQ and EnKS-based regional data assimilation system - Xingxia Kou; Zhen Peng; Xiao Han; Jialin Li; Li Qin; Meigen Zhang; Robert J. Parker; Hartmut Boesch (Atmospheric Pollution Research, 2025)

Transitional shale reservoir quality evaluation based on Random Forest algorithm—a case study of the Shanxi Formation, eastern Ordos Basin, China - Wanli Gao; Qin Zhang; Jingtao Zhao; Wen Liu; Weiliang Kong; Guangyin Cai; Tianquan Qu; Hongjie Peng; Wenyu Li; Yugang Yang; Yingfang Zhou; Zhen Qiu (Earth Science Informatics, 2025)

Evaluation of the Decreased Cholesterol Potential of Levilactobacillus brevis M-10 Isolated from Spontaneously Fermented Sour Porridge in Mice with High-Cholesterol Levels - Qi Wang; Jiawei Peng; Ye Tian; Jianhua Li; Jin Cai; Wenjun Qin (Current Microbiology, 2025)

Development of seismic risk models for low-rise masonry structures considering age and deterioration effects - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Lin-Lin Zheng; Can Zhang (Bulletin of Earthquake Engineering, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Fractionation and tidal characteristics of per- and polyfluoroalkyl substances in the estuarine maximum turbidity zone - Chang Liu; Xin-Xin Ma; Si-Quan Wang; Qin Li; Peng Cheng; Wei Hou; Yong-Yu Li; Wen-Long Li; Xin-Hong Wang (Science of The Total Environment, 2024)

Effect of 9-year water and nitrogen additions on microbial necromass carbon content at different soil depths and its main influencing factors - Xiujin Yuan; Yuchun Qi; Yu Guo; Yunshe Dong; Qin Peng; Zhongqing Yan; Zhaolin Li; Ruyue Dong; Yilian Zheng (Science of The Total Environment, 2024)

Nitrogen oxides emissions from coastal wetland sediments: Experimental assessment of the influence of vegetation and nitrogen input - Jiang-Chen Gong; Bing-Han Li; Chun-Ying Liu; Qin-Dao Li; Jing-Wen Hu; Pei-Feng Li; Dan He; Gui-Peng Yang (Science of The Total Environment, 2024)

Surface in situ Co-Mn modification over LaMnO3 perovskite with enhanced activity for ethane combustion - Peng Zhao; Jingwei Liu; Wei Zhu; Jie Meng; Zhuang Li; Jinwei Qin; Xiaohui Wang; Haiqin Wan; Chao Yao; Lin Dong (Journal of Environmental Chemical Engineering, 2024)

Effect of trehalose dehydration on crystal morphology and food caking during post-treatment - Ronghua Peng; Jingwei Cai; Xueyou Qin; Mingxuan Li; Yanbo Liu; Jiahui Li; Miao Ma; Ziwen Deng; Mingyang Chen; Junbo Gong (Food Research International, 2024)

A smartphone-based supramolecular biosensor for portable and rapid detection of buprofezin in real food samples - Yilin Zhan; Na Li; Tianyi Qin; Linhui Peng; Weihua Deng; Zhongyong Xu; Lei Wang; Immanuel David Charles; Bin Liu (Food Chemistry, 2024)

Polygonati Rhizoma varieties and origins traceability based on multivariate data fusion combined with an artificial intelligence classification algorithm - Peng Chen; Chenghao Fei; Rao Fu; Xiaoyan Xiao; Yuwen Qin; Xiaoman Li; Zhijun Guo; Jianmin Huang; De Ji; Lin Li; Tulin Lu; Qiaosheng Guo; et al. (Food Chemistry, 2024)

Phenolic compounds in dietary target the regulation of gut microbiota: Role in health and disease - Qinqiu Zhang; Yi Xu; Danka Bukvicki; Yue Peng; Fan Li; Qing Zhang; Jing Yan; Shang Lin; Shuxiang Liu; Wen Qin (Food Bioscience, 2024)

Copper doped carbon dots modified bacterial cellulose with enhanced antibacterial and immune regulatory functions for accelerating wound healing - Yingyu Liu; Yifan Zhao; Susu Guo; Danlei Qin; Jingyu Yan; Huaiyi Cheng; Jian Zhou; Jianing Ren; Lingxiang Sun; Hongyi Peng; Xiuping Wu; Bing Li (Carbohydrate Polymers, 2024)

rAAV-CRISPR/Cas9-mediated in vivo delivery of porcine embryos to construct knockout pigs - Mengyu Gao; YuTing He; XingLong Zhu; WanLiu Peng; Xinmei Liu; Yanyan Zhou; Yang Deng; Qin Liu; Guangneng Liao; Yi Li; Wei Ni; Guang Yang; et al. (Science China Life Sciences, 2024)

Comparative analyses of immune gene profiles and antioxidant capabilities in the midgut and liver of three species of grass carps (Ctenopharyngodon idella) following gut infection with Aeromonas hydrophila - Wei-Sheng Luo; Zi-Han Xu; Qin-Yang He; Jie Peng; Fei Wang; Jian Li; Sheng-Wei Luo (Aquaculture International, 2024)

Seismic multiple attenuation based on improved U-Net - Quan Zhang; Xiao-yu Lv; Qin Lei; Bo Peng; Yan Li; Yao-wen Zhang (Applied Geophysics, 2024)

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Unveiling the toxicological effects and risks of prometryn on red swamp crayfish (Procambarus clarkii): Health assessments, ecological, and molecular insights - Lang Zhang; Ziwei Song; Li He; Shan Zhong; Xiaoqian Ju; Hang Sha; Jing Xu; Qiuying Qin; Jie Peng; Hongwei Liang (Science of The Total Environment, 2024)

Insights into the environmental risk variation of heavy metals from MSWI fly ash after thermal plasma vitrification - Xiaoqing Lin; Yizhe Shen; Zhiliang Chen; Jie Chen; Peng Yi; Qin Wang; Xiaodong Li; Jianhua Yan (Process Safety and Environmental Protection, 2024)

A newly identified secretory phospholipase A2 group XIIA homolog (LcPLA2XIIA) in Larimichthys crocea exhibits antimicrobial and antitumor activities - Shouhu Li; Chuang Qin; Shi-Ming Peng; Ya-Bing Wang; Yuan Wang; Xiao-Shan Wang; Jian-Gao Shi; Xin-Cang Li (Fish & Shellfish Immunology, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Classification and regression machine learning models for predicting the combined toxicity and interactions of antibiotics and fungicides mixtures - Li-Tang Qin; Jun-Yao Zhang; Qiong-Yuan Nong; Xia-Chang-Li Xu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Environmental Pollution, 2024)

Dual functionality of cathode microporous layers: Reducing hydrogen permeation and enhancing performance in proton exchange membrane water electrolyzers - Junjie Wang; Dingding Ye; Jian Huang; Qin Peng; Fang Chen; Barbara Mecheri; Alessandra D’Epifanio; Enrico Traversa; Jie Song; Guizhi Xu; Jun Li; Xun Zhu; et al. (Chemical Engineering Journal, 2024)

Disentangling the spatially combined and temporally lagged influences of climate oscillations on seasonal droughts in the East Asian monsoon influenced Poyang Lake Basin - Zikang Xing; Jianhui Wei; Yunliang Li; Xuejun Zhang; Miaomiao Ma; Peng Yi; Qin Ju; Patrick Laux; Harald Kunstmann (Atmospheric Research, 2024)

Monthly Runoff forecasting using A Climate‑driven Model Based on Two-stage Decomposition and Optimized Support Vector Regression - Zhuo Jia; Yuhao Peng; Qin Li; Rui Xiao; Xue Chen; Zhijin Cheng (Water Resources Management, 2024)

Unveiling potential sex-determining genes and sex-specific markers in autotetraploid Carassius auratus - Kun Zhang; Xu Huang; Chongqing Wang; Xidan Xu; Xiaowei Xu; Xiaoping Dong; Qingwen Xiao; Jinhai Bai; Yue Zhou; Zhengkun Liu; Xinyi Deng; Yan Tang; et al. (Science China Life Sciences, 2024)

Assessment of the seismic failure of reinforced concrete structures considering the directional effects of ground motions - Si-Qi Li; Ke Du; Yong-Sheng Chen; Peng-Fei Qin; Gabriele Milani; Antonio Formisano; Peng-Chi Chen; Lin-Lin Zheng; Can Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sesquiterpene lactones from Tithonia diversifolia with ferroptosis-inducing activities - Ao-Xue Ding; Yi-Ming Shan; Chen-Yue Li; Guo-Qing Qin; Tong Chen; Qing Wang; Xiang-Gang Hu; Peng-Ju Guo; Hai-Jun Yu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

Occurrence and maturation transformation of organic and inorganic nitrogen in the Lower Cambrian shelf–slope facies shale: Implications for overmature N2-rich shale reservoirs in Southern China - Guangming Meng; Haifeng Gai; Xiumin Yang; Ping Gao; Qin Zhou; Chengang Lu; Gang Li; Xing Wang; Peng Cheng (Marine and Petroleum Geology, 2024)

Zinc oxide nanoparticles and nano-hydroxyapatite enhanced Cd immobilization, activated antioxidant activity, improved wheat growth, and minimized dietary health risks in soil-wheat system - Guangxin Li; Ran Duan; Xinran Liang; Hongen Liu; Shiyu Qin; Long Wang; Haichao Fu; Peng Zhao; Chang Li (Journal of Environmental Chemical Engineering, 2024)

Multi-scenario application of chitosan emulsions as fat replacers: Based on the regulation of chitosan hydrophobicity and emulsion rheological properties - Cheng-Zhen Nie; Yao Li; Xu-Hui Huang; Hao-Peng Wang; Xu-Song Wang; Xiu-Ping Dong; Bei-Wei Zhu; Lei Qin (Food Hydrocolloids, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

Programmable bionanocomposite coated fertilizers for prolonged controlled release of nitrogen - Jiaxuan Liu; Yue Yuan; Ji Gao; Zhaoxian Qin; Wenbo Peng; Akanksha Lakra; Yuxuan Zhang; Shugang Zhang; Guodong Liu; Yongsheng Chen; Qun Li; Zhaohui Tong (Chemical Engineering Journal, 2024)

The differentiated adoption of green planting technology by farmers and its influencing factors: the case from Juxian County, China - Xiao Lyu; Wenlong Peng; Yi Qu; Mengzhen Li; Qin Wang; Sergey Yu. Solodovnikov; Tatsiana V. Serhiyevich (Environment, Development and Sustainability, 2024)

In vitro generation of trophoblast like stem cells from goat pluripotent stem cells - Qin Na; Siyu Zhang; Peng Shao; Yu Jia; Yanqiu Wang; Mengyi Wei; Yanglin Chen; Chen Chen; Lixia Zhao; Zixin Wang; Yongli Song; Baojiang Wu; et al. (Theriogenology, 2024)

Activity of OSBPI fungicide fluoxapiprolin against plant-pathogenic oomycetes and its systemic translocation in plants - Chengcheng Li; Song Tian; Yixin Fu; Yiying Li; Jianqiang Miao; Qin Peng; Xili Liu (Pesticide Biochemistry and Physiology, 2024)

The impact of aeration rate on the denitrification performance and microbial community characteristics of the HN-AD bacteria-inoculated MBBR system - Qian Zhang; Chenxi Yang; Shumin Qin; Peng Zhang; Yu Hu; Huacan Tian; Baiying Liu; Haiying Chen; Wei Li (Journal of Water Process Engineering, 2024)

Resolve the species-specific effects of iron (hydr)oxides on the performance of underlying zerovalent iron for metalloid removal: Identification of their key properties - Peng Fan; Xuechen Wu; Jianrong Zeng; Lina Li; Kun Qian; Hejie Qin; Xiaohong Guan (Journal of Hazardous Materials, 2024)

Rational design of a dual-mode fluorescent probe for portable detection of pyriproxyfen in the environment and food - Zhongyong Xu; Qifeng Zheng; Na Li; Weihua Deng; Tianyi Qin; Taoyuze Lv; Lei Wang; Mingle Li; Xiaoqiang Chen; Wenxing Zhang; Bin Liu; Xiaojun Peng (Journal of Hazardous Materials, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Aquaporin mediated silicon-enhanced root hydraulic conductance is benefit to cadmium dilution in tobacco seedlings - Zhiguo Liu; Lei Hou; Jiyuan Yan; Parvaiz Ahmad; Mengzhan Qin; Runze Li; Mohamed A. El-Sheikh; Rupesh Deshmukh; Sreeja S. Sudhakaran; Basharat Ali; Li Zhang; Long Yang; et al. (Journal of Hazardous Materials, 2024)

Comprehensive transcriptome, physiological and biochemical analyses reveal that key role of transcription factor WRKY and plant hormone in responding cadmium stress - Xiuzhe Wu; Jiyuan Yan; Mengzhan Qin; Runze Li; Tao Jia; Zhiguo Liu; Parvaiz Ahmad; Mohamed A. El-Sheikh; Krishna Kumar Yadav; Joan Manuel Rodríguez-Díaz; Li Zhang; Peng Liu (Journal of Environmental Management, 2024)

Recent advances in nanomaterials-enabled active food packaging: Nanomaterials synthesis, applications and future prospects - Bo Peng; Jichao Qin; Yujie Li; Kao Wu; Ying Kuang; Fatang Jiang (Food Control, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Electro-mechano transduction of stacked triboelectric nanogenerator considering wave force: Modeling, validation and applications - Chen Cao; Fan Shen; Chuanfu Xin; Qin Zhang; Qiwei Zheng; Ying Gong; Heming Liu; Yan Peng; Zhongjie Li (Chemical Engineering Journal, 2024)

A novel mesoporous carbon pocket with single atom Cr sites for high performance Lithium-Sulfur battery - Zhenwen Li; Peng Li; Zheng Huang; Dong Wang; Dongshen Ma; Liyu Zheng; Shaojie Lu; Qin Yue (Chemical Engineering Journal, 2024)

Sodic adakitic granites in the East Kunlun Orogen, China: Partial melting of ultrahigh-pressure metamorphic terranes during continental collision - Lei Qin; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Li-Qun Dai; Gang Wen; You-Shan Xia; Yao Zhou (Chemical Geology, 2024)

SS-31 mitigates oxidative stress and restores mitochondrial function in cigarette smoke-damaged oral epithelial cells via PINK1-mediated mitophagy - Pei Ye; Hong Liu; Yao Qin; Zhiyuan Li; Zhuwei Huang; Xiangwen Bu; Qiao Peng; Ning Duan; Wenmei Wang; Xiang Wang (Chemico-Biological Interactions, 2024)

Investigation of Toxoplasma gondii Infection in Yunnan Semi-fine Wool Sheep (Ovis aries) and wild Rodents in Yunnan, China - Zhao Li; Wen-Jie Cheng; Cai-Qin Deng; Meng-Ling Deng; Hai-Bo Peng; Xing-Quan Zhu; Feng-Cai Zou (Acta Parasitologica, 2024)

Feasibility exploration and comparative analysis of interspecific hybridization between Crassostrea hongkongensis and Crassostrea dianbaiensis - Jiangwei Li; Yanping Qin; Zhongli Peng; Weitao Wan; Chao Yue; Zhongyu Wang; Haitao Ma; Qinggan Xing; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2024)

A deep learning approach for hydrofoil optimization of tidal turbines - Changming Li; Bingchen Liang; Peng Yuan; Qin Zhang; Junzhe Tan; Xiancai Si; Yonghui Liu (Ocean Engineering, 2024)

New insights of selective rupture of synthetic sample under high voltage pulse discharge: A numerical simulation of electric field distribution - Yonghong Qin; Ziyu Yang; Yuexin Han; Peng Gao; Yanjun Li; Ningyu Zhang; Jianming Gao (Minerals Engineering, 2024)

A highly efficient and selective rapid detection method applied to the detection of amide herbicides in fish serum - Sili Zeng; Zhongxiang Chen; Li Huang; Chenhui Li; Peng Wang; Dongli Qin; Lei Gao (Food Chemistry, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

All-in-one, gas-permeable, ultrathin, flexible, and self-adhesive epidermal electrode for biopotential recording and muscle theranostics - Hui-Ling Peng; Tu Qian; Tong Xian; Chunsheng Jiang; Yunbai Qin; Quanfu Li; Shuxiang Song (Chemical Engineering Journal, 2024)

Synergy between electron donor and steric hindrance in Alkylated-Piperazine absorbents for efficient CO2 capture - Shaojun Jia; Yao Jiang; Yi Li; Wu Chen; Jin Huang; Kang Wang; Xiao-Qin Liu; Peng Cui (Chemical Engineering Journal, 2024)

A blue light 3D printable hydrogel with water absorption, antibacterial, and hemostatic properties for skin wound healing - Xiu-Chong He; Xiu-Ning Chen; Yi-Hao Liu; Xinyu Zhong; Lei Qiang; Hong-Qin Wang; Fang-Zhou Wang; Jun-Song Wang; Cheng-Hui Li; Peng-Fei Zheng (Chemical Engineering Journal, 2024)

Insights into the combined toxicity and mechanisms of BDE-47 and PFOA in marine blue mussel: An integrated study at the physiochemical and molecular levels - Qianqian Geng; Liang Zou; Mengmeng Guo; Jixing Peng; Fengling Li; Yujie Bi; Shuqi Jiang; Hanlin Qin; Zhijun Tan (Aquatic Toxicology, 2024)

Response of soil aggregate-associated fertility and microbial communities to afforestation in the degraded ecosystem of the Danjiangkou Reservoir, China - Peng Chen; Li Wang; Jun-Ya Li; Wenjie Wan; Run-Qin Zhang; Yi Liu; Zhi-Guo Li (Plant and Soil, 2024)

Comprehensive Insights into the Health Effects of Selenium Exposure and Supplementation Among the Chinese Community Middle-Aged and Elderly: a Combined Retrospective Cohort Study and Intervention Study - Chen Li; Xiangwen Peng; Jiayang Zheng; Kexin Shi; Liqiang Qin; Qinyi Yang; Zhangmin Wang; Ying Liu; Lei Huang (Biological Trace Element Research, 2024)

Impact of the biological fouling on the hydrodynamic characteristics of nets under different current and attack angle conditions - Songchen Yu; Hongde Qin; Peng Li; Fangyu Gong (Aquacultural Engineering, 2024)

Numerical and experimental study of two common types of fouled net panels in the ocean - Peng Li; Fangyu Gong; Hongde Qin; Songchen Yu (Aquacultural Engineering, 2024)

Biomass power generation: A pathway to carbon neutrality - Wei Du; Zhanpeng Cui; Jinze Wang; Yiming Qin; Jianhuai Ye; Nan Lin; Yuanchen Chen; Wenyan Duan; Zhaofeng Chang; Hao Li; Peng Zhang; Bo Pan (Science of The Total Environment, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Development of transcriptional factor-based whole-cell biosensors to monitor and degrade antibiotics using mutant cells obtained via adaptive laboratory evolution - Jiawei Li; Ziqing Qin; Baohui Zhang; Xiaofeng Wu; Jing Wu; Lifeng Peng; Yi Xiao (Journal of Hazardous Materials, 2024)

Analysis of Root Response Mechanism of Quinoa Seedlings to Waterlogging Stress Based on Metabolome - Yirui Guo; Qianchao Wang; Heng Xie; Xuesong Zhang; Tingzhi Huang; Ping Zhang; Junna Liu; Li Li; Peng Qin (Journal of Plant Growth Regulation, 2024)

Examining the evolution of tidal creeks in the Huanghe River delta using multi-temporal Landsat images - Zhen Han; Kai Jin; Quanli Zong; Peng Qin; Chunxia Liu; Xiuzhi Zhu; Xinyue Li (Journal of Oceanology and Limnology, 2024)

RETRACTED: Effect of calcium and phosphorus on ammonium and nitrate nitrogen adsorption onto iron (hydr)oxides surfaces: CD-MUSIC model and DFT computation - Mengke Jia; Jie Ma; Qiongqiong Zhou; Lijie Liu; Xiaolei Jie; Hongen Liu; Shiyu Qin; Chang Li; Fuqing Sui; Haichao Fu; Haijiao Xie; Long Wang; et al. (Chemosphere, 2024)

Deep tillage enhances the spatial homogenization of bacterial communities by reducing deep soil compaction - Ruiwen Hu; Bufan Zheng; Yongjun Liu; Shuguang Peng; Jia Gong; Junhui Li; Tian Qin; Jingsong Liang; Kunlong Xiong; Lanjun Shao; Zhongyi Zheng; Zhenxie Yi; et al. (Soil and Tillage Research, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Source rock and climate model for the Cretaceous Jiufotang Formation, Kazuo Basin, China: Geochemistry and petrography - Shangli Liu; Haifeng Gai; Peng Cheng; Qin Zhou; Tengfei Li; Sui Ji; Xing Wang; Hui Tian (Organic Geochemistry, 2024)

Electroporation of Chlorella vulgaris with laboratory devices capable of generating arbitrary waveform pulses - Liuxia Li; Zihuang Peng; Nan Liu; Yi Liu; Hua Li; Qin Zhang; Fuchang Lin (Innovative Food Science & Emerging Technologies, 2024)

Simultaneous removal of NO and VOCs by Si doping CeO2 based catalysts: An acidity and redox properties balance strategy - Lina Gan; Peng Ye; Xi Tian; Jinxing Mi; Jiaying Xing; Qitong Xue; Qin Wu; Jianjun Chen; Junhua Li (Fuel, 2024)

Rapid immunoassays for the detection of quinoxalines and their metabolites residues in animal-derived foods: A review - Liangni Qin; Jiaxu Xiao; Hongfei Yang; Jixiang Liang; Long Li; Shixiang Wu; Dapeng Peng (Food Chemistry, 2024)

The effects of dextran in residual impurity on trehalose crystallization and formula in food preservation - Mingxuan Li; Jiahui Li; Xueyou Qin; Jingwei Cai; Ronghua Peng; Mengdi Zhang; Leida Zhang; Wei Zhao; Mingyang Chen; Dandan Han; Junbo Gong (Food Chemistry, 2024)

Combination of virtual screening, machine learning, molecular dynamics simulations and sensory evaluation to discover novel umami peptides from fermented Atlantic cod - Hao Zou; Hao Wang; Jinlong Zhao; Hua Feng; Shanyu Peng; Qingwen Liu; Zhihui Qin; Ziye Zhang; Hong Lin; Zhenxing Li (Food Bioscience, 2024)

Pickering emulsion stabilized by glycosylated whey protein isolate complexed with chitooligosaccharide for the improving stability of delivery and bioaccessibility of DHA - Lian Zhou; Yang Liu; Yaochang Li; Wenhao Zhou; Sihao Peng; Xinguang Qin; Gang Liu; Haizhi Zhang (Food Hydrocolloids, 2024)

Development and application of intelligent packaging films based on carboxymethyl starch/PVA with Cu-LTE nanocrystal as functional compatibilizer - Nannan Li; Hai Qin; Qun Tang; Daijiang Peng; Xiaoyan Luo; Heping Li; Zhiming Zou (Food Packaging and Shelf Life, 2024)

Electrode microstructure design to improve effective utilization of Fe-N/C catalysts towards oxygen reduction reaction process - Qin Peng; Yang Yang; Haokai Xu; Monja Schilling; Akeel Shah; Roswitha Zeis; Pang-Chieh Sui; Xun Zhu; Jun Li; Qiang Liao (Chemical Engineering Journal, 2024)

Toxicity, Oxidative Stress, and Tissue Distribution of Butachlor in the Juvenile Chinese Mitten Crab (Eriocheir sinensis) - Song Wu; Peng Wang; Ying Zhang; Li Huang; Qirui Hao; Lei Gao; Dongli Qin; Xiaoli Huang (Fishes, 2024)
The Chinese mitten crab (Eriocheir sinensis) is one of the most commercially important crustacean species in China. The aim of this study was to characterize the toxic effects of butachlor (an herbicide of the acetanilide class) on juvenile E. sinensis crabs. The lethal effects and the acute toxicity of butachlor on juvenile E. sinensis specimens were assessed through a semi-static in vitro experiment. We determined the activities of superoxide dismutase (SOD) and catalase (CAT) as well as the levels of glutathione (GSH) and malondialdehyde (MDA) in the gills and the hepatopancreas of the juvenile crabs, at different time points over a 14-day short-term exposure to butachlor. Moreover, we measured the residual levels of butachlor in three different tissues (gills, hepatopancreas, and muscles) of the juvenile crabs over a longer period. Our findings revealed that butachlor is highly toxic for juvenile E. sinensis crabs. In fact, the median lethal concentration (LC50) values of butachlor at 24, 48, 72, and 96 h were found to be 4.22, 1.84, 0.34, and 0.14 mg/L, respectively, while the safe concentration was 0.014 mg/L. The antioxidant defense ability of the juvenile E. sinensis crabs against butachlor was induced after exposure to the herbicide at a concentration of 0.01 mg/L. After 14 days of exposure to butachlor at 0.04 and 0.16 mg/L, both SOD and CAT were found to be significantly inhibited (p

Toxic interactions at the physiological and biochemical levels of green algae under stress of mixtures of three azole fungicides - Li-Tang Qin; Yu-Xue Lei; Min Liu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Science of The Total Environment, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

The conversion of mycorrhizal types closely associated with the changes in microbial keystone taxa and potential function in subtropical forests - Wenhao Jin; Jiaying Tu; Weixing Sheng; Jiajia Xing; Liyuan Peng; Xiaomin Ma; Junhui Chen; Yongfu Li; Hua Qin (Plant and Soil, 2024)

Two new chromone derivatives from the rhizosphere soil fungus Ilyonectria robusta - Min Kuang; Wei-Wei Peng; Yuan-Tao Huang; Mei-Fang Li; Si-Yu Qin; Yu-Ting Zheng; Li Xu; Qi Huang; Zhen-Xing Zou (Natural Product Research, 2024)

Newly-found ferns in an artificially illuminated deep karst cave have the most negative known carbon isotope values - Yunxia Li; Qianqian Qin; Yiping Tian; Jiayan Li; Chenxi Yang; Shiyin Peng; Fuxi Shi; Zhiguo Rao (Science Bulletin, 2024)

Investigation of gas diffusion behavior and detection of 86 Ah LiFePO4 batteries in energy storage systems during thermal runaway - Zhuangzhuang Jia; Shuping Wang; Peng Qin; Changhao Li; Kaiqiang Jin; Jinhua Sun; Qingsong Wang (Process Safety and Environmental Protection, 2024)

Magnetic nickel ferrite for efficient persulfate activation to remove aqueous refractory organics: Synthesis, advantages, mechanism, and environmental implications - Guang Xian; Zeqing Long; Bing Qin; Jie Liu; Wei Peng; Bin Jing; Guangming Zhang; Qiangang Li; Siqi Li (Journal of Environmental Chemical Engineering, 2024)

Organic nanowire sensor with seeing, smelling and heat sensation capabilities - Jian Song; Xinyue Cui; Peng Liu; Yaohua Shi; Xingjie Wang; Miao Li; Yuanyuan Zhou; Jien Yang; Hairui Liu; Yong Yan; Congxin Xia; Ruiping Qin (Chemical Engineering Journal, 2024)

Seismic hazard models for typical urban masonry structures considering optimized regression algorithms - Si-Qi Li; Yi-Ru Li; Jia-Cheng Han; Peng-Fei Qin; Ke Du (Bulletin of Earthquake Engineering, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Eighteen iridoids from the roots and rhizomes of Valeriana jatamansi and their protective effects against α-hemolysin - Yao Zhu; Peng-Ju Guo; Ao-Xue Ding; Liu Zheng; Gao-Xiang Du; Tong Chen; Guo-Qing Qin; Xiang-Gang Hu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

The pre-corrosion fatigue behavior of 321 steel coated by laser additively manufactured FeCoNiCrMn high-entropy alloy - Wei Li; Shengnan Hu; Shunpeng Zhu; Guowei Bo; Chipeng Zhang; Houjun Qin; Hui Chen; Libo Zhou; Xulong Peng; Jianjun He; Cong Li; Shengde Zhang; et al. (Ocean Engineering, 2024)

Impact of deoxynivalenol on rumen function, production, and health of dairy cows: Insights from metabolomics and microbiota analysis - Jia-nan Dong; Zhi-kun Zhao; Zhan-qing Wang; Song-ze Li; Yong-peng Zhang; Zhe Sun; Gui-xin Qin; Xue-feng Zhang; Wei Zhao; Natnael Demelash Aschalew; Tao Wang; Yu-guo Zhen (Journal of Hazardous Materials, 2024)

Monospecific and ultrasensitive detection of ofloxacin: A computational chemistry-assisted hapten screening strategy and analysis of molecular recognition mechanism - Jiaxu Xiao; Liangni Qin; Dan Zhao; Niexie Huang; Wennuo Xu; Linwei Zhang; Xiaoming Pan; Shiyun Han; Mingyue Ding; Long Li; Tao Le; Dapeng Peng (Journal of Hazardous Materials, 2024)

Three-dimensional lookup table for more precise SAR scatterers positioning in urban scenarios - Chisheng Wang; Mingxuan Wei; Xiaoqiong Qin; Tao Li; Shuo Chen; Chuanhua Zhu; Peng Liu; Ling Chang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Assessment of nonylphenol exposure based on global urinary concentration data and its risk analysis - Jiemei Li; Hongling Zhang; Juanhua Li; Ning Qin; Qiufen Wei; Yuanyuan Li; Yang Peng; Han Li (Environmental Research, 2024)

Constructing light-insensitive Ag(I) sites by in situ integration of nanoheaters for efficient adsorptive desulfurization - Jun Liu; Zhen Fu; Peng Tan; Min Li; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Successive landsliding on the G213 National Highway, a section of the Sichuan-Qinghai traffic corridor (May 10, 2023, Songpan County, Sichuan, China) - Yizhi Li; Shunyu Huang; Peng Tang; Yichao Wang; Gianvito Scaringi; Enlong Liu; Minghui Meng; Liang Qin (Landslides, 2024)

Nanotechnology of inhalable vaccines for enhancing mucosal immunity - Li Qin; Yanhua Sun; Nan Gao; Guixia Ling; Peng Zhang (Drug Delivery and Translational Research, 2024)

Electrochemical capacitance of clay minerals by diamine modification - Yi Liao; Shan-Shan Chai; Wei-Bin Zhang; Yao Yao; Jing-Lei Yang; Yi Yin; Jia-Jun Li; Ze-Qin Yang; Xue-Jing Ma; Qiang Peng (Applied Clay Science, 2024)

Design of an active-source seismic detection system based on illumination analysis and migration imaging experiments: considering the Zhuxi mining area as an example - Wen Li; Yong Chen; Shan-Hui Xu; Jiu-Peng Hu; Bao-Jin Liu; Yong-Peng Ouyang; Yin-Juan He; Ya-Li Tan; Xin-Sheng Hua; Jing-Jing Qin; Qian Li; Jia Jia (Applied Geophysics, 2024)

Corrigendum to “Exposure to benzo(a)pyrene interfered with cell composition and immune ability of common carp (Cyprinus carpio) intestine through inducing cell heterogeneous responses” [Volume 579, 30 January 2024] - Qirui Hao; Peng Wang; Dongli Qin; Zhongxiang Chen; Chenhui Li; Li Huang; Song Wu; Jixian Yang (Aquaculture, 2024)

Association of co-exposure to polycyclic aromatic hydrocarbons and phthalates with oxidative stress and inflammation - Zhuliangzi Lu; Qin Li; Yingyi Dai; Xinhong Pan; Xiaoyan Luo; Rongfei Peng; Chongshan Guo; Lei Tan (Science of The Total Environment, 2024)

Four pairs of neolignan enantiomers with distinctive isochroman moiety from the fruits of Crataegus pinnatifida and their protective activities against H2O2-induced SH-SY5Y cells - Peng Zhao; Shi-Fang Li; Jiao-Yang Hou; Shu-Yan Qin; Jia-Yi Li; Xiao-Fang Zhou; Xuan Liu; Jin-Le Hao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Enantiomeric α-pyrone derivatives with immunosuppressive activity from Talaromyces adpressus - Meijia Zheng; Chenxi Zhou; Hong Liao; Qin Li; Alan Bao; Chunmei Chen; Feng He; Peng Wu; Weiguang Sun; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2024)

Homoerythrina-type alkaloids with neuroprotective activity from the branches of Cephalotaxus hainanensis Li - Hao Yan; Hao Wang; Peng-Wei Chen; Li Yang; Hui-Qin Chen; Fei Wu; Pei Wang; Hao-Fu Dai; Xiao-Long Huang; Shuang-Qing Zhou; Wen-Li Mei (Phytochemistry Letters, 2024)

Enhanced atmospheric water harvesting (AWH) by Co-based MOF with abundant hydrophilic groups and open metal sites - Sihan Li; Peng Wu; Long Chen; Yiwen Tang; Yanhe Zhang; Ling Qin; Xiaofei Qin; Haibo Li (Journal of Water Process Engineering, 2024)

Tuning CO2 hydrogenation selectivity via support interface types on Cu-based catalysts - Caiyun Han; Langlang Qin; Peng Wang; Haotian Zhang; Yunfei Gao; Minghui Zhu; Shuang Wang; Jinping Li (Fuel, 2024)

Corrigendum to “Procyanidin B2: A promising multi-functional food-derived pigment for human diseases” [Food Chem. 420 (2023) 136101] - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2024)

Increasing winter wheat yield and nitrogen utilization, and reducing residual soil nitrogen in semi-humid areas: A study matching deep fertilizer application with regional water scenarios - Yingxin Wang; Yirui Xu; Qin Guo; Hui Li; Peng Zhang; Tie Cai; Zhikuan Jia (European Journal of Agronomy, 2024)

Cannabinoids improve mitochondrial function in skeletal muscle of exhaustive exercise training rats by inhibiting mitophagy through the PINK1/PARKIN and BNIP3 pathways - Juncheng Si; Lili Sun; Ying Qin; Lina Peng; Yongshan Gong; Chun Gao; Wenhui Shen; Mengqi Li (Chemico-Biological Interactions, 2024)

Integration of transcriptome and metabolome reveals the accumulation of related metabolites and gene regulation networks during quinoa seed development - Qianchao Wang; Jirong Shi; Junna Liu; Ping Zhang; Li Li; Heng Xie; Hanxue Li; Hongxin Wang; Chenghong Liu; Peng Qin (Plant Molecular Biology, 2024)

Dietary Zinc Ameliorates TNBS-Induced Colitis in Mice Associated with Regulation of Th1/Th2/Th17 Balance and NF-κB/NLRP3 Signaling Pathway - Changlin Wen; Jiayu Wang; Zhenhua Sun; Rao Zhong; Mengjie Li; Xuemei Shen; Qiaobo Ye; Kaihua Qin; Xi Peng (Biological Trace Element Research, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Exposure to benzo(a)pyrene interfered with cell composition and immune ability of common carp (Cyprinus carpio) intestine through inducing cell heterogeneous responses - Qirui Hao; Peng Wang; Dongli Qin; Zhongxiang Chen; Chenhui Li; Li Huang; Song Wu; Jixian Yang (Aquaculture, 2024)

In vivo and in vitro antiviral effect and mechanisms of rhein against nervous necrosis virus - Xiang Liu; Bing-Ke Li; Qin-Xue Liu; Peng-Fei Li; Fei Ling; Gao-Xue Wang (Aquaculture, 2024)

Binding interaction of environmental DNA with typical emerging perfluoroalkyl acids and its impact on bioavailability - Chao Qin; Lei Xiang; Yi-Ze Wang; Peng-Fei Yu; Can Meng; Yan-Wen Li; Hai-Ming Zhao; Xiaojie Hu; Yanzheng Gao; Ce-Hui Mo (Science of The Total Environment, 2024)

Conjugative plasmids facilitate the transmission of tmexCD2-toprJ2 among carbapenem-resistant Klebsiella pneumoniae - Hong Yao; Tingting Zhang; Kai Peng; Junke Peng; Xu Liu; Ziwei Xia; Leizi Chi; Xiaoyu Zhao; Shihong Li; Sheng Chen; Shangshang Qin; Ruichao Li (Science of The Total Environment, 2024)

The carbon budget of China: 1980–2021 - Xiaosheng Xia; Peiyang Ren; Xuhui Wang; Dan Liu; Xiuzhi Chen; Li Dan; Bin He; Honglin He; Weimin Ju; Minqi Liang; Xingjie Lu; Jing Peng; et al. (Science Bulletin, 2024)

Assessment of heavy metals concentrations in five marine organisms from Lianyungang in China and the corresponding health risk - Ya-Qin Zhang; Chun-Hui Gong; Xiang-Hua Qi; Wen-Jun Wang; Peng-Tao Cao; Qiang Li; Peng Wang; Yi Yang (Regional Studies in Marine Science, 2024)

Resistance risk assessment of mefentrifluconazole in Corynespora cassiicola and the control of cucumber target spot by a two-way mixture of mefentrifluconazole and prochloraz - Qin Peng; Xiuhuan Li; Guixiang Li; Xinchang Hao; Xili Liu (Pesticide Biochemistry and Physiology, 2024)

Reduction of soil methane emissions from croplands with 20–40 years of cultivation mediated by methane-metabolizing microorganisms - Tian Qin; Yongjun Liu; Ruiwen Hu; Kun Yang; Bufan Zheng; Junhui Li; Zhixuan Liu; Peng Li; Tingting Ma; Kunlong Xiong; Jingsong Liang; Zhongwen Rang; et al. (Journal of Cleaner Production, 2024)

The use of urea hydrogen peroxide as an alternative N-fertilizer to reduce accumulation of arsenic in rice grains - Zhenni Peng; Chuxia Lin; Kaiqing Fan; Jidong Ying; Huashou Li; Junhao Qin; Rongliang Qiu (Journal of Environmental Management, 2024)

Effects of konjac glucan-nan/low-acyl gellan edible coatings loaded thymol-β-cyclodextrin microcapsules on postharvest blueberry - Jie Ding; Chunyan Liu; Peng Huang; Hongying Li; Yan Liu; Dur E. Sameen; Yuwei Zhang; Yaowen Liu; Wen Qin (Food Chemistry, 2024)

Large-area nanofiber membrane of NIR photothermal Cs0.32WO3 for flexible and all-weather solar thermoelectric generation - Sheng Zhuo; Wangkai Jiang; Yu Dong Zhao; Jin-Zhuo Liu; Xinyu Zhao; Jianyong Ye; Min Zheng; Zuo-Shan Wang; Xiao-Qing Zhou; Xiao-Qiao Wang; Ying-Li Shi; Weifan Chen; et al. (Chemical Engineering Journal, 2024)

Seismic response of a mid-story isolated structure considering SSI in mountainous areas under long-period earthquakes - Feng Wan; Shengwu Qin; Dewen Liu; Tiange Zhao; Yanping Zheng; Hang Shan; Zhiang Li; Fusong Peng; Jingran Xu; Min Lei (Earthquake Engineering and Engineering Vibration, 2024)

Association of glyphosate exposure with multiple adverse outcomes and potential mediators - Wenxiang Li; Daizai Lei; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yunru Lin; Fan Xu; Yuan-jun Qin (Chemosphere, 2023)

Gestational exposure to ambient fine particulate matter disrupts maternal hepatic lipid metabolism - Yunlu Wu; Yirun Wang; Wenhui Zhang; Jing Peng; Li Qin; Lu Zhang; Rucheng Chen; Weijia Gu; Qinghua Sun; Cuiqing Liu; Ran Li (Chemosphere, 2023)

Spatial variation of soil phosphorus in the water level fluctuation zone of the Three Gorges Reservoir: Coupling effects of elevation and artificial restoration - Dongming Qin; Shanze Li; Jingfu Wang; Dengjun Wang; Peng Liao; Yuchun Wang; Zhiqiang Zhu; Zhihui Dai; Zuxue Jin; Xinping Hu; Shuoru Qiu; Yiming Ma; et al. (Science of The Total Environment, 2023)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

Investigation of the acicular aragonite growth behavior in AOD stainless steel slag during slurry-phase carbonation - Ya-Jun Wang; Jun-Guo Li; Meng-Jie Tao; Xi Zhang; Jian-Bao Zhang; Song Qin; Shao-Hua Liu; Li-Jie Peng; Xiao-Pei Zhang; Ya-Nan Zeng (Science of The Total Environment, 2023)

Associations between long-term exposure to PM2.5 chemical constituents and allergic diseases: evidence from a large cohort study in China - Chuanteng Feng; Ying Shao; Tingting Ye; Changwei Cai; Chun Yin; Xiaobo Li; Hongyun Liu; Hua Ma; Bin Yu; Mingfang Qin; Yang Chen; Yongfang Yang; et al. (Science of The Total Environment, 2023)

Three point mutations in AaCYP51 combined with induced overexpression of AaCYP51 conferred low-level resistance to mefentrifluconazole in Alternaria alternata - Guixiang Li; Xiuhuan Li; Yan Zeng; Shuailin Liao; Yue Chen; Jianqiang Miao; Qin Peng; Xili Liu (Pesticide Biochemistry and Physiology, 2023)

Two new eudesmane sesquiterpenoids with neuroprotective activity from Pogostemon cablin - Qi Zheng; Chuan Ma; Liang Xiong; Cheng Peng; Li Guo; Da-Le Guo; E Zhao; Qin-Mei Zhou; Ou Dai (Phytochemistry Letters, 2023)

Highly efficient removal of Aflatoxin B1 employing a flower-like covalent organic framework-based fiber membrane - Shuning Li; Kang Qin; Yixue Fu; Defu He; Dianpeng Han; Shuang Li; Yu Wang; Shuyue Ren; Yuan Peng; Zhixian Gao (Journal of Environmental Chemical Engineering, 2023)

Fragmentation engineering on the edge of hydroxy-functional COFs for the enhanced photocatalytic production of H2O2 and direct photo-oxidation of benzene to phenol in aqueous systems - Shijian Zhou; Yuexin Shi; Guangyuan Chen; Weiguo Kong; Hao Hu; Haoran Xie; Changlai Li; Jinping Qin; Zewu Zhang; Luming Peng; Xiaokang Ke; Yan Kong (Chemical Engineering Journal, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

Association between polycyclic aromatic hydrocarbon exposure and blood lipid levels: the indirect effects of inflammation and oxidative stress - Si Zhou; Xiaotong Li; Yingyi Dai; Chongshan Guo; Rongfei Peng; Pengzhe Qin; Lei Tan (Environmental Science and Pollution Research, 2023)

Proteomic characteristics of six snake venoms from the Viperidae and Elapidae families in China and their relation to local tissue necrosis - Wan-Gang Qin; Zhan-Peng Zhuo; Hao Hu; Mimi Lay; Qian-Qin Li; Jun-Ting Huang; Liang-Bo Zeng; Zi-Jing Liang; Fei Long; Qing Liang (Toxicon, 2023)

Soil aggregate-associated organic carbon mineralization and its driving factors in rhizosphere soil - Jun-Ya Li; Peng Chen; Zhi-Guo Li; Lin-Yang Li; Run-Qin Zhang; Wei Hu; Yi Liu (Soil Biology and Biochemistry, 2023)

New insights on the breakage mechanism of magnetite quartzite via high voltage pulse discharge: liberation, property difference, micro morphology, and numerical simulation - Yonghong Qin; Yuexin Han; Peng Gao; Yanjun Li; Yanxia Guo; Fangqin Cheng (Minerals Engineering, 2023)

Phylotranscriptomic analyses reveal deep gene tree discordance in Camellia (Theaceae) - Qiong Zhang; Ryan A. Folk; Zhi-Qiong Mo; Hang Ye; Zhao-Yuan Zhang; Hua Peng; Jian-Li Zhao; Shi-Xiong Yang; Xiang-Qin Yu (Molecular Phylogenetics and Evolution, 2023)

Recycling valuable metals from spent lithium-ion battery cathode materials based on microwave-assisted hydrogen reduction followed by grind-leaching and magnetic separation - Jinxiang You; Zhongxiao Qin; Gaohui Wang; Mingjun Rao; Jun Luo; Zhiwei Peng; Shang Zou; Guanghui Li (Journal of Cleaner Production, 2023)

Dissecting the genetic basis of grain weight and size in common oat by genome-wide association study - Honghai Yan; Di Deng; Pingping Zhou; Yun Peng; Xiaolong Dong; Shuchang Li; Yongjie Zhang; Qin Man; Ziqin Lv; Tao Chen; Changzhong Ren; Yuanying Peng (Journal of Cereal Science, 2023)

A novel C-type lectin (SpccCTL) suppresses MCRV replication by binding viral protein and regulating antiviral peptides in Scylla paramamosain - Qing-Feng Yang; Shouhu Li; Guang-Peng Feng; Chuang Qin; Xiu-Wen Min; Wen-Hong Fang; Yue Wu; Jin Zhou; Xin-Cang Li (Fish & Shellfish Immunology, 2023)

GRg1 inhibits the TLR4/NF-kB signaling pathway by upregulating miR-216a-5p to reduce growth factors and inflammatory cytokines in DR - Liping Xue; Min Hu; Qin Zhu; Yadi Li; Guanglong Zhou; Xiaofan Zhang; Yuan Zhou; Jieying Zhang; Peng Ding (Molecular Biology Reports, 2023)
Background Diabetic retinopathy (DR) is a common diabetic neurodegenerative disease that affects vision in severe cases. Current therapeutic drugs are ineffective for some patients with severe side effects, and ginsenoside-Rg1 (GRg1) has been shown to protect against DR and may serve as a new potential drug for DR. This study aimed to confirm the protective effect of GRg1 against DR and its molecular mechanism. Methods Human retinal microvascular endothelial cells (hRMECs) and rats were used to construct DR models in vitro and in vivo. Cell proliferation was detected by BrdU assays, the cell cycle was detected by flow cytometry, and TNF-α, IL-6 and IL-1β levels were detected by ELISA. qRT‒PCR, Western blotting and immunohistochemistry were used to detect the expression of related genes and proteins, and angiogenesis assays were used to assess angiogenesis. RIP and RNA pull down assays were used to determine the relationship between miR-216a-5p and TLR4; retinal structure and changes were observed by HE staining and retinal digestive spread assays. Results GRg1 effectively inhibited HG-induced hRMEC proliferation, cell cycle progression and angiogenesis and reduced the levels of intracellular inflammatory cytokines and growth factors. HG downregulated the expression of miR-216a-5p and upregulated the expression of TLR4/NF-kB signaling pathway-related proteins. Importantly, GRg1 inhibited TLR4/NF-kB signaling pathway activation by upregulating miR-216a-5p, thereby inhibiting HG-induced cell proliferation, cell cycle progression, angiogenesis, and the production of inflammatory cytokines and growth factors. In addition, animal experiments confirmed the results of the cell experiments. Conclusions GRg1 inhibits TLR4/NF-kB signaling by upregulating miR-216a-5p to reduce growth factors and inflammatory cytokines in DR, providing a potential therapeutic strategy for DR.

Effects of heavy metal exposure on hypertension: A machine learning modeling approach - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Chemosphere, 2023)

Konjac glucomannan/low-acyl gellan gum edible coating containing thymol microcapsule regulates cell wall polysaccharides disassembly and delays postharvest softening of blueberries - Peng Huang; Jie Ding; Chunyan Liu; Hongying Li; Chenlin Wang; Yezi Lin; Dur E. Sameen; Md Alomgir Hossen; Mingrui Chen; Jing Yan; Yaowen Liu; Wen Qin (Postharvest Biology and Technology, 2023)

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Association between co-exposure to phenols, phthalates, and polycyclic aromatic hydrocarbons with the risk of frailty - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Environmental Science and Pollution Research, 2023)

Multiple insights into lignin-mediated cadmium detoxification in rice (Oryza sativa) - Qin Dong; Yingjie Wu; Bing Li; Xi Chen; Lu Peng; Zulfiqar Ali Sahito; Huanxiu Li; Yulan Chen; Qi Tao; Qiang Xu; Rong Huang; Youlin Luo; et al. (Journal of Hazardous Materials, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Procyanidin B2: A promising multi-functional food-derived pigment for human diseases - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Approximate analytical solution to the axisymmetric model for PVD-enhanced in-situ flushing of double-layered contaminated soils - Lianghua Jiang; Aifang Qin; Linzhong Li; Peng Tang (Computers and Geotechnics, 2023)

Kinetically accelerated oxygen evolution reaction in metallic (oxy)hydroxides enabled by Cr-dopant and heterostructure - Feng Cao; Mengyang Li; Yixuan Hu; Xinge Wu; Xin Li; Xiangying Meng; Peng Zhang; Song Li; Gaowu Qin (Chemical Engineering Journal, 2023)

Metabolic characteristics of self-pollinated wheat seed under red and blue light during early development - Ping Zhang; Yongsheng Tang; Yongjiang Liu; Junna Liu; Qianchao Wang; Hongxin Wang; Hanxue Li; Li Li; Peng Qin (Planta, 2023)

Three-dimensional experimental investigation on hazard reduction of landslide-generated impulse waves in the Baihetan Reservoir, China - Huang Bolin; Yin Yueping; Li Renjiang; Zhang Peng; Qin Zhen; Li Yang; Cheng Shulou; Li Qiuwang; Xu Kaikai (Landslides, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Precipitation regulates the responses of xylem phenology of two dominant tree species to temperature in arid and semi-arid forest of the southern Altai Mountains - Wenjin Wang; Jian-Guo Huang; Tongwen Zhang; Li Qin; Shaowei Jiang; Peng Zhou; Yaling Zhang; Josep Peñuelas (Science of The Total Environment, 2023)

Spatio-temporal variations of nitrate pollution of groundwater in the intensive agricultural region: Hotspots and driving forces - Xueqiang Zhu; Peng Miao; Jimin Qin; Wanhong Li; Lei Wang; Zhujun Chen; Jianbin Zhou (Journal of Hydrology, 2023)

A sensitive and specific enzyme-linked immunosorbent assay for the detection of pymetrozine in vegetable, cereal, and meat - Xiaoyang Yin; Huaming Li; Shuangmin Wu; Yanrong Lu; Yalin Yang; Liangni Qin; Long Li; Jiaxu Xiao; Jixiang Liang; Yu Si; Tao Le; Dapeng Peng (Food Chemistry, 2023)

Theoretical study of supported ionic liquid membrane reaction and transport for CO2 cycloaddition reaction - Jian-Fei Sun; Xu-Peng Chen; Xin-Tong Li; Kun-Peng Yu; Qin-Qin Xu; Jin-Tao Wu; Lin Li; Jian-Zhong Yin (Chemical Engineering Journal, 2023)

Effects of elevated temperature and acidification on sulfate assimilation and reduction of microalgae - Qin-Dao Li; Pei-Feng Li; Shan-Shan Duan; Chun-Ying Liu; Li-Jun Xie; Gui-Peng Yang (Journal of Applied Phycology, 2023)

Gas-in-Place (GIP) Variation and Main Controlling Factors for the Deep Wufeng-Longmaxi Shales in the Luzhou Area of the Southern Sichuan Basin, China - Wei Wu; Peng Cheng; Shenyang Liu; Chao Luo; Haifeng Gai; Haitao Gao; Qin Zhou; Tengfei Li; Kesu Zhong; Hui Tian (Journal of Earth Science, 2023)

Divergent molecular responses of greater amberjack (Seriola dumerili) to acute salinity stress revealed by comparative transcriptome analysis - Yuqi Liu; Yuchen Yang; Ruotong Qin; Yuhao Peng; Yang Huang; Chunhua Zhu; Guangli Li; Dongneng Jiang; Hongjuan Shi (Frontiers in Marine Science, 2023)
Greater amberjack ( Seriola dumerili ) is an important commercial fish for its high growth rate and excellent flesh quality. However, its sensitivity to variations of water salinity poses challenges to the cage culture. In this study, the greater amberjack were reared in the optimum salinity (30 ppt, CK) and undesired regimes (10 and 40 ppt) for 72 hours. The molecular adaptive mechanisms to salinity stress were revealed by the comparative transcriptome analysis for the gills and kidneys. In gills, a total of 445 and 423 differentially expressed genes (DEGs) were identified in 10 and 40 ppt salinity stress groups, respectively. Those DEGs were involved in cartilage and skeletal development, ions transport, and immune response. The major ion secretion and osmoregulation transport proteins gene slc12a2 / nkcc1 and cftr expression levels were significantly down-regulated at 10 ppt, but slightly activated at 40 ppt, compared with the control group. The expression changes in response to the Na + , K + movement, and Cl - ion secretion reduced under the hypo-osmotic exposure and ion excretion boost upon hyper-salinity stress. Meanwhile, the cartilage and skeletal development were enhanced in the gills by hypo- or hyper-salinity stimuli, which is critical for maintaining gill structures and improving respiration and osmoregulation under salinity stress. In kidneys, 600 and 539 DEGs were identified in 10 and 40 ppt groups, respectively. Those DEGs were enriched in oxygen transport, pronephros development, regulation of growth, blood coagulation, ion transmembrane transport, and immune response. While the known renal Na + /Cl – co-transporter gene slc12a3 / ncc expression level was significantly down-regulated at 10 ppt, the organic cation transporter 2 gene slc22a2 , ammonium transmembrane transport gene rhd and rhag expression levels were overexpressed under the hyper-salinity condition at 40 ppt, contributing to the salts secretion and ammonium transport regulation, to combat the osmotic influx of salts following the drink of seawater and elevated ammonia production upon high salinity stress. These findings advance our knowledge of adaptative mechanisms to the salinity stress and provide theoretical guidance for the optimal breeding mode for the aquaculture of greater amberjack.

Two new isoquinolines from Corydalis saxicola - Zhi-Wei Ouyang; Ji-Man He; Feng Qin; Ling Li; Wen-Di Tang; Dian-Peng Li; Jiang-Ke Qin (Natural Product Research, 2023)

High-quality petroleum-like fuels and/or profitable value-added platform chemicals manufactured via a solid acid-catalyzed two-stage fast oil shale pyrolysis - Guojing Xu; Zhaoyang Ren; Lijie Cui; Zhenpeng Wang; Nannan Wang; Peng Li; Bo Guan; Xujin Qin; Penglei Chen (Fuel, 2023)

Orally administered BZL-sRNA-20 oligonucleotide targeting TLR4 effectively ameliorates acute lung injury in mice - Dandan Zhao; Yuhao Qin; Jiaqi Liu; Kegong Tang; Shuaiyao Lu; Zirui Liu; Yexuan Lin; Cong Zhang; Fengming Huang; Jiahui Chang; Chang Li; Mingyao Tian; et al. (Science China Life Sciences, 2023)

New insights into the phylogeny and evolution of Chinese Ovophis (Serpentes, Viperidae): Inferred from multilocus data - Yang‐Mei Zeng; Ke Li; Qin Liu; Ya‐Yong Wu; Shao‐Bing Hou; Gui‐Gang Zhao; Sang Ngoc Nguyen; Peng Guo; Lei Shi (Zoologica Scripta, 2023)
The Asian pitviper genus Ovophis is a group of venomous snakes widely distributed in mid to high elevation mountains in Asia, and presently five species are recognised. However, its systematics, species diversity and species distribution boundaries remain poorly understood. We reconstructed the phylogenetic relationships and explored species diversity of Chinese Ovophis based on two mitochondrial fragments (Cyt b and ND4) and four nuclear genes ( BACH1 , c‐mos , Rag1 , NT3 ) and also conducted a morphological comparison between focal species. Our results indicated that the species diversity had been underestimated within Ovophis and we described a population from southern Yunnan, China, as a new taxon, naming it as Ovophis malhotrae sp . nov . Based on more extensive sampling, we redefined the distribution of O. monticola and O. makazayazaya in China. Divergence date estimation suggested that Ovophis originated at about 16.79 Ma in the middle Miocene.

KCNQ1 rs2237892 polymorphism modify the association between short-term ambient particulate matter exposure and fasting blood glucose: A family-based study - Hexiang Peng; Mengying Wang; Siyue Wang; Xueheng Wang; Meng Fan; Xueying Qin; Yiqun Wu; Dafang Chen; Jing Li; Yonghua Hu; Tao Wu (Science of The Total Environment, 2023)

Knockout of cyclase-associated protein CAP1 confers tolerance towards salt and osmotic stress in Arabidopsis - Qian Zhang; Boya Wang; Xiangge Kong; Kexuan Li; Yaling Huang; Lu Peng; Li Chen; Jiajia Liu; Qin Yu; Juan He; Yi Yang; Xiaoyi Li; et al. (Journal of Plant Physiology, 2023)

Control of N-nitrosodimethylamine (NDMA) formation from N,N-dimethylhydrazine compounds by ozone-based advanced oxidation processes - Yang Song; Jianshan Peng; Kai Li; Sha Feng; Wen Qin; Jin Jiang; Jun Ma (Journal of Hazardous Materials, 2023)

Effects and mechanisms of foam suppression in food waste anaerobic digester using defoaming agents - Pingjin Yang; Lei Li; Shuai Qin; Di Wu; Yun Peng; Hengyi Liu; Xuya Peng (Fuel, 2023)

Thermal efficiency improvement of a spark ignition engine by stratified water distribution - Zhiqiang Li; Yiqiang Pei; Jing Qin; Zhong Peng (Fuel, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Genome-wide Transcriptome Analysis Reveals the Gene Regulatory Network in Star Fruit Flower Blooming - Si Qin; Xiao-Ping Li; Chun-Mei Wu; Le You; Donghui Peng; Sagheer Ahmad; Hui Ren; Zhong-Jian Liu; Jun-Wen Zhai; Sha-Sha Wu (Tropical Plant Biology, 2023)

Schisandrin B Improves the Hypothermic Preservation of Celsior Solution in Human Umbilical Cord Mesenchymal Stem Cells - Ying Zhang; Peng Wang; Mei-xian Jin; Ying-qi Zhou; Liang Ye; Xiao-juan Zhu; Hui-fang Li; Ming Zhou; Yang Li; Shao Li; Kang-yan Liang; Yi Wang; et al. (Tissue Engineering and Regenerative Medicine, 2023)

The effects of serotonergic psychedelics in synaptic and intrinsic properties of neurons in layer II/III of the orbitofrontal cortex - Zi-Hang Tang; Zhi-Peng Yu; Qiong Li; Xiao-Qin Zhang; Kadeliya Muhetaer; Zheng-Chun Wang; Peng Xu; Hao-Wei Shen (Psychopharmacology, 2023)

Phylogenomic insights into the origin and evolutionary history of evergreen broadleaved forests in East Asia under Cenozoic climate change - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Cen Guo; Xin‐Yu Du; Shui‐Yin Liu; Xiang‐Qin Yu; Xiao‐Guo Xiang; Jun Rong; Bing Liu; Zhi‐Fang Liu; Peng‐Fei Ma; De‐Zhu Li (Molecular Ecology, 2023)
The evergreen versus deciduous leaf habit is an important functional trait for adaptation of forest trees and has been hypothesized to be related to the evolutionary processes of the component species under paleoclimatic change, and potentially reflected in the dynamic history of evergreen broadleaved forests (EBLFs) in East Asia. However, knowledge about the shift of evergreen versus deciduous leaf with the impact of paleoclimatic change using genomic data remains rare. Here, we focus on the Litsea complex (Lauraceae), a key lineage with dominant species of EBLFs, to gain insights into how evergreen versus deciduous trait shifted, providing insights into the origin and historical dynamics of EBLFs in East Asia under Cenozoic climate change. We reconstructed a robust phylogeny of the Litsea complex using genome‐wide single‐nucleotide variants (SNVs) with eight clades resolved. Fossil‐calibrated analyses, diversification rate shifts, ancestral habit, ecological niche modelling and climate niche reconstruction were employed to estimate its origin and diversification pattern. Taking into account studies on other plant lineages dominating EBLFs of East Asia, it was revealed that the prototype of EBLFs in East Asia probably emerged in the Early Eocene (55–50 million years ago [Ma]), facilitated by the greenhouse warming. As a response to the cooling and drying climate in the Middle to Late Eocene (48–38 Ma), deciduous habits were evolved in the dominant lineages of the EBLFs in East Asia. Up to the Early Miocene (23 Ma), the prevailing of East Asian monsoon increased the extreme seasonal precipitation and accelerated the emergence of evergreen habits of the dominant lineages, and ultimately shaped the vegetation resembling that of today.

Zein nanospheres assisting inorganic and organic drug combination to overcome stent implantation-induced thrombosis and infection - Hua-Jie Wang; Meng-Fei Hao; Guan Wang; Hao Peng; Fazli Wahid; Yan Yang; Lei Liang; Shan-Qin Liu; Ren-Long Li; Shu-Ying Feng (Science of The Total Environment, 2023)

An efficient approach to synthesize sterile allopolyploids through the combined reproduction mode of ameiotic oogenesis and sperm-egg fusion in the polyploid Carassius complex - Meng Lu; Qin-Can Zhang; Zi-Yu Zhu; Fang Peng; Zhi Li; Yang Wang; Xi-Yin Li; Zhong-Wei Wang; Xiao-Juan Zhang; Li Zhou; Jian-Fang Gui (Science Bulletin, 2023)

The development of a fluorescence/colorimetric biosensor based on the cleavage activity of CRISPR-Cas12a for the detection of non-nucleic acid targets - Yu Wang; Yuan Peng; Shuang Li; Dianpeng Han; Shuyue Ren; Kang Qin; Huanying Zhou; Tie Han; Zhixian Gao (Journal of Hazardous Materials, 2023)

Beer-derived nitrogen, phosphorus co-doped carbon quantum dots: Highly selective on–off-on fluorescent probes for the detection of ascorbic acid in fruits - Xinyue Li; Chao Wang; Peng Li; Xinyang Sun; Zhiying Shao; Ji Xia; Qin Liu; Fei Shen; Yong Fang (Food Chemistry, 2023)

OsPEX1, an extensin-like protein, negatively regulates root growth in a gibberellin-mediated manner in rice - Jieni Li; Yuexiong Zhang; Zhenyong Li; Hang Dai; Xin Luan; Tianxiu Zhong; Shu Chen; Xin-Ming Xie; Gang Qin; Xiang-Qian Zhang; Haifeng Peng (Plant Molecular Biology, 2023)

CRISPR/Cas9-based point-of-care lateral flow biosensor with improved performance for rapid and robust detection of Mycoplasma pneumonia - Rong Zhu; Han Jiang; Chaoyou Li; Yan Li; Min Peng; Junfeng Wang; Qian Wu; Chao Yan; Qingli Bo; Jie Wang; Chenlin Shen; Panzhu Qin (Analytica Chimica Acta, 2023)

Role of ambient climate in the response of soil respiration to different grassland management measures - Shuqi Qin; Qin Peng; Yunshe Dong; Yuchun Qi; Zhaolin Li; Yu Guo; Xingren Liu; Shengsheng Xiao; Xinchao Liu; Junqiang Jia; Yunlong He; Zhongqing Yan (Agricultural and Forest Meteorology, 2023)

Effect of non-fully enclosed windshield on aerodynamic and acoustic behaviors of high-speed train - Deng Qin; Tian Li; Peng Zhou; Jiye Zhang (Environmental Science and Pollution Research, 2023)

Antifungal activity of volatile compounds from Bacillus tequilensis XK29 against Botrytis cinerea causing gray mold on cherry tomatoes - Jianheng Guo; Yue Xu; Sunyan Liang; Zhengkun Zhou; Chunmei Zhang; Kui Li; Xue Peng; Sheng Qin; Ke Xing (Postharvest Biology and Technology, 2023)

AaWIN1, an AP2/ERF protein, positively regulates glandular secretory trichome initiation in Artemisia annua - Chen Wang; Tiantian Chen; Yongpeng Li; Hang Liu; Wei Qin; Zhangkuanyu Wu; Bowen Peng; Xiuyun Wang; Xin Yan; Xueqing Fu; Ling Li; Kexuan Tang (Plant Science, 2023)

Effect of lithofacies on differential movable fluid behaviors of saline lacustrine fine-grained mixed sedimentary sequences in the Jimusar sag, Junggar Basin, NW China: Forcing mechanisms and multi-scale models - Wei Yang; Yaohua Wang; Ming Xie; Yingyan Li; Yang Gao; Yuan Deng; Changfu Xu; Jianhua Qin; Shouchang Peng; Leilei Yang; Linjie Yao; Haodong Hou (Marine and Petroleum Geology, 2023)

Effect of air frying and baking on physicochemical properties and digestive properties of scallop (Patinopecten yessoensis) adductor muscle - Zi-Ye Wang; Zi-Xuan Wu; Guan-Hua Zhao; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2023)

Quality analysis of ultra-fine whole pulp of bamboo shoots (Chimonobambusa quadrangularis) fermented by Lactobacillus plantarum and Limosilactobacillus reuteri - Lei Wang; Yan-Yu Luo; Ying Zhang; Chun-Xia Zou; Peng-Ju Wang; Li-Kang Qin; Qiu-Jin Zhu; Yu-Long Jia (Food Bioscience, 2023)

VOC emission profiles from typical solid fuel combustion in Fenhe River Basin: Field measurements and environmental implication - Qin Peng; Lizhen Li; Jian Sun; Kun He; Bin Zhang; Haijiang Zou; Hongmei Xu; Junji Cao; Zhenxing Shen (Environmental Pollution, 2023)

Shaking table experimental investigations on dynamic characteristics of CFRP cable dome - Weihong Qin; Han Gao; Zhuo Xi; Peng Feng; Yunjie Li (Engineering Structures, 2023)

Water-favored reaction mechanism for selective catalytic conversion of 2-methylfuran to 1,4-pentanediol - Min Wu; Ting Wang; Wenhui Li; Qin Zhang; Bin Zhang; Kaiqin Chen; Siyuan Peng; Guojia Li; Jinning Huang; Qiang Wang; Chuan Wang (Chemical Engineering Journal, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Sedimentary and tectonic evolution of the Banquan pull-apart basin and implications for late Cenozoic dextral strike-slip movement of the Tanlu Fault Zone - Peng Shu; Xiwei Xu; Shaoying Feng; Baojin Liu; Kang Li; Paul Tapponnier; Xiaojuan Deng; Guihua Chen; Nuan Xia; Hongtai Xu; Jingjing Qin; Fubing He; et al. (Science China Earth Sciences, 2023)

Brassica seed meal fumigation restores beneficial bacterial communities by enriching taxa with high resistance and resilience - Junwei Peng; Minchong Shen; Ruihuan Chen; Hong Liu; Yang Sun; Qin Liu; Yuanhua Dong; Jiangang Li (Plant and Soil, 2023)

Canopy greenness, atmospheric aridity, and large rain events jointly regulate evapotranspiration partitioning in a temperate semiarid shrubland - Shaorong Hao; Xin Jia; Yanmei Mu; Tianshan Zha; Shugao Qin; Peng Liu; Yun Tian; Jiandong Qi; Hongxian Zhao; Xinhao Li (Agricultural and Forest Meteorology, 2023)

A record-breaking extreme heat event caused unprecedented warming of lakes in China - Weijia Wang; Kun Shi; Xiwen Wang; Siqi Wang; Dong Zhang; Yuanyuan Peng; Na Li; Yunlin Zhang; Yibo Zhang; Boqiang Qin; R. Iestyn Woolway; Erik Jeppesen (Science Bulletin, 2023)

Appropriate oxygen vacancies and Mo-N bond synergistically modulate charge transfer dynamics of MoO3−x/S-CN for superior photocatalytic disinfection: Unveiling synergistic effects and disinfection mechanism - Ya-Ya Yang; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Hao-Peng Feng; Lu Li; Hui-Yun Liu; Qian-Qian Fan; Meng-Zhu Qin (Journal of Hazardous Materials, 2023)

Distribution, source, risk and phytoremediation of polycyclic aromatic hydrocarbons (PAHs) in typical urban landscape waters recharged by reclaimed water - Zheng Zhu; Lanxin Li; Yanan Yu; Liqiong Tan; Zhefeng Wang; Siyu Suo; Chuang Liu; Yiming Qin; Xianchun Peng; Haoran Lu; Wenyan Liang (Journal of Environmental Management, 2023)

Permeability of micro-scale structure in coal: Insights from μ-CT image and pore network modelling - Peng Liu; Baisheng Nie; Zhengduo Zhao; Jiajun Li; Huiming Yang; Chaozhong Qin (Gas Science and Engineering, 2023)

Tracking and dating incipient melting of a new grouplet of primitive achondrites - Yun Jiang; Ye Li; Jia Liu; Qing Wang; Li-Ping Qin; Ke Zhu; Shiyong Liao; Zongjun Yin; Yongbo Peng; Piers Koefoed; Weibiao Hsu (Geochimica et Cosmochimica Acta, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Self-supply of H2O2 and O2 by a composite nanogenerator for chemodynamic therapy/hypoxia improvement and rapid therapy of biofilm-infected wounds - Junjie Wu; Peng Shen; Xian Qin; Yulu Yang; Chuanchuan Lin; Xuan Li; Wenbo Geng; Pengfei Gao; Lixue Chen; Li Miao; Yang Jiao; Bailong Tao (Chemical Engineering Journal, 2023)

Air-Backed Aluminum Shells Subjected to Underwater Penetration: Torpedo Interception Simulations - Chucai Peng; Chufan Ding; Bin Chen; Xichen Sun; Weibing Li; Taotao Qin; Jun Feng (Journal of Marine Science and Engineering, 2023)
Underwater torpedoes have become a serious threat to ocean liners and warships, and the interception against attacking torpedoes is always the hotspot in marine engineering. To simulate the underwater torpedo interception by a high velocity projectile, this work numerically deals with the process of projectile water entry and sequent penetration into underwater aluminum shells, whereby conical and ogival nose projectiles are comparatively studied. With the arbitrary Lagrange–Euler (ALE) algorithm adopted to describe fluid medium, the projectile water entry model is developed and validated against the test data. Similarly, the penetration model validation is made by modeling a tungsten ball perforation on an aluminum plate. Covered by water fluid, the air-backed aluminum shell is utilized to simulate an underwater torpedo subjected to projectile impact. The numerical predictions of underwater penetration reveal that ogival nose projectiles have a superior performance in underwater motion and perforation while conical nose counterparts deteriorate the shell targets more severely. For 20 cm, 40 cm and 60 cm underwater depth scenarios, a numerical prediction suggests that the energy consumed by water is proportional to the water depth, meanwhile aluminum shell perforation absorbs almost the identical projectile kinetic energy. Such findings may shed some light on the nose shape optimization design of high velocity projectile intercepting underwater torpedoes.

Experimental study on drag characteristics of the practical rigid net under different current conditions - Songchen Yu; Hongde Qin; Peng Li; Fangyu Gong; Yu Tian (Frontiers in Marine Science, 2023)
The net structure of a cage is an important component to ensure the survival environment of aquaculture. In order to ensure the safety of the net, an experimental study on practical rigid nets is conducted in this paper. The drag force characteristics of the nets with different mesh sizes and different twine thicknesses are analyzed, and the impact of 90° and 45° attack angles on the drag force characteristics of the net are further studied. The empirical formulae for calculating the drag force of the net under different attack angles are given. The calculated drag forces are compared with the literature, and the results are in good agreement. Particularly, the current velocity is taken as one of the variables in the formulae to include the influence of nonlinear factors caused by the extreme current velocity in the drag force calculation.

Highly efficient transformation of slowly-biodegradable organic matter into endogenous polymers during hydrolytic fermentation for achieving effective nitrite production by endogenous partial denitrification - Chen Xie; Qiong Zhang; Xiyao Li; Qiongpeng Dan; Luyang Qin; Chuanxin Wang; Shuying Wang; Yongzhen Peng (Water Research, 2023)

Geosmin disrupts energy metabolism and locomotor behavior of zebrafish in early life stages - Weicheng Zhou; Yuming Wang; Jinglong Wang; Chengrong Peng; Zhicong Wang; Hongjie Qin; Genbao Li; Dunhai Li (Science of The Total Environment, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Effects of desert riparian vegetation roots on the riverbank retreat process in the Tarim River in China - Quanli Zong; Tiegang Zheng; Ruize Tang; Kai Jin; Lin Li; Peng Qin; Chunxia Liu (Journal of Hydrology, 2023)

Negatively charged nano-hydroxyapatite can be used as a phosphorus fertilizer to increase the efficacy of wollastonite for soil cadmium immobilization - Rong Huang; Peng Mao; Lei Xiong; Guoming Qin; Jinge Zhou; Jingfan Zhang; Zhian Li; Jingtao Wu (Journal of Hazardous Materials, 2023)

Ecophysiology of seed dormancy and germination in the alpine-subalpine medicinal plant species Sinopodophyllum hexandrum (Royle) T. S. Ying - De-Li Peng; Bo-Yang Geng; Ying-Bo Qin; Li-E Yang; Carol C. Baskin; Jerry M. Baskin (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Effects of thymol concentration on postharvest diseases and quality of blueberry fruit - Jie Ding; Chunyan Liu; Peng Huang; Yuwei Zhang; Xinjie Hu; Hongying Li; Yan Liu; Liwei Chen; Yaowen Liu; Wen Qin (Food Chemistry, 2023)

Effect of 4 °C and ice temperature on umami-enhancing nucleotides of conditioned pork - Yin Zhang; Yingjie Zhang; Hui Li; Ting Bai; Qin Qian; Haichuan Peng; Yunlong Mu; Linguo Wang; Baohua Liu; Jie Chen; Zhongli Pan; Dayu Liu; et al. (Food Chemistry, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

Corrigendum to “Dendrobium huoshanense stem polysaccharide ameliorates rheumatoid arthritis in mice via inhibition of inflammatory signaling pathways” [Carbohydr. Polym. 258 (2021) 117657] - Zhen-Zi Shang; Dan-Yang Qin; Qiang-Ming Li; Xue-Qiang Zha; Li-Hua Pan; Dai-Yin Peng; Jian-Ping Luo (Carbohydrate Polymers, 2023)

Evaluation of physicochemical properties, bacterial community, and product fertility during rice straw composting supplemented with different nitrogen-rich wastes - Shi-Peng Wang; Xiao-Xing Li; Zhao-Yong Sun; Wen-Liang Shuai; Zi-Yuan Xia; Cai-Yun Xie; Min Gou; Yue-Qin Tang (Bioresource Technology, 2023)

Comammox Nitrospira and AOB communities are more sensitive than AOA community to different fertilization strategies in a fluvo-aquic soil - Haiyang Liu; Shiyu Qin; Yong Li; Peng Zhao; Zhaojun Nie; Hongen Liu (Agriculture, Ecosystems & Environment, 2023)

Evaluation of digestate-derived biochar to alleviate ammonia inhibition during long-term anaerobic digestion of food waste - Yun Peng; Lei Li; Qin Dong; Pingjin Yang; Hengyi Liu; Wenjie Ye; Di Wu; Xuya Peng (Chemosphere, 2023)

Synergism of cell adhesion regulatory genes and instant air pollutants on blood pressure elevation - Siyue Wang; Mengying Wang; Hexiang Peng; Yaohua Tian; Huangda Guo; Jiating Wang; Huan Yu; Enci Xue; Xi Chen; Xueheng Wang; Meng Fan; Yi Zhang; et al. (Chemosphere, 2023)

Galanin, a central appetite factor, affects appetite signals in the hypothalamus and promotes feeding in Siberian sturgeon (Acipenser baerii Brandt) - Xin Zhang; Shuhuang Chen; Hongwei Wu; Zhengzhi Tian; Ni Tang; Youlian Liu; Peng Tang; Qiang Hu; Yingzi Li; Qin Kang; Defang Chen; Zhiqiong Li (Aquaculture, 2023)

Flash pyrolysis of oil shale assisted by Zr-doped TiOSO4 nanocomposites: Excellent selectivity for hydrocarbons and toluene - Guojing Xu; Peng Li; Penglei Chen; Lijie Cui; Zhenpeng Wang; Zhaoyang Ren; Xujin Qin; Nannan Wang; Minghua Liu (Fuel, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Numerical studies on wake and turbulence characteristics of aquaculture nets - Lingyun Xu; Peng Li; Hongde Qin; Zhijing Xu (Frontiers in Marine Science, 2022)
This paper aims to understand the drag coefficient discrepancy between the equivalent-twine and twisted-twine nets based on their wake and turbulence characteristics. To that end, we conduct unsteady Reynolds-averaged Navier-Stokes (URANS) and the second-moment (Reynolds stress, RSM) simulations at a Reynolds number, Re =4.5×10 3 , based on the effective diameter of the net twine, which corresponds to the subcritical flow regime. Then, the vortex structures and the turbulence statistics are assessed at AOA=90°. The results highlight that the wake interactions for the twisted-twine net are relatively strong compared to the equivalent-twine net, due to the disturbance of the helixes on the twisted twines. In comparison to the classical Karman vortex, the overall vortex shedding of these two nets is well organized. Symmetric vortices form behind the equivalent-twine net, while single vortices form behind the twisted-twine net. Moreover, the Reynolds normal and shear stresses show symmetric and anti-symmetric profiles. The addition of helixes to smooth circular cylinders changes the flow development, leading to a decrease of turbulence kinetic energy. With this understanding, engineers need to be carefully select the net type for preliminary design of marine aquaculture cages to avoid over- or underestimation of the drag forces.

Periodic phosphorus fertilization is beneficial to lowering potential risk of phosphorus loss from Inceptisols - Yongzhuang Wang; Liuying Lai; Xiangying Peng; Hongxing Chen; Joann K. Whalen; Caiyan Lu; Dan Li; Xinying Zhang; Lingling Qin; Xin Chen; Lingtian Xie (Journal of Soils and Sediments, 2022)

Diversity of endophytic fungi in Coptis chinensis Franch. and their activity against methicillin-resistant Staphylococcus aureus - Qianliang Ming; Xiuning Huang; Linming Guo; Dong Liu; Lingyue Qin; Yimo He; Yu Tang; Yanxia Liu; Junkang Liu; Peng Li (Folia Microbiologica, 2022)

Longitude correction method for the field magnetic surveyed diurnal-variation correction - Shu-Peng Su; Bo Li; Hai-Yang Zhang; Hui-Qin Zhao; Jin-Peng Huang (Applied Geophysics, 2022)

Carbon sequestration in soil and biomass under native and non-native mangrove ecosystems - Ziming Zhang; Ying Wang; Yakun Zhu; Kehong He; Tingting Li; Umakant Mishra; Yisheng Peng; Fan Wang; Lingfei Yu; Xiaosong Zhao; Liye Zhu; Xudong Zhu; et al. (Plant and Soil, 2022)

Expression patterns and correlation analyses of muscle-specific genes in the process of sheep myoblast differentiation - Hejie Wang; Minmin Dou; Jun Li; Peng Cao; Junling Li; Tianyan Guo; Dipeng Zhao; Ajab Khan; Yingliang Li; Baojun Li; Jian Qin; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2022)

Dynamic networks of P300-related process - Qin Tao; Lin Jiang; Fali Li; Yuan Qiu; Chanlin Yi; Yajing Si; Cunbo Li; Tao Zhang; Dezhong Yao; Peng Xu (Cognitive Neurodynamics, 2022)

Development of a landscape index to link landscape pattern to runoff and sediment - Peng Shi; Yan-li Qin; Peng Li; Zhan-bin Li; Ling-zhou Cui (Journal of Mountain Science, 2022)

A Novel Thermal-driven Self-assembly Method to Prepare Albumin Nanoparticles: Formation Kinetics, Degradation Behavior and Formation Mechanism - Fang Li; Stacy Yeh; Qin Shi; Peng Wang; Hongyan Wu; Junbo Xin (AAPS PharmSciTech, 2022)

Proteome Based Comparative Investigation of a High Sucrose Sugarcane Mutant in Contrast to the Low Sucrose Mother Variety by Using TMT Quantitative Proteomics - Qaisar Khan; Ying Qin; Dao-Jun Guo; Zhen Lu; Xian-Qiu Xie; Li-Tao Yang; Qiang Liang; Xiu-Peng Song; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

Runoff projections of the Qinling Mountains and their impact on water demand of Guanzhong region in Northwest China - Zhao-peng Zhang; Ke-qin Duan; Huan-cai Liu; Ya-li Meng; Rong Chen; Da-wei Li; Shuang-shuang Li (Journal of Mountain Science, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Response of ancient landslide stability to a debris flow: a multi-hazard chain in China - Jian Guo; Peng Cui; Mingyue Qin; Jiao Wang; Yao Li; Chenxing Wang (Bulletin of Engineering Geology and the Environment, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Localization of salt-tolerant QTL in rice germination stage under different salinity concentrations - Yanning Wang; Liping Chen; Guiting Song; Tao Huang; Guangliang Wu; Jingai Tan; Peng Wang; Qin Cheng; Caijing Li; Qi Zhong; Shiying Huang; Mengmeng Yang; et al. (Euphytica, 2022)

Improved Process Management of Glacial Lake Outburst Flood Hazards by Integrating Modular Monitoring, Assessment, and Simulation - Xiang Wang; Guo Chen; Xiaoai Dai; Jingjing Zhao; Xian Liu; Yu Gao; Junmin Zhang; Yongjun Chen; Xiaozhen Li; Wenyi Qin; Peng Wang (Water Resources Management, 2022)

Metabolomic and antioxidant enzyme activity changes in response to cadmium stress under boron application of wheat (Triticum aestivum) - Shiyu Qin; Yafang Xu; Zhaojun Nie; Hongen Liu; Wei Gao; Chang Li; Peng Zhao (Environmental Science and Pollution Research, 2022)

The specific DNA barcodes based on chloroplast genes for species identification of Theaceae plants - Shuai Jiang; Fenglin Chen; Pai Qin; Hai Xie; Guo Peng; Yongliang Li; Xinhong Guo (Physiology and Molecular Biology of Plants, 2022)

Bone Marrow Mesenchymal Stem Cells Exert Protective Effects After Ischemic Stroke Through Upregulation of Glutathione - Xiao-Yan Lan; Zheng-Wu Sun; Gui-Lian Xu; Cheng-Yan Chu; Hua-Min Qin; Shen Li; Xin Geng; Peng Gao; Johannes Boltze; Shen Li (Stem Cell Reviews and Reports, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Response of soil respiration to water and nitrogen addition and its influencing factors: a four-year field experiment in a temperate steppe - ZhaoLin Li; Qin Peng; YunShe Dong; YunLong He; ZhongQing Yan; Yu Guo; Shuqi Qin; Yuchun Qi (Plant and Soil, 2022)

Selenium inhibits cadmium uptake and accumulation in the shoots of winte wheat by altering the transformation of chemical forms of cadmium in soil - Xiaoming Qin; Peng Zhao; Hongen Liu; Zhaojun Nie; Jiaojiao Zhu; Shiyu Qin; Chang Li (Environmental Science and Pollution Research, 2022)

A survey of brain network analysis by electroencephalographic signals - Cuihua Luo; Fali Li; Peiyang Li; Chanlin Yi; Chunbo Li; Qin Tao; Xiabing Zhang; Yajing Si; Dezhong Yao; Gang Yin; Pengyun Song; Huazhang Wang; et al. (Cognitive Neurodynamics, 2022)

Investigation of Antibiotic-Resistant Bacterial Communities and Antibiotic-Resistant Genes in Wastewater Treatment Plants: Removal of Antibiotic-Resistant Genes by the BBR Process - Zi-fan Weng; Yu-qin He; Guo-xiang Li; Xiao-tong Wu; Yi Dai; Peng Bao (Bulletin of Environmental Contamination and Toxicology, 2022)

Modelling deep convective activity using lightning clusters and machine learning - Manxing Shi; Wei Zhang; Peng Fan; Qihao Chen; Zhipeng Liu; Qin Li; Xiuguo Liu (International Journal of Climatology, 2022)
Retrieving thunderstorm activity through specific thermodynamic and kinematic parameters is paramount for predicting deep convective weather and investigating long‐term climatology of storm. However, the reliability of the relationship between parameters and convective events is restricted by the modelling methods and sampling of thunderstorm activity. There is no objective definition of a thunderstorm, so the clustering method is applied to the cloud‐to‐ground (CG) lightning stroke data in Central China to identify lightning clusters. These clusters are then gridded and associated with environmental variables derived from ERA5 reanalysis. Finally, machine learning (ML) technologies are applied to model the occurrence of thunderstorms. In addition, ERA5 is also evaluated. The parameters related to moisture and lapse rate calculated by ERA5 are close to sounding measurements, such as Td850, PW, LR700_400 and KI, whose correlation coefficients exceed 0.90. ERA5 has a good estimation of some parameters that are susceptible to the influence of the boundary layer. Compared with the lightning strike‐based scheme, our scheme obtains the best performance index values. An agreement between observations and predictions based on lightning clusters is also evident from the diurnal cycle of thunderstorm probabilities. Although thunderstorm activity on complex terrain is underestimated, the created ML model can explain 61.4% of the variance in the observed frequency. The results of the significance test reveal that there are statistically significant differences between the soundings corresponding to some isolated CG strikes and the thunderstorm class, but the distribution is the same as that of the non‐thunderstorm class. Solar radiation, topographic features and lake distribution play a major role in promoting the occurrence and development of thunderstorms.

Fine mapping and candidate gene analysis of qGSN5, a novel quantitative trait locus coordinating grain size and grain number in rice - Hua Yuan; Peng Gao; Xiaoling Hu; Min Yuan; Zhengyan Xu; Mengya Jin; Wencheng Song; Shijie Zhan; Xiaobo Zhu; Bin Tu; Ting Li; Yuping Wang; et al. (Theoretical and Applied Genetics, 2022)

Effect of Sodium Salicylate on Calcium Currents and Exocytosis in Cochlear Inner Hair Cells: Implications for Tinnitus Generation - Ting Fan; Meng-Ya Xiang; Ruo-Qiao Zhou; Wen Li; Li-Qin Wang; Peng-Fei Guan; Geng-Lin Li; Yun-Feng Wang; Jian Li (Neuroscience Bulletin, 2022)

Standard litterbags underestimate early-stage lower-order root decomposition rate in a subtropical forest, China - Guan-tao Chen; Yu-qin Chen; Yong Peng; Hong-ling Hu; Jiu-long Xie; Gang Chen; Yin-long Xiao; Li Liu; Yi Tang; Li-hua Tu (Plant and Soil, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Retraction Note: River wetland landscape planning and design from low-carbon perspective - Qin Li; Peng Wang (Arabian Journal of Geosciences, 2021)

Characteristics and risk factors for Pneumocystis jirovecii pneumonia in patients with idiopathic membranous nephropathy - Lie Yang; Peng Xia; Yangzhong Zhou; Quexuan Cui; Gang Chen; Ke Zheng; Yan Qin; Xuemei Li (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Additive and Epistatic QTL on Cadmium (Cd) Tolerance Associated with Seed Germinating Ability in Rice - Changsheng Li; Peng Wang; Guangliang Wu; Yanning Wang; Qin Cheng; Yicong Cai; Dahu Zhou; Caijing Li; Xiangyu Zhang; Jingai Tan; Cuijuan Li; Haohua He; et al. (Journal of Plant Growth Regulation, 2021)

Humoral immune durability of IgG for anti-SARS-CoV-2 in the normal pregnant women in Wuhan, China - Hongwen Ma; Jing Peng; Ruobing Li; Xuan Zheng; Shiyao Wu; Heng Yin; Min Li; Liu Qin; Fei Tang; Yun Zhao (Immunologic Research, 2021)

Effect of different boron levels on yield and nutrient content of wheat based on grey relational degree analysis - Shiyu Qin; Yafang Xu; Hongen Liu; Chang Li; Yu Yang; Peng Zhao (Acta Physiologiae Plantarum, 2021)

Astragaloside IV inhibits adriamycin-induced cardiac ferroptosis by enhancing Nrf2 signaling - Li-Fei Luo; Peng Guan; Lu-Yun Qin; Jian-Xin Wang; Na Wang; En-Sheng Ji (Molecular and Cellular Biochemistry, 2021)

Mining subsidence prediction for multi-seam and non-rectangular goafs based on probability integral model: a case study from China - Shuaiying Peng; Shengwu Qin; Ming Wang; Guangjie Li (Arabian Journal of Geosciences, 2021)

Paleoclimatic proxies from global closed basins and the possible beginning of Anthropocene - Yu Li; Qin Han; Lu Hao; Xinzhong Zhang; Dawei Chen; Yuxin Zhang; Lingmei Xu; Wangting Ye; Simin Peng; Yichan Li; Zhuowen Feng; Hebin Liu (Journal of Geographical Sciences, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Genome-wide association mapping for resistance to bacterial blight and bacterial leaf streak in rice - Nan Jiang; Jun Fu; Qin Zeng; Yi Liang; Yanlong Shi; Zhouwei Li; Youlun Xiao; Zhizhou He; Yuntian Wu; Yu Long; Kai Wang; Yuanzhu Yang; et al. (Planta, 2021)

RETRACTED ARTICLE: River wetland landscape planning and design from low-carbon perspective - Qin Li; Peng Wang (Arabian Journal of Geosciences, 2021)

Identification of QTL for leaf angle at canopy-wide levels in maize - Dengguo Tang; Zhengjie Chen; Jixing Ni; Qin Jiang; Peng Li; Le Wang; Jinhong Zhou; Chenyang Li; Jian Liu (Euphytica, 2021)

miR-122-5p Mediates Fluoride-Induced Osteoblast Activation by Targeting CDK4 - Chen Li; Yu Qin; Ting Ouyang; Maolin Yao; Aihua Zhang; Peng Luo; Xueli Pan (Biological Trace Element Research, 2021)

Degradation stage effects on vegetation and soil properties interactions in alpine steppe - Cheng-yang Li; Fei Peng; Xian Xue; Chi-min Lai; Wen-juan Zhang; Quan-gang You; Xiao-jie Chen; Xue-qin Zhang; Tao Wang (Journal of Mountain Science, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Construction and characterization of UAA-controlled recombinant Zika virus by genetic code expansion - Rong-Rong Zhang; Qing Ye; Xiao-Feng Li; Yong-Qiang Deng; Yan-Peng Xu; Xing-Yao Huang; Qing Xia; Cheng-Feng Qin (Science China Life Sciences, 2021)

Discrimination of Tourette Syndrome Based on the Spatial Patterns of the Resting–State EEG Network - Keyi Duan; Qian Wu; Yuanyuan Liao; Yajing Si; Joyce Chelangat Bore; Fali Li; Qin Tao; Li Lin; Wei Lei; Xudong Hu; Dezhong Yao; Changfu Pei; et al. (Brain Topography, 2021)

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

Tree-ring-based temperature reconstruction since 1766 ce in the eastern Tianshan Mountains, arid Central Asia - Zhengbing Peng; Li Qin; Xinjian Li; Heli Zhang; Youping Chen; Rui Liu; Ruibo Zhang (Theoretical and Applied Climatology, 2020)

ERas regulates cell proliferation and epithelial–mesenchymal transition by affecting Erk/Akt signaling pathway in pancreatic cancer - Yang Liu; Peng Qin; Rong Wu; Lianfang Du; Fan Li (Human Cell, 2020)
Pancreatic cancer is the fourth most common lethal malignancy with an overall 5-year survival rate of less than 5%. ERas, a novel Ras family member, was first identified in murine embryonic stem cells and is upregulated in various cancers. However, the expression and potential role of ERas in pancreatic cancer have not been investigated. In this study, we found that ERas mRNA and protein were upregulated in pancreatic cancer tissues and cells compared with controls. Knockdown of ERas in pancreatic cancer cells by siRNA significantly decreased cell proliferation, colony formation, migration, and invasion and promoted cell apoptosis in vitro. Epithelial–mesenchymal transition (EMT) is closely related to tumor progression. We observed a significant decrease in N-cadherin expression in pancreatic cancer cells in response to ERas gene silencing by immunofluorescence assay and western blot. Furthermore, tumor growth and EMT were inhibited in xenografts derived from pancreatic cancer cells with ERas downregulation. We further investigated the regulatory mechanisms of ERas in pancreatic cancer and found that ERas may activate the Erk/Akt signaling pathway. Moreover, Erk inhibitor decreased pancreatic cancer cells proliferation and colony formation activities. Our data suggest that targeting ERas and its relevant signaling pathways might represent a novel therapeutic approach for the treatment of pancreatic cancer.

Pharmacokinetic Advantage of ASD Device Promote Drug Absorption through the Epicardium - Reyaj Mikrani; Cunyu Li; Muhammad Naveed; Cuican Li; Mirza Muhammad Faran Ashraf Baig; Qin Zhang; Yue Wang; Juanjuan Peng; Lingzhi Zhao; Xiaohui Zhou (Pharmaceutical Research, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Intrusion of Fall Armyworm (Spodoptera frugiperda) in Sugarcane and Its Control by Drone in China - Xiu-Peng Song; Yong-Jian Liang; Xiao-Qiu Zhang; Zhen-Qiang Qin; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Effects of Spray Parameters of Drone on the Droplet Deposition in Sugarcane Canopy - Xiao-Qiu Zhang; Xiu-Peng Song; Yong-Jian Liang; Zhen-Qiang Qin; Bao-Qing Zhang; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

A continuous simulation of Holocene effective moisture change represented by variability of virtual lake level in East and Central Asia - Yu Li; Yuxin Zhang; Xinzhong Zhang; Wangting Ye; Lingmei Xu; Qin Han; Yichan Li; Hebin Liu; Simin Peng (Science China Earth Sciences, 2020)

Genetic analysis of germinating ability under alkaline and neutral salt stress by a high-density bin genetic map in rice - Xin Luo; Haodong Deng; Peng Wang; Xiangyu Zhang; Caijing Li; Cuijuan Li; Jingai Tan; Guangliang Wu; Yanning Wang; Qin Cheng; Haohua He; Jianmin Bian (Euphytica, 2020)

Flower cultivation regimes affect apocarotenoid accumulation and gene expression during the development of saffron stigma - Guifen Zhou; Liqin Li; Jiemiao Lu; Jing Li; Chong Yao; Peng Sun; Kaohua Liu; Yan Dong; Luping Qin; Xiaodong Qian (Horticulture, Environment, and Biotechnology, 2020)

Preparation of non-sintered lightweight aggregates through co-mechanochemical treatment of oil-contaminated drill cuttings, circulation fluidized bed combustion fly ash, and quicklime - Xiaoyue Chen; Zhonghui Xu; Zhengzhen Yao; Qin Shuai; Zao Jiang; Xi Peng; Yu Li; Ran An; Xin Jiang; Han Li (Environmental Science and Pollution Research, 2020)

Determination of cadmium in rice bran oils by ICP-MS with rapid ultrasound-assisted acid leaching extraction - Zhiying Shao; Mei Xue; Qin Liu; Peng Li; Yong Fang; Qiuhui Hu (Journal of Consumer Protection and Food Safety, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Plant abiotic stress response and nutrient use efficiency - Zhizhong Gong; Liming Xiong; Huazhong Shi; Shuhua Yang; Luis R. Herrera-Estrella; Guohua Xu; Dai-Yin Chao; Jingrui Li; Peng-Yun Wang; Feng Qin; Jijang Li; Yanglin Ding; et al. (Science China Life Sciences, 2020)

Viral metagenomics reveals sapoviruses of different genogroups in stool samples from children with acute gastroenteritis in Jiangsu, China - Wang Li; Surong Dong; Juan Xu; Xiaobin Zhou; Junling Han; Zhaqing Xie; Qin Gong; Hailin Peng; Chenglin Zhou; Mei Lin (Archives of Virology, 2020)
Sapoviruses (SAVs), including several genogroups (GI to GV), are one of the causes of acute gastroenteritis (AGE). In this study, viral metagenomics revealed the presence of sapoviruses of different genogroups in stool from children with AGE. Eight different complete SAV genomes were determined, of which five belonged to GI and the other three belonged to GII, GIV and GV, respectively. Although they were highly similar to published sequences, the GIV and GV were the first complete genome sequences of these SAVs found in China. In a prevalence investigation, 19% of subjects with AGE were positive for SAVs, while none of the control group was positive.

Clinical and biochemical indexes from 2019-nCoV infected patients linked to viral loads and lung injury - Yingxia Liu; Yang Yang; Cong Zhang; Fengming Huang; Fuxiang Wang; Jing Yuan; Zhaoqin Wang; Jinxiu Li; Jianming Li; Cheng Feng; Zheng Zhang; Lifei Wang; et al. (Science China Life Sciences, 2020)

Rutin protects against pirarubicin-induced cardiotoxicity by adjusting microRNA-125b-1-3p-mediated JunD signaling pathway - Qi Li; Meng Qin; Tengteng Li; Zehui Gu; Qi Tan; Peng Huang; Liqun Ren (Molecular and Cellular Biochemistry, 2020)

Global vegetation biomass production efficiency constrained by models and observations - Yue He; Shushi Peng; Yongwen Liu; Xiangyi Li; Kai Wang; Philippe Ciais; M. Altaf Arain; Yuanyuan Fang; Joshua B. Fisher; Daniel Goll; Daniel Hayes; Deborah N. Huntzinger; et al. (Global Change Biology, 2020)
Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

A simple and low-energy method to prepare loratadine nanosuspensions for oral bioavailability improvement: preparation, characterization, and in vivo evaluation - Dandan Yang; Ruirui Li; Fang Zhang; Li Qin; Feifei Peng; Shanshan Jiang; Huiyang He; Xiumei Lu; Peng Zhang (Drug Delivery and Translational Research, 2020)

Heme oxygenase-1 regulates autophagy through carbon–oxygen to alleviate deoxynivalenol-induced hepatic damage - Zhao Peng; Yuxiao Liao; Xiaoqian Wang; Liangkai Chen; Liangliang Wang; Chenyuan Qin; Zhenting Wang; Mengyao Cai; Jiawei Hu; Dan Li; Ping Yao; Andreas K. Nüssler; et al. (Archives of Toxicology, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Enhancement of growth and salt tolerance of tomato seedlings by a natural halotolerant actinobacterium Glutamicibacter halophytocola KLBMP 5180 isolated from a coastal halophyte - You-Wei Xiong; Yuan Gong; Xue-Wei Li; Pan Chen; Xiu-Yun Ju; Chun-Mei Zhang; Bo Yuan; Zuo-Peng Lv; Ke Xing; Sheng Qin (Plant and Soil, 2019)

Genomic characterization of a novel astrovirus identified in Amur tigers from a zoo in China - Hui-Hui Zhang; Qi-Guan Qiu; Shu-Jing Liu; Wen-Qin Hu; Jie-Yu Li; Tian-Ning Liu; You-Song Peng; Xing-Yi Ge; Chao-Ting Xiao (Archives of Virology, 2019)

Application of Multi-rotor Unmanned Aerial Vehicle Application in Management of Stem Borer (Lepidoptera) in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Zhen-Qiang Qin; De-Wei Li; Chun-Yan Wei; Jin-Ju Wei; Yang-Rui Li; Xiu-Peng Song (Sugar Tech, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

Cloning, molecular characterization, and tissue differential expression of connective tissue growth factor (ctgf) of grass carp - Wen-Qian Pan; Jun-Peng Wang; Zhi-Han Tu; Tian Gan; Jing Hu; Jing Wei; Xiang-Jun Leng; Xiao-Qin Li (Fish Physiology and Biochemistry, 2019)

Analysis of the microRNA Profile of Coal-Burning Endemic Fluorosis Using Deep Sequencing and Bioinformatic Approaches - Fei Wang; Chen Li; Yu Qin; Xue Han; Jiayu Gao; Aihua Zhang; Peng Luo; Xueli Pan (Bulletin of Environmental Contamination and Toxicology, 2019)

Performance analysis of indoor pseudolite positioning based on the unscented Kalman filter - Xin Li; Peng Zhang; Guanwen Huang; Qin Zhang; Jiming Guo; Yinzhi Zhao; Qingzhi Zhao (GPS Solutions, 2019)

Identification and Analysis of Vulnerability in Traffic-Intensive Areas of Water Transportation Systems - Yong-jun Chen; Qing Liu; Cheng-peng Wan; Qin Li; Peng-wei Yuan (Journal of Marine Science and Engineering, 2019)
Water transportation accidents have occurred frequently in recent years. In order to improve the emergency response capability of water transportation systems under traffic-intensive conditions, this paper identifies and analyzes the vulnerability in traffic-intensive areas of water transportation systems. Firstly, the vulnerability identification model was constructed based on the analysis of characteristics and the vulnerability-influencing factors of water transportation systems. The newly proposed model is composed of three parts including the DEMATEL (Decision Making Trial and Evaluation Laboratory) method, ISM (interpretative structural modeling) model, and AHP (Analytic Hierarchy Process)–entropy weight method. Finally, a case study of the Yangtze River was conducted to test the logicality and feasibility of the proposed model. The research results reveal that traffic flow density, ship traffic, tides, fog, and bad weather are the key factors affecting the vulnerability of water transportation in traffic-intensive areas of the Yangtze River estuary. However, the influence of navigation aid configuration, berth, anchorage, and obstruction on the system vulnerability is relatively lower. The findings of this study can provide helpful references for maritime administration authorities on the management of water transportation safety.

Mesoscopic Crack Initiation, Propagation, and Coalescence Mechanisms of Coal Under Shear Loading - Lichao Cheng; Jiang Xu; Shoujian Peng; Yixin Liu; Gang Chen; Xinwang Li; Yiling Qin (Rock Mechanics and Rock Engineering, 2019)

Identification and Characterization of ATP/ADP Isopentenyltransferases (ATP/ADP PpIPTs) Genes in Peach - Min-ji Li; Qin-ping Wei; Fu-tian Peng; Wen Yu; Jing-jing Luo; Yong-fei Zhao (Journal of Plant Growth Regulation, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Thalamocortical dysconnectivity in premenstrual syndrome - Peng Liu; Ying Wei; Hai Liao; Yingying Fan; Ru Li; Nana Feng; Gaoxiong Duan; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2019)

Predicting expressway subsidence based on niching genetic algorithm and Holt–Winters model - Shuaiying Peng; Shengwu Qin; Guangjie Li (Arabian Journal of Geosciences, 2019)

First Report on Toxoplasma gondii Seroprevalence in Free-Ranging Pigs in Northeastern China - Qi Li; Si-Yuan Qin; Shuo Li; Peng Peng; Quan Zhao; Hong-Lin Jia; Chun-Ren Wang (Acta Parasitologica, 2019)

A Novel Biscarbazole-Xanthene Hybrid Fluorescent Probe for Selective and Sensitive Detection of Cu2+ and Applications in Bioimaging - Kun Huang; Defang Han; Xianglin Li; Mengni Peng; Qi Qiu; Dabin Qin (Journal of Fluorescence, 2019)

An H-ferritin from the hydrothermal vent shrimp Rimicaris exoculata and its potential role in iron metabolism - Xiao-Li Liu; Sen Ye; Hua-Wei Li; Bo Lu; Yan-Qin Yu; Yu-Peng Fan; Wei-Jun Yang; Jin-Shu Yang (BioMetals, 2019)

Effects of ageing on bioavailability of selenium in soils assessed by diffusive gradients in thin-films and sequential extraction - Qin Peng; Jun Li; Dan Wang; Tian-Jiao Wei; Chang-Er L. Chen; Dong-Li Liang (Plant and Soil, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Occurrence of Telenomus dignus (Gahan) on the Sugarcane Borers, Scirpophaga intacta Snellen and Chilo sacchariphagus Bojer in Guangxi Province, China - Zhen-Qiang Qin; François-Régis Goebel; De-Wei Li; Jin-Ju Wei; Xiu-Peng Song; Ya-Wei Luo; Lu Liu; Zhan-Yun Deng (Sugar Tech, 2018)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Evaluation of Calcium Oxide of Quicklime and Si–Ca–Mg Fertilizer for Remediation of Cd Uptake in Rice Plants and Cd Mobilization in Two Typical Cd-Polluted Paddy Soils - Xin-Yang Li; Jian Long; Pei-Qin Peng; Qi Chen; Xia Dong; Kai Jiang; Hong-Bo Hou; Bo-Han Liao (International Journal of Environmental Research, 2018)

AsA–GSH Cycle and Antioxidant Enzymes Play Important Roles in Cd Tolerance of Wheat - Shiyu Qin; Hongen Liu; Zhaojun Nie; Wei Gao; Chang Li; Yonghui Lin; Peng Zhao (Bulletin of Environmental Contamination and Toxicology, 2018)

Knockout of ush2a gene in zebrafish causes hearing impairment and late onset rod-cone dystrophy - Shanshan Han; Xiliang Liu; Shanglun Xie; Meng Gao; Fei Liu; Shanshan Yu; Peng Sun; Changquan Wang; Stephen Archacki; Zhaojing Lu; Xuebin Hu; Yayun Qin; et al. (Human Genetics, 2018)

Altered topological patterns of brain functional networks in Crohn’s disease - Peng Liu; Ru Li; Chunhui Bao; Ying Wei; Yingying Fan; Yanfei Liu; Geliang Wang; Huangan Wu; Wei Qin (Brain Imaging and Behavior, 2018)

Correlation of IL-31 gene polymorphisms with susceptibility and clinical recurrence of bladder cancer - Qin Li; Tielong Tang; Peng Zhang; Chenlu Liu; Yan Pu; Yan Zhang; Huizi Song; Yanyun Wang; Yaping Song; Min Su; Bin Zhou; Lin Zhang (Familial Cancer, 2018)

Docking study and antiosteoporosis effects of a dibenzylbutane lignan isolated from Litsea cubeba targeting Cathepsin K and MEK1 - Wei Peng; Hui Shen; Bing Lin; Ping Han; Changhui Li; Qiaoyan Zhang; Bingzhu Ye; Khalid Rahman; Hailiang Xin; Luping Qin; Ting Han (Medicinal Chemistry Research, 2018)

Dissecting the genetic basis of heavy panicle hybrid rice uncovered Gn1a and GS3 as key genes - Shiguang Wang; Bingtian Ma; Qiang Gao; Guojing Jiang; Lei Zhou; Bin Tu; Peng Qin; Xueqin Tan; Peixiong Liu; Yunhai Kang; Yuping Wang; Weilan Chen; et al. (Theoretical and Applied Genetics, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Physiological and quantitative proteomic analyses unraveling potassium deficiency stress response in alligator weed (Alternanthera philoxeroides L.) root - Li-qin Li; Lun Liu; Wei Zhuo; Qian Chen; Sheng Hu; Shuang Peng; Xi-yao Wang; Yi-fei Lu; Li-ming Lu (Plant Molecular Biology, 2018)

Changes of functional connectivity of the anterior cingulate cortex in women with primary dysmenorrhea - Peng Liu; Yanfei Liu; Geliang Wang; Ru Li; Ying Wei; Yingying Fan; Yang Yu; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

Establishment and characterization of a kidney cell line from kelp grouper Epinephelus moara - Xiao-Feng Liu; Ya-Hong Wu; Shi-Na Wei; Na Wang; Peng-Fei Li; Yang-Zhen Li; Nian-Wei Zhang; Qi-Wei Qin; Song-Lin Chen (Fish Physiology and Biochemistry, 2018)

Risk alleles for IgA nephropathy-associated SNPs conferred completely opposite effects to idiopathic membranous nephropathy in Chinese Han - Xiaosong Qin; Chen Wang; Guanting Lu; Mengle Peng; Guixue Cheng; Hongquan Zhu; Yun Cao; Jianhua Liu; Yuzhong Li; Hong Cai; Funing Yang; Yanhong Liu; et al. (Immunologic Research, 2017)

Seasonal-related effects on ammonium removal in activated carbon filter biologically enhanced by heterotrophic nitrifying bacteria for drinking water treatment - Wen Qin; Wei-Guang Li; Xu-jin Gong; Xiao-Fei Huang; Wen-biao Fan; Duoying Zhang; Peng Yao; Xiao-ju Wang; Yang Song (Environmental Science and Pollution Research, 2017)

Two-Stage Prediction on Effects of Mixtures Containing Phenolic Compounds and Heavy Metals on Vibrio qinghaiensis sp. Q67 - Ling-Yun Mo; Jie Liu; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Bulletin of Environmental Contamination and Toxicology, 2017)

Landscape dynamics and driving forces of wetlands in the Tumen River Basin of China over the past 50 years - Xiao Jun Zheng; Peng Sun; Wei Hong Zhu; Zhen Xu; Jing Fu; Wei Dong Man; Hai Long Li; Jian Zhang; Lei Qin (Landscape and Ecological Engineering, 2017)

Solanerioside A, an unusual 14,15-dinor-cyclophytane glucoside from the leaves of Solanum erianthum - Shi-yi Peng; Hang Li; De-po Yang; Bai Bai; Long-ping Zhu; Qin Liu; Juan Shen; Zhi-min Zhao (Natural Product Research, 2017)

Analysis of the characteristics of offshore currents in the Changjiang (Yangtze River) estuarine waters based on buoy observations - Peng Li; Benwei Shi; Yaping Wang; Weihua Qin; Yangang Li; Jian Chen (Acta Oceanologica Sinica, 2017)

Patterns and drivers of soil microbial communities in Tibetan alpine and global terrestrial ecosystems - Yong‐Liang Chen; Jin‐Zhi Ding; Yun‐Feng Peng; Fei Li; Gui‐Biao Yang; Li Liu; Shu‐Qi Qin; Kai Fang; Yuan‐He Yang (Journal of Biogeography, 2016)
Aim Soil microorganisms play key roles in regulating many important ecosystem processes. However, our understanding of the patterns and drivers of soil microbial communities remains limited. This study aims to test the hypothesis that edaphic factors are more important in explaining variations in soil microbial communities than climatic and biotic factors, as soils directly provide substrates and environment for soil microbial communities. Location Tibetan alpine grasslands and global terrestrial biomes. Methods On the basis of phospholipid fatty acid ( PLFA ) analysis, we investigated large‐scale patterns and drivers of soil microbial communities using data obtained from 196 sites within two major grassland types (alpine steppe and alpine meadow) on the Tibetan Plateau. We also explored global patterns of soil microbial communities by analysing published data from around the world. Results Soil microbial PLFA s in Tibetan alpine grasslands were positively associated with mean annual temperature and mean annual precipitation ( MAP ), contradicting patterns previously observed across global biomes. A combined stepwise regression and variation partitioning analysis revealed that soil microbial community variations in Tibetan alpine grasslands were mainly explained by edaphic factors, such as soil organic carbon, C : N ratio, pH and soil texture, then by biotic factors, such as aboveground biomass and plant species richness, and further by climatic factors, such as MAP . The global analysis confirmed that edaphic factors accounted for a greater portion of the variation in soil microbial communities than did climatic and biotic variables. Main conclusions These results provide strong support for the hypothesis that edaphic factors are the dominant drivers of spatial variations in soil microbial communities across regional and global scales.

Sirtuin-3 (SIRT3) protects pancreatic β-cells from endoplasmic reticulum (ER) stress-induced apoptosis and dysfunction - Hao-Hao Zhang; Xiao-Jun Ma; Li-Na Wu; Yan-Yan Zhao; Peng-Yu Zhang; Ying-Hui Zhang; Ming-Wei Shao; Fei Liu; Fei Li; Gui-Jun Qin (Molecular and Cellular Biochemistry, 2016)

Glacier change in the western Nyainqentanglha Range, Tibetan Plateau using historical maps and Landsat imagery: 1970-2014 - Kun-peng Wu; Shi-yin Liu; Wan-qin Guo; Jun-feng Wei; Jun-li Xu; Wei-jia Bao; Xiao-jun Yao (Journal of Mountain Science, 2016)

The permafrost carbon inventory on the Tibetan Plateau: a new evaluation using deep sediment cores - Jinzhi Ding; Fei Li; Guibiao Yang; Leiyi Chen; Beibei Zhang; Li Liu; Kai Fang; Shuqi Qin; Yongliang Chen; Yunfeng Peng; Chengjun Ji; Honglin He; et al. (Global Change Biology, 2016)
The permafrost organic carbon ( OC ) stock is of global significance because of its large pool size and the potential positive feedback to climate warming. However, due to the lack of systematic field observations and appropriate upscaling methodologies, substantial uncertainties exist in the permafrost OC budget, which limits our understanding of the fate of frozen carbon in a warming world. In particular, the lack of comprehensive estimates of OC stocks across alpine permafrost means that current knowledge on this issue remains incomplete. Here, we evaluated the pool size and spatial variations of permafrost OC stock to 3 m depth on the Tibetan Plateau by combining systematic measurements from a substantial number of pedons ( i.e . 342 three‐metre‐deep cores and 177 50‐cm‐deep pits) with a machine learning technique ( i.e . support vector machine, SVM ). We also quantified uncertainties in permafrost carbon budget by conducting Monte Carlo simulations. Our results revealed that the combination of systematic measurements with the SVM model allowed spatially explicit estimates to be made. The OC density ( OC amount per unit area, OCD ) exhibited a decreasing trend from the south‐eastern to the north‐western plateau, with the exception that OCD in the swamp meadow was substantially higher than that in surrounding regions. Our results also demonstrated that Tibetan permafrost stored a large amount of OC in the top 3 m, with the median OC pool size being 15.31 Pg C (interquartile range: 13.03–17.77 Pg C). 44% of OC occurred in deep layers ( i.e . 100–300 cm), close to the proportion observed across the northern circumpolar permafrost region. The large carbon pool size together with significant permafrost thawing suggests a risk of carbon emissions and positive climate feedback across the Tibetan alpine permafrost region.

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

Low Shear Stress Inhibited Endothelial Cell Autophagy Through TET2 Downregulation - Qin Yang; Xiaohong Li; Rongqing Li; Juan Peng; Zuo Wang; Zhisheng Jiang; Xiaoqing Tang; Zhao Peng; Yu Wang; Dangheng Wei (Annals of Biomedical Engineering, 2016)

De novo transcriptome sequencing of blue honeysuckle fruit (Lonicera caerulea L.) and analysis of major genes involved in anthocyanin biosynthesis - Jun-wei Huo; Peng Liu; Yong Wang; Dong Qin; Li-juan Zhao (Acta Physiologiae Plantarum, 2016)

The Receptor-Like Cytoplasmic Kinase OsRLCK102 Regulates XA21-Mediated Immunity and Plant Development in Rice - Jing Wang; Guanwen Wu; Chunfang Peng; Xiaogang Zhou; Weitao Li; Min He; Jichun Wang; Junjie Yin; Can Yuan; Weiwei Ma; Bintian Ma; Yuping Wang; et al. (Plant Molecular Biology Reporter, 2016)

Influence of Pak choi plant cultivation on Se distribution, speciation and bioavailability in soil - Qin Peng; Lu Guo; Fayaz Ali; Jun Li; Siyue Qin; Puyang Feng; Dongli Liang (Plant and Soil, 2016)

Cloning, molecular characterization, and expression analysis of the unc45 myosin chaperone b(unc45b)gene of grass carp (Ctenopharyngodon idellus) - Jing Hu; Ting Guo; Wen-Qian Pan; Tian Gan; Jing Wei; Jun-Peng Wang; Xiang-Jun Leng; Xiao-Qin Li (Journal of Muscle Research and Cell Motility, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Genome analysis of enterovirus 71 strains differing in mouse pathogenicity - Peng Li; Yingying Yue; Nannan Song; Bingqing Li; Hong Meng; Guiwen Yang; Zhihui Li; Liguo An; Lizeng Qin (Virus Genes, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

EDARV370A associated facial characteristics in Uyghur population revealing further pleiotropic effects - Qianqian Peng; Jinxi Li; Jingze Tan; Yajun Yang; Manfei Zhang; Sijie Wu; Yu Liu; Juan Zhang; Pengfei Qin; Yaqun Guan; Yi Jiao; Zhaoxia Zhang; et al. (Human Genetics, 2016)

(−)-Epicatechin-3-gallate (a polyphenol from green tea) potentiates doxorubicin-induced apoptosis in H9C2 cardiomyocytes - Yi Cai; Hui-Qi Hong; Li Zhao; Yue-Peng Cai; Yuan Qin (Biotechnology Letters, 2015)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Linear regression model for predicting interactive mixture toxicity of pesticide and ionic liquid - Li-Tang Qin; Jie Wu; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2015)

Spatiotemporal variation of riverine nutrients in a typical hilly watershed in southeast China using multivariate statistics tools - Xiao-fei Nie; Heng-peng Li; Jia-hu Jiang; Ya-qin Diao; Peng-cheng Li (Journal of Mountain Science, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

A Time-Course Proteomic Analysis of Rice Triggered by Plant Activator BTH - Zhuo Chen; Binghua Chen; Qin Guo; Li Shi; Ming He; Zhiyang Qin; Lianhua Li; Peng He; Zhenchao Wang; Deyu Hu; Song Yang (Journal of Plant Growth Regulation, 2015)

SIRT1 overexpression in skeletal muscle in vivo induces increased insulin sensitivity and enhanced complex I but not complex II–V functions in individual subsarcolemmal and intermyofibrillar mitochondria - Hao-Hao Zhang; Gui-Jun Qin; Xia-Lian Li; Ying-Hui Zhang; Pei-Jie Du; Peng-Yu Zhang; Yan-Yan Zhao; Jing Wu (Journal of Physiology and Biochemistry, 2015)

Geissoschizine methyl ether N -oxide, a new alkaloid with antiacetylcholinesterase activity from Uncaria rhynchophylla - Wei-Wei Jiang; Jia Su; Xing-De Wu; Juan He; Li-Yan Peng; Xiao Cheng; Qin-Shi Zhao (Natural Product Research, 2015)

Determination of the Proteins Encoded by BmBDV VD1-ORF4 and Their Interacting Proteins in BmBDV-Infected Midguts - Guohui Li; Qian Zhou; Zhaoyang Hu; Peng Wang; Qi Tang; Keping Chen; Qin Yao (Current Microbiology, 2015)

Multiparameter-Based Bioassay of 2-(4-Chlorophenyl)-4-(4-methoxyphenyl) Quinazoline, a Newly-Synthesized Quinazoline Derivative, Toward Microcystis aeruginosa HAB5100 (Cyanobacteria) - Yang Zhao; Weisheng Liu; Qi Li; Qin Yang; Wenbo Chai; Mengjing Zeng; Renhui Li; Yiyuan Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Myosin II regulates actin rearrangement-related structural synaptic plasticity during conditioned taste aversion memory extinction - Ai-Ling Bi; Yue Wang; Shuang Zhang; Bo-Qin Li; Zong-Peng Sun; Hong-Sheng Bi; Zhe-Yu Chen (Brain Structure and Function, 2015)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Expression Analysis of Bombyx mori Bidensovirus Structural Proteins and Assembly of Virus-like Particles in Insect Cells - Xiaoli Pan; Peng Lü; Miaomiao Zhang; Zhaoyang Hu; Guohui Li; Shangshang Ma; Fan Feng; Keping Chen; Qin Yao (Current Microbiology, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Development of proteomic technology of shotgun and label free combined with multiple reaction monitoring to simultaneously detect southern rice black-streaked dwarf virus and rice ragged stunt virus - Zhuo Chen; Qin Guo; Bing-Hua Chen; Xiang-Yang Li; Zhen-Chao Wang; Peng He; Fei Yan; De-Yu Hu; Song Yang (VirusDisease, 2014)

Autophagy Regulates Vascular Endothelial Cell eNOS and ET-1 Expression Induced by Laminar Shear Stress in an Ex Vivo Perfused System - Fengxia Guo; Xiaohong Li; Juan Peng; Yaling Tang; Qin Yang; Lushan Liu; Zuo Wang; Zhisheng Jiang; Ming Xiao; Chuyu Ni; Ruixing Chen; Dangheng Wei; et al. (Annals of Biomedical Engineering, 2014)

The methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and tumor risk: evidence from 134 case–control studies - Min Tang; Shang-Qian Wang; Bian-Jiang Liu; Qiang Cao; Bing-Jie Li; Peng-Chao Li; Yong-Fei Li; Chao Qin; Wei Zhang (Molecular Biology Reports, 2014)

A Randomized and Controlled Multicenter Prospective Study of the Chinese Medicinal Compound Fufang Xuelian Burn Ointment for the Treatment of Superficial and Deep Second-Degree Burn Wounds - Jing Ouyang; Yong-chuan Chen; Gao-xing Luo; Hong Yan; Yi-zhi Peng; Yue-sheng Huang; Pei-yuan Xia; Qin Zhang; Zhen-jiang Liao; Guo-hui Li; Xiao-dong Yang; Yong-qing Cai (Cell Biochemistry and Biophysics, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Down-regulated Six2 by knockdown of neurofibromin results in apoptosis of metanephric mesenchyme cells in vitro - Puhui Zhou; Tielin Chen; Yin Fang; Honglian Wang; Mi Li; Pengpeng Ma; Lu He; Qianyin Li; Tianming Liu; Xianggui Yang; Fang Nie; Xiaoyan Wang; et al. (Molecular and Cellular Biochemistry, 2014)

Coffee consumption and prostate cancer risk: an updated meta-analysis - Yu Lu; Limin Zhai; Jie Zeng; Qiliu Peng; Jian Wang; Yan Deng; Li Xie; Cuiju Mo; Shi Yang; Shan Li; Xue Qin (Cancer Causes & Control, 2014)

Elevation‐induced climate change as a dominant factor causing the late Miocene C 4 plant expansion in the Himalayan foreland - Haibin Wu; Zhengtang Guo; Joël Guiot; Christine Hatté; Changhui Peng; Yanyan Yu; Junyi Ge; Qin Li; Aizhi Sun; Deai Zhao (Global Change Biology, 2014)
During the late Miocene, a dramatic global expansion of C 4 plant distribution occurred with broad spatial and temporal variations. Although the event is well documented, whether subsequent expansions were caused by a decreased atmospheric CO 2 concentration or climate change is a contentious issue. In this study, we used an improved inverse vegetation modeling approach that accounts for the physiological responses of C 3 and C 4 plants to quantitatively reconstruct the paleoclimate in the Siwalik of Nepal based on pollen and carbon isotope data. We also studied the sensitivity of the C 3 and C 4 plants to changes in the climate and the atmospheric CO 2 concentration. We suggest that the expansion of the C 4 plant distribution during the late Miocene may have been primarily triggered by regional aridification and temperature increases. The expansion was unlikely caused by reduced CO 2 levels alone. Our findings suggest that this abrupt ecological shift mainly resulted from climate changes related to the decreased elevation of the Himalayan foreland.

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Association between statin use and colorectal cancer risk: a meta-analysis of 42 studies - Yanqiong Liu; Weizhong Tang; Jian Wang; Li Xie; Taijie Li; Yu He; Yan Deng; Qiliu Peng; Shan Li; Xue Qin (Cancer Causes & Control, 2014)

Changes in some soil properties induced by re-conversion of cropland into grassland in the semiarid steppe zone of Inner Mongolia, China - Zhi-Hua Zhang; Xiao-Yan Li; Zhi-Yun Jiang; Hai-Ying Peng; Liu Li; Guo-Qin Zhao (Plant and Soil, 2013)

Tumour necrosis factor alpha (TNF-α) genetic polymorphisms and the risk of autoimmune liver disease: a meta-analysis - SHAN LI; XIAMEI HUANG; HUIZHI ZHONG; ZHIPING CHEN; QILIU PENG; YAN DENG; XUE QIN (Journal of Genetics, 2013)

Zinc fertilizer placement affects zinc content in maize plant - Yue-Qiang Zhang; Li-Li Pang; Peng Yan; Dun-Yi Liu; Wei Zhang; Russell Yost; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2013)

Cloning and characterization of a novel diacylglycerol acyltransferase from the diatom Phaeodactylum tricornutum - Yulin Cui; Guoting Zheng; Xueqin Li; Hanzhi Lin; Peng Jiang; Song Qin (Journal of Applied Phycology, 2013)

Characterizing the microbial culprit of white spot disease of the conchocelis stage of Porphyra yezoensis (Bangiales, Rhodophyta) - Xiangyu Guan; Jinbo Li; Zhe Zhang; Fuchao Li; Rui Yang; Peng Jiang; Song Qin (Journal of Applied Phycology, 2013)

Sensory–sympathetic coupling in superior cervical ganglia after myocardial ischemic injury facilitates sympathoexcitatory action via P2X7 receptor - Jun Liu; Guilin Li; Haiying Peng; Guihua Tu; Fanjun Kong; Shuangmei Liu; Yun Gao; Hong Xu; Shuyi Qiu; Bo Fan; Qicheng Zhu; Shicheng Yu; et al. (Purinergic Signalling, 2013)

Role of Endoplasmic Reticulum Stress in Aberrant Activation of Fluoride-Treated Osteoblasts - Yu-lai Zhou; Hong-yan Shi; Xi-ning Li; Peng Lv; Guang-sheng Li; Qin-yi Liu; Hui Xu (Biological Trace Element Research, 2013)

Screening and test of CD40 related signal transduction pathway in AGS cells and construction of gene silencing vector - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2013)

Association between non-steroidal anti-inflammatory drug use and melanoma risk: a meta-analysis of 13 studies - Shan Li; Yanqiong Liu; Zhiyu Zeng; Qiliu Peng; Ruolin Li; Li Xie; Xue Qin; Jinmin Zhao (Cancer Causes & Control, 2013)

Molecular characterization and phylogenetic analysis of infectious bursal disease viruses isolated from chicken in South China in 2011 - Di Liu; Xiang-Bin Zhang; Zhuan-Qiang Yan; Feng Chen; Jun Ji; Jian-Ping Qin; Hai-Yan Li; Jun-Peng Lu; Yu Xue; Jia-Jia Liu; Qing-Mei Xie; Jing-Yun Ma; et al. (Tropical Animal Health and Production, 2013)

Identification of Bombyx mori Bidensovirus VD1-ORF4 Reveals a Novel Protein Associated with Viral Structural Component - Guohui Li; Zhaoyang Hu; Xuli Guo; Guangtian Li; Qi Tang; Peng Wang; Keping Chen; Qin Yao (Current Microbiology, 2013)

Experimental analysis and application of sparsity constrained deconvolution - Guo-Fa Li; De-Hai Qin; Geng-Xin Peng; Ying Yue; Tong-Li Zhai (Applied Geophysics, 2013)

Bacillus abyssalis sp. nov., isolated from a sediment of the South China Sea - Zhi-Qing You; Jie Li; Sheng Qin; Xin-Peng Tian; Fa-Zuo Wang; Si Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Net fluxes of ammonium and nitrate in association with H+ fluxes in fine roots of Populus popularis - Jie Luo; Jingjing Qin; Fangfang He; Hong Li; Tongxian Liu; Andrea Polle; Changhui Peng; Zhi-Bin Luo (Planta, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Effect of PI3K gene silencing on growth, migration and related proteins expression of CD40 signal-mediated gastric cancer cells - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2013)

Beraprost sodium attenuates cigarette smoke extract-induced apoptosis in vascular endothelial cells - Yan Chen; Hong Luo; Naixin Kang; Chaxiang Guan; Yingjiao Long; Jun Cao; Qin Shen; Junli Li; Min Yang; Hong Peng; Ping Chen (Molecular Biology Reports, 2012)

Atorvastatin suppresses oxidized LDL-induced dendritic cell-like differentiation of RAW264.7 cells regulated by the p38 MAPK pathway - Liu-hua Hu; Tuo Zhang; Qin Shao; Dan-dan Li; Shu-xuan Jin; Peng Nie; Jing Yi; Ben He; Ling-hong Shen (Molecular and Cellular Biochemistry, 2012)

Phylogenetic analysis of the bovine parainfluenza virus type 3 from cattle herds revealing the existence of a genotype A strain in China - Yong-Jun Wen; Xin-Chuan Shi; Feng-Xue Wang; Wei Wang; Shu-Qin Zhang; Guo Li; Ni Song; Li-Zhi Chen; Shi-Peng Cheng; Hua Wu (Virus Genes, 2012)

Repairing Facial Injury with Refining Plastic Surgery Techniques - Donghong Zhao; Jiang Li; Kehua Wang; Xiaoping Guo; Yuhong Lang; Lijun Peng; Qin Wang; Yamin Li (Cell Biochemistry and Biophysics, 2012)

The nuclear localization of MGF receptor in osteoblasts under mechanical stimulation - Qin Peng; Juhui Qiu; Jiaoxia Sun; Li Yang; Bingbing Zhang; Yuanliang Wang (Molecular and Cellular Biochemistry, 2012)

Combined effect of sCD40L and PI3K siRNA on transplanted tumours growth and microenvironment in nude mice with gastric cancer - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2012)

CD40 signal expression in gastric cancer tissue and its correlation with prognosis of gastric cancer patients - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2012)

Effect of hepcidin on intracellular calcium in human osteoblasts - Guang-Fei Li; You-Jia Xu; Yin-Feng He; Ben-Cai Du; Peng Zhang; Dong-Yang Zhao; Chen Yu; Chen-Hao Qin; Kai Li (Molecular and Cellular Biochemistry, 2012)

Treating Cutis Verticis Gyrata Using Skin Expansion Method - Donghong Zhao; Jiang Li; Kehua Wang; Xiaoping Guo; Yuhong Lang; Lijun Peng; Qin Wang; Yamin Li (Cell Biochemistry and Biophysics, 2012)

Identification of genes differentially expressed during embryogenesis in Brassica campestris L. - Wenlan Li; Qin Zhao; Peng Tao; Jianbo Wang (Acta Physiologiae Plantarum, 2012)

Quantitative structure-activity relationships of antimicrobial fatty acids and derivatives against Staphylococcus aureus - Hui Zhang; Lu Zhang; Li-juan Peng; Xiao-wu Dong; Di Wu; Vivian Chi-Hua Wu; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2012)

Effects of applied urea and straw on various nitrogen fractions in two Chinese paddy soils with differing clay mineralogy - Shao-Jun Qiu; Pei-Qin Peng; Ling Li; Ping He; Qiang Liu; Jin-Shui Wu; Peter Christie; Xiao-Tang Ju (Biology and Fertility of Soils, 2012)

Reconstructions of annual summer precipitation and temperature in north-central China since 1470 AD based on drought/flood index and tree-ring records - Liang Yi; Hongjun Yu; Junyi Ge; Zhongping Lai; Xingyong Xu; Li Qin; Shuzhen Peng (Climatic Change, 2012)

Expression and function of two chaperone proteins, AtGroEL and AtGroES, from Acidithiobacillus ferrooxidans ATCC 23270 - Wenqing Qin; Qiuxia Huang; Jianyu Zhu; Peng Yang; Runlan Yu; Jiaokun Li; Xueduan Liu; Guanzhou Qiu (World Journal of Microbiology and Biotechnology, 2011)

Molecular cloning and characterization of sensory neuron membrane protein and expression pattern analysis in the diamondback moth, Plutella xylostella (Lepidoptera: Plutellidae) - Peng-Yan Li; Yu-Chuan Qin (Applied Entomology and Zoology, 2011)

β-1,4-Galactosyltransferase I Promotes Tumor Necrosis Factor-α Autocrine via the Activation of MAP Kinase Signal Pathways in Schwann Cells - Huiguang Yang; Qin Yuan; Qian Chen; Chunmiao Li; Xiujie Wu; Chen Peng; Lihua Kang; Xiang Lu; Huiqing Sun; Zhengming Zhou; Aiguo Shen; Chun Cheng (Journal of Molecular Neuroscience, 2011)

Protection of CHO cells by transfer of survivin driven by ovarian-specific promoter OSP-2 - Chun-Hua Tu; Wei-Peng Liu; Mei Dong; Li-Ping Cai; Ya-Qin Mo; Dong-Zi Yang (Molecular Biology Reports, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Silica-supported sulfonic acid-functionalized ionic liquid coated with [bmim][PF6] as a scavenger for the synthesis of amides - Li-Qin Kang; Yue-Qin Cai; Yan-Qing Peng; Xi-Li Ying; Gong-Hua Song (Molecular Diversity, 2011)

osa-MIR393: a salinity- and alkaline stress-related microRNA gene - Peng Gao; Xi Bai; Liang Yang; Dekang Lv; Xin Pan; Yong Li; Hua Cai; Wei Ji; Qin Chen; Yanming Zhu (Molecular Biology Reports, 2011)

Genetic transformation in Kappaphycus alvarezii using micro-particle bombardment: a potential strategy for germplasm improvement - Jinfeng Wang; Peng Jiang; Yulin Cui; Xiangyuan Deng; Fuchao Li; Jianguo Liu; Song Qin (Aquaculture International, 2010)

Jeotgalibacillus soli sp. nov., isolated from non-saline forest soil, and emended description of the genus Jeotgalibacillus - Yi-Guang Chen; De-Jiao Peng; Qi-Hui Chen; Yu-Qin Zhang; Shu-Kun Tang; Da-Chun Zhang; Qing-Zhong Peng; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

KCNQ1 loss-of-function mutation impairs gastric acid secretion in mice - Qin Pan; Jun Ma; Qinshu Zhou; Jun Li; Yongqing Tang; Yi Liu; Yiqing Yang; Junjie Xiao; Luying Peng; Pengjuan Li; Dandan Liang; Hong Zhang; et al. (Molecular Biology Reports, 2010)

Virgibacillus zhanjiangensis sp. nov., a marine bacterium isolated from sea water - Qing-Zhong Peng; Jun Chen; Yu-Qin Zhang; Qi-Hui Chen; De-Jiao Peng; Xiao-Long Cui; Wen-Jun Li; Yi-Guang Chen (Antonie van Leeuwenhoek, 2009)

Halobacillus hunanensis sp. nov., a moderately halophilic bacterium isolated from a subterranean brine - Qing-Zhong Peng; Qing-Jing Peng; Yu-Qin Zhang; Zhu-Xiang Liu; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui; Yi-Guang Chen (Antonie van Leeuwenhoek, 2009)

Virgibacillus litoralis sp. nov., a moderately halophilic bacterium isolated from saline soil - Yi-Guang Chen; Zhu-Xiang Liu; De-Jiao Peng; Yu-Qin Zhang; Yong-Xia Wang; Shu-Kun Tang; Wen-Jun Li; Xiao-Long Cui; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

SSR and SCAR mapping of a multiple-allele male-sterile gene in Chinese cabbage (Brassica rapa L.) - Hui Feng; Peng Wei; Zhong-Yun Piao; Zhi-Yong Liu; Cheng-Yu Li; Yu-Gang Wang; Rui-Qin Ji; Shu-Juan Ji; Ting Zou; Su-Ryun Choi; Yong-Pyo Lim (Theoretical and Applied Genetics, 2009)

Microprojectile bombardment of Laminaria japonica gametophytes and rapid propagation of transgenic lines within a bubble-column bioreactor - Xiangyuan Deng; Song Qin; Qun Zhang; Peng Jiang; Yulin Cui; Xiaokun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

The integrative expression of GUS gene driven by FCP promoter in the seaweed Laminaria japonica (Phaeophyta) - Fuchao Li; Song Qin; Peng Jiang; Yun Wu; Wei Zhang (Journal of Applied Phycology, 2009)

Association of polymorphisms at restriction enzyme recognition sites of apolipoprotein B and E gene with dyslipidemia in children undergoing primary nephrotic syndrome - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Feng Ying Lei; Ping Chen; Ming Fang Li (Molecular Biology Reports, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Antitumor activities of D-glucosamine and its derivatives - Li Zhang; Wan-shun Liu; Bao-qin Han; Yan-fei Peng; Dong-feng Wang (Journal of Zhejiang University-SCIENCE B, 2006)

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population - Weiying Jiang; Guolong Yu; Peng Liu; Qian Geng; Luming Chen; Qundi Lin; Xiaoqin Ren; Wenhong Ye; Yongshu He; Yibin Guo; Shan Duan; Jing Wen; et al. (Human Genetics, 2006)

Vitreoscilla hemoglobin overexpression increases submergence tolerance in cabbage - Xian Li; Ri-He Peng; Hui-Qin Fan; Ai-Sheng Xiong; Quan-Hong Yao; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2005)

Different effects on ACC oxidase gene silencing triggered by RNA interference in transgenic tomato - Ai-Sheng Xiong; Quan-Hong Yao; Ri-He Peng; Xian Li; Pei-Lai Han; Hui-Qin Fan (Plant Cell Reports, 2005)

Developmental analyses reveal early arrests of the spore-bearing parts of reproductive organs in unisexual flowers of cucumber (Cucumis sativus L.) - Su-Lan Bai; Yi-Ben Peng; Ji-Xin Cui; Hai-Tao Gu; Li-Yun Xu; Yi-Qin Li; Zhi-Hong Xu; Shu-Nong Bai (Planta, 2004)

Nectar production and transportation in the nectaries of the female Cucumis sativus L. flower during anthesis - Yi-Ben Peng; Yi-Qin Li; Yu-Jin Hao; Zhi-Hong Xu; Shu-Nong Bai (Protoplasma, 2004)

DNA damage in the early primordial anther is closely correlated with stamen arrest in the female flower of cucumber ( Cucumis sativus L.) - Yu-Jin Hao; Dong-Hui Wang; Yi-Ben Peng; Su-Lan Bai; Li-Yun Xu; Yi-Qin Li; Zhi-Hong Xu; Shu-Nong Bai (Planta, 2003)

Angiostatin production in cultivation of recombinant Pichia pastoris fed with mixed carbon sources - Jingli Xie; Li Zhang; Qin Ye; Qingwei Zhou; Li Xin; Peng Du; Renbao Gan (Biotechnology Letters, 2003)

Review of genetic engineering of Laminaria japonica (Laminariales, Phaeophyta) in China - Song Qin; Guo-Qiong Sun; Peng Jiang; Li-Hong Zou; Yun Wu; Cheng-Kui Tseng (Hydrobiologia, 1999)